Fabrication and application of carbon sequestration grouting material for sealing leakages in mine strata - Jing Mei; Jianwei Cheng; Shuping Sheng; Yejiao Liu; Zhiyuan Ma; Qiang Fu; Dezhi Ran (European Journal of Environmental and Civil Engineering, 2026)

Comparative genomic epidemiology of food- and patient-derived diarrheagenic Escherichia coli from sentinel surveillance in Southeast China - Xiaomeng Huang; Li Gong; Fuming Liu; Jianhua Mei; Jinkai Li; Siyu Fu; Liyang Qiu; Deyong Zhang; Xiuying Chen (International Journal of Food Microbiology, 2026)

Monsoon intensification as a driver of enhanced biogenic silica burial during the Bajocian cooling event in the western Yarlung Zangbo Suture Zone, southern Tibet - Xiaohui Cui; Xin Li; Jonathan C. Aitchison; Mei-Fu Zhou; Yichun Zhang; Jun Chen; Xuejin Wu; Xiru Li; Jiaqi Song; Hui Luo (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

TBBPA facilitates splenic inflammation and pyroptosis by targeting HMGB1 - Fu-Wei Jiang; Jing-Han Lin; Jia-Xin Wang; Ming-Shan Chen; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Ming Lou; Zi-Yan Hu; Yi Zhao; Jin-Long Li (Journal of Environmental Sciences, 2026)

Hierarchical assembly of sub-1 nm nanowire for the construction of aerogels - Yuxiang Du; Xin Yang; Xiuqin Mei; Ran Du; Dan Liu; Changqing Miao; Rui Fu; Huazheng Sai (Chemical Engineering Journal, 2026)

AIE-active photoresponsive Ir(III) complex as an oxidase mimic for ratiometric ascorbic acid detection - Qianghui Zheng; Ping Huang; Ying Peng; Mei-Jin Li; Fengfu Fu (Analytica Chimica Acta, 2026)

Rapid and sensitive on-site detection of PBoV G3 using an EsCas13d-based platform - Peng-fei Fu; Zhuo-wei Zhang; Jun Hong; An-xin Hu; Yi-yang Shi; Jia-wen Lin; Si-yi Pi; Yu-yan Zhang; Yan-hong Wang; Min Lu; Guo-you Yin; Dong-mei Wang (Analytica Chimica Acta, 2026)

Scalable nanoconfined GO/SWCNT-OH membranes for efficient high-salinity organic wastewater treatment - Yechen An; Xiaoxu Gao; Jing-Long Han; Yuting Ning; Xinping Fu; Ruiyun Ren; Liang Mei; Wenli Jiang; Ruifeng Yan; Jun Cui; Yu Tao; Aijie Wang (Water Research, 2026)

Enhanced solar-driven interfacial vapor generation of lignite-based aerogel via water and thermal dual management - Mei Xiong; Hong-Lei Yan; Zhan-Ku Li; Wei-Dong Zhang; Jing-Chong Yan; Zhi-Ping Lei; Zhao Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui (Journal of Environmental Chemical Engineering, 2026)

Short-chain fatty acid-acylated high-amylose maize starch: Synthesis, physicochemical properties, and biomedical applications - Mei Guo; Lixin Fu; Quanbo Wang; Charles R. Mackay (Food Bioscience, 2026)

The ISChip: A high-throughput qPCR array for absolute quantification of insertion sequences across the One Health continuum - Yanyan Zhou; Wen-Jing Zhong; Xin-Li An; Fu-Yi Huang; Xiao-Yu Guo; Meng-Ke Gao; Mei-Rong Xu; Xu Huang; Hu Li; Bangzhou Zhang; Dirk Springael; Jian-Qiang Su (Environmental Pollution, 2026)

A dynamic DNA nanoconstruct-integrated hydrogel: Reprogramming osteoimmune for diabetic bone defect repair - Mei Zhang; Xiao Fu; Zhen Zhao; Yiliu Zhou; Jiahui Xiong; Bo Huang; Yao He; Zhiqiang Liu; Yunfeng Lin (Chemical Engineering Journal, 2026)

Multi-environmental biodegradation of a cellulose-based/polylactic acid non-leaching antibacterial composite membrane - Xianpei Xu; Hongbo Wang; Junming Liang; Youbo Di; Mei Liu; Fu Li; Pengfei Fei (Biomass and Bioenergy, 2026)

Plant diversity drives grassland restoration by enhancing belowground ecosystem multifunctionality - Meili He; Chunyang Fu; Mei Hua; Wanjie Chen; Lingling Chen (Agriculture, Ecosystems & Environment, 2026)

Rhizophagus intraradices differentially promotes growth and phosphorus uptake in Camellia oleifera under low versus adequate phosphorus supply - Wan-Lin Fu; Ying-Ning Zou; Shi-Qi Pu; Fang-Ling Wang; Zhi-Yan Xiao; Jun-Yong Cheng; Mei-Hua Yang; Mashael Daghash Alqahtani; Qiang-Sheng Wu (Rhizosphere, 2026)

Assessing the impacts of ecotourism on perceived ecosystem services and livelihoods: a case study in the Hani Terraces, China - Zhongde Huang; Degui Fu; Maroof Ali; Zhengchang Ma; Mei Li; Xiong Luo; Anjian He; Yang Bai (Journal of Outdoor Recreation and Tourism, 2026)

Oral exposure to non-brain-penetrable microplastics induces neurotoxicity via disrupting the gut microbiota−tryptophan metabolism−microglial autophagy cascade - Yulong Wu; Zhouyan Dong; Dong Wang; Jiayi Dong; Xinze Jiang; Guangcheng Fu; Mei Cheng (Journal of Hazardous Materials, 2026)

Low-molecular-weight soybean peptides alleviate hyperuricemia in mice through xanthine oxidase inhibition, gut microbiota modulation, and metabolic reprogramming - Chen Wang; Jin Qian; Jiajing Liao; Lijuan Rao; Sen Mei; Bing Yuan; Tingting Geng; Haowei Fan; Guiming Fu; Yin Wan (Food Bioscience, 2026)

Heavy sulfur isotope of arc ultramafic cumulates revealed by S-rich apatite from the Dongwanzi intrusion, North China - Huan Jennifer Chang; Mei-Fu Zhou; Wen-Jun Hu; Shengbiao Yang; Jian-Feng Gao (Chemical Geology, 2026)

Vegetable waste into soil acts as slowly released water and fertilizer to improve current vegetable productivity with less chemical fertilization - Adnan Khan; Ling Zhao; Jing Wang; Yun-Li Xiao; Jian-Ming Li; Hua-Guo Zhu; Shi-Sheng Li; Meng-Ying Li; Habimana Evode; Chang Nan; Muhammad Ashraf; Fu-Jian Mei; et al. (Bioresource Technology, 2026)

Disruption of intestinal mucosal immunity and microbial homeostasis in Schizothorax davidi under chronic DBP exposure: From functional compensation to transcriptional decompensation - Luo Lei; Rongrong Liao; Mei Peng; Yinhua Zhou; Chang Xiao; Xiayu Yu; Shuang Liu; Yuting Duan; Suxing Fu; Hejiao Li; Can Liu; Xiao Chen; et al. (Aquatic Toxicology, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Dimeric 2-(2-phenethyl)chromones from agarwood of Aquilaria malaccensis - Wei Li; Xian-Yun Yan; Hao Wang; Li Yang; Sheng-Zhuo Huang; Jun Zeng; Fei Wu; Guang-Ying Chen; Wen-Li Mei; Lin-Fu Liang; Hao-Fu Dai; Yong-Min Zhang (Phytochemistry, 2026)

Corrigendum to “Assessing the impacts of ecotourism on perceived ecosystem services and livelihoods: a case study in the Hani Terraces, China” [Journal of Outdoor Recreation and Tourism 55 (2026) 101077] - Zhongde Huang; Degui Fu; Maroof Ali; Zhengchang Ma; Mei Li; Xiong Luo; Anjian He; Yang Bai (Journal of Outdoor Recreation and Tourism, 2026)

Constraints of integrated Fe and Li isotopes on fractional crystallization and fluid-magma interaction in the formation of unzoned Li-mineralized pegmatites - Shuaijie Liu; Mona-Liza C. Sirbescu; Bin Chen; Wenjing Li; Mei-Fu Zhou (Geochimica et Cosmochimica Acta, 2026)

Reactivity of calcined shale gas drilling cuttings as supplementary cementitious materials: Competing mechanisms of phase evolution, mineral structure and microstructure - Chao Liu; Zhi Fu; Kun Huang; Chunmei Zhang; Kaiyuan Mei; Xiaowei Cheng (Environmental Research, 2026)

Rational design of phosphide catalyst for high-performance vanadium redox flow batteries - Yadong Xu; Hao Cheng; Mei Ding; Xiaolei Huang; Jian Xu; Su Yan; Hu Fu; Ming Yang; Chuankun Jia (Chemical Engineering Journal, 2026)

Ovarian Development in Channa argus var.: Joint Mediation by Melatonin, the cAMP Signaling Pathway, and the PI3K-Akt Signaling Pathway in Response to Photoperiod - Hejiao Li; Yuting Duan; Rongrong Liao; Yinhua Zhou; Jian Su; Xinyu Liu; Tinghui Xia; Yixin Luan; Mei Peng; Suxing Fu; Benhe Zeng; Luo Lei; et al. (Marine Biotechnology, 2026)

The role of fractional crystallization in the formation of unzoned Li-mineralized pegmatites: insights from in situ apatite geochemistry - Shuaijie Liu; Mei-Fu Zhou; Huan Chang; Bin Chen; Hui Zhao (Contributions to Mineralogy and Petrology, 2026)

Synthesis and biological evaluation of Phorbazole D analogues identify IO-5a as a promoter of hUC-MSC chondrogenic differentiation - Ai-zhu Wang; Xiao-mei Liu; Li-ming Zhang; Lu-lu Fu; Ping Li; Jie-ping Zhang; Hua Han (Molecular Diversity, 2026)

Preparation and characterisation of two new malonylated rare ginsenosides by acid hydrolysis and their anti-hepatoma activities - Ya-Qian Lu; Xiao-Man Jin; Fu-Rui Zhang; Mei-Hui Li; Wen-Wen Li; Wei Li; Chun-Su Yuan; Zhi Liu (Natural Product Research, 2026)

Bio-matrix film mulching enhances Salvia miltiorrhiza quality by reprogramming the rhizosphere microbiota and activating the secondary metabolic pathway - Jin Xu; Yan Wang; Bing Zhao; Yi-Hao Liu; Mao-Qiang He; Yun-Fu Gu; Xiu-Mei Yu; Qiang Chen (Soil and Tillage Research, 2026)

The role of water in REE mineralization of carbonatite systems: constraints from apatite and biotite volatiles - Jian-Hui Su; Xin-Fu Zhao; Johannes Hammerli; Sheng-Ren Chang; Xiao-Chun Li; Wen-Lei Song; Mei-Fu Zhou (Geochimica et Cosmochimica Acta, 2026)

Autotetraploid induction and one-step regeneration, and transcriptomic analysis in Dendrobium officinale - Cong-Dan Zheng; Jun-Yu Su; Shang-Yan Fu; Jie-Mei Deng; Zi-Ting Zhu; Heng-Yu Huang; Yuan-Zhong Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

A novel C17-sesquiterpene alkaloid derived from Dendrobium huoshanense : in vitro evaluation of its anti-lung cancer activity and molecular dynamics simulation study - Jun Chen; Xiu-Mei Li; Yong-Peng Sun; Ya-Feng Dai; Shi-Hao Li; Nai-Fu Chen; Nai-Dong Chen (Natural Product Research, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

Soil water and inorganic nitrogen contents drive soil microbial carbon fixation during wetland reclamation and restoration - Jia Qi; Yanyu Song; Shouyang Luo; Mengyuan Zhu; Fangcong Fu; Yisong Feng; Wenkai Mei; Huanhuan Feng; Xiaoyu Li; Changchun Song (Water Research, 2026)

Chemical constituents from the stem of Nauclea officinalis and their anti-inflammatory activities - Bo Wen Wan; Ting Wang; Xiong Bo Zhu; Rui Hua Xu; Hao Fu Dai; Wen Li Mei; Fei Wu; Xiao Ying Peng; Sheng Zhuo Huang (Phytochemistry Letters, 2026)

Brachiopods and associated skeletal taxa from the early Cambrian of southeastern Shaanxi, South China - Mei Luo; Timothy P. Topper; Guoxiang Li; Baopeng Song; Zhao Wang; Caibin Zhang; Jingliang Zhao; Peiyao Wang; Rao Fu; Fan Liu; Zhifei Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Ophiolites in Pakistan: Key evidence for the geodynamic evolution of the Neo-Tethys Ocean - Inayat Ullah; Peng-Fei Zhang; Wen-Jun Hu; Mei-Fu Zhou (Journal of Asian Earth Sciences, 2026)

Functional characterization of chemosensory proteins in Pharsalia antennata with special emphasis on the roles of CSP2 orthologs in pheromone detection - Fu-Peng Li; Xiao-Rong Xiong; Zi-Hui Liu; Zi-Hao Long; Lin-Mei Pu; Nai-Yong Liu (Insect Biochemistry and Molecular Biology, 2026)

Mg–K isotopic compositions deciphering mantle heterogeneity beneath southeast Tibet - Qiong Chen; Hao Cheng; Guo-Chun Zhao; Mei-Fu Zhou; Ping-Ping Liu; Wen-Jun Li; Min Sun (Geochimica et Cosmochimica Acta, 2026)

The Lhasa Terrane: A tale of two origins and its convergence at the Northern Margin of Gondwana - Chang-Sheng Yu; Mei-Fu Zhou; Ming Wang; Jian-Bo Zhou; Wen-Jun Hu (Earth-Science Reviews, 2026)

λ-Carrageenan inhibits African swine fever virus infection potentially through its interaction with the viral envelope protein CD2v - Kun Han; Limeng Sun; Can Jin; Siqi Wan; Caiqin Cao; Yulu Yue; Man Lu; Xiaotong Wang; Yi Zheng; Hailong Liu; Yilin Guo; Dagang Tao; et al. (Carbohydrate Polymers, 2026)

Fish community and its relationships with environmental factors in the Jiupan River, a secondary tributary of the Three Gorges Reservoir - Junquan Ren; Zhenxin Chen; Kaiyang Wu; Lilong Chen; Rongchao He; Mengqiao Long; Yankun Shen; Hanlin Wang; Mei Fu; Hongjian Lv; Weizhi Yao (Environmental Biology of Fishes, 2026)

The role of biological uptake, coalification and hydrothermal overprinting on the formation of coal-hosted Ge deposits - Hao-Yu Sun; Mei-Fu Zhou (Journal of Asian Earth Sciences, 2026)

Large-scale gold incorporation in bulk pyrite mediated by arsenic - Zi-Yue Gao; Kun-Feng Qiu; Razvan Caracas; Bing-Cheng Luo; Xin Liu; Zheng-Yu Long; Deng-Yang He; Jia-Nan Fu; Mei-Jing Xu; Hao-Cheng Yu; Zheng-Jiang Ding; Jun Deng (Geochimica et Cosmochimica Acta, 2026)

Flavor characterization of Chenxiang-type baijiu-Daoguang nianwu aged in wooden Jiuhai with different vintages integrating GC-E-nose, GC-IMS, GC-MS-O, ROAV and chemometrics approaches - Na Wang; Xiangyang Zhang; Li Xue; Zhen Zhang; Li Fu; Xuejiao Ren; Hui Zhang; Bo Zhang; Xiaoyu Jiang; Lili Zhang; Mei Wang (Food Research International, 2026)

High-low seedbed planting increases wheat productivity by optimizing the utilization of light and water resources and grain-filling strategies - Jia-Ju Dong; Shou-Tian Ma; Fu-Jian Mei; Shou-Chen Ma; He-Bing Zhang (Field Crops Research, 2026)

Dual-crosslinked polysaccharide microspheres via glycated collagen and sodium alginate/chitosan for intestine targeted delivery of curcumin in ulcerative colitis treatment - Jing-jing Fu; Si-yi Mei; Yong-qiang Chen; Xiang-yu Fu; Yong-jie Long; Jun-xin Wu; Wen-qiang Cai; Yue-wen Chen (Carbohydrate Polymers, 2026)

Responses of greenhouse gases emissions from wetland soils to the interactive effects of nitrogen input and warming in Sanjiang Plain, China - Yisong Feng; Wenkai Mei; Yanyu Song; Fangcong Fu; Mengyuan Zhu; Shouyang Luo; Changchun Song (Applied Soil Ecology, 2026)

Nitrogen inhibitors enhance ecosystem multifunctionality through microbial networks in alpine grasslands of the Tibetan Plateau - Fang-Kun Yang; Peng-Yang Wang; Ze-Yang Liu; Fu-Ying Niu; Cheng-Yi Xie; Yi-Ming Gao; Yan-Mei Ma; Yu-Xing Wang; Jia-Cheng Guo; Wen-Ying Wang (Applied Soil Ecology, 2026)

Evaluation of Taxonomic Positions of Robertmurraya yapensis Hitch et al. 2025, Bacillus yapensis Xu et al. 2025, Pseudonocardia saturnea (Hirsch 1960) Warwick et al. 1994 and Pseudonocardia autotrophica (Takamiya and Tubaki 1956) Warwick et al. 1994 - ZhouYan Dong; Guangcheng Fu; Paula Andrea Santana Sepúlveda; Neeta Raj Sharma; Syed Raziuddin Quadri; Mei Cheng; Manik Prabhu Narsing Rao; Yulong Wu (Current Microbiology, 2026)

Novel Models to Predict Pregnancy for Patients Receiving In-Vitro-Fertilization Embryo Transfer: The Significance of Clinical Indicators and Key Gene Expression in the Endometrium - Cheng Shi; Yan-Bin Wang; Huan Shen; Fu-Mei Gao; Min Fu; Xi Chen; Hong-Jing Han (Biochemical Genetics, 2026)

Dual effects of tidal stress on carbon turnover by biochar incorporation in estuarine wetlands: Obscuring the promotion of plant CO2 fixation while magnifying carbon stabilization of sediments - Wenxuan Mei; Haoyu Dong; Xiaoyu Gao; Haoting Liu; Lin Liu; Wei Wu; Xiaohua Fu; Lei Wang (Water Research, 2026)

Comprehensive diversity index for microplastics provides insight into lake pollution sources - Yuan Zhao; Yi Yu; Yidan Gai; Xiutong Xiao; Yuxin Fu; Ziyi Nie; Mei Feng; Renjun Wang; Changchao Li; Yandong Gan; Ying Liu (Journal of Hydrology, 2026)

Stronger functional coupling rather than enhanced ecosystem multifunctionality in mangrove mixed-species plantations versus monocultures - Zhigao Fu; Mei Li; Kun Xin; Yujun Chen; Danwei Wang; Yanpeng Li (Journal of Environmental Management, 2026)

Oceanic deoxygenation linked to enhanced water column stratification in the eastern Tethys during Cretaceous Oceanic Anoxic Event 2 - Yu Liang; Yong-Xiang Li; Hongxuan Lu; Huanye Wang; Cece Wang; Cheng Quan; Weiguo Liu; Mei-Fu Zhou; Zhonghui Liu (Global and Planetary Change, 2026)

Competition release dominates growth recovery of four subtropical broadleaved tree species following an extreme snow event - Tong-Liang Xu; Rao-Qiong Yang; Zaw Zaw; Shankar Panthi; Xin-Hua Peng; Ju-Mei Zhang; Pei-Li Fu; Ke-Yan Fang; Ze-Xin Fan (Forest Ecology and Management, 2026)

Effect of roasting on the chemical profiles of white and black sesame seeds during accelerated storage - Hao Liu; Shu-Guang Gao; Ming-Zhe Sun; Mei-Qi Yang; Huai-Yang Cao; Ke-Xin Zhang; Min-Shu Hong; Rui-Fu Cui; Zhao Qin; Hua-Min Liu; Xue-Ya Wang; Zhi-Jie Li (Food Chemistry, 2026)

Ionic liquid-mediated concurrent oxygen vacancies and N-doped carbon in hierarchical TiP2O7 for lithium storage - Wenfang Cui; Yongmei Sun; KeYu Zhang; Chengcheng Shi; Peng Fu; Mei Ma (Chemical Engineering Journal, 2026)

Two new compounds from Atractylodes japonica Koidz. ex Kitam - Mei Yi; Jing Wang; Jie Sun; Yan Liu; Zhen-Xing Fang; Lei Fu; Yuan-Yuan Zhou (Natural Product Research, 2026)

Comprehensive analysis of Salvia uliginosa extract: HPLC-MS, GC-MS and evaluation of antioxidant and neuroprotective effects - Yang-xin Liao; Zi-fu Wang; Peng Zhao; Shi-mei Liao; Jia-wei Tang; Shi-jun Hu; Dong-hua Zhang; Xiao-hui Yan (Natural Product Research, 2026)

TMEM158-mediated TGF-β signaling pathway modulates the sensitivity of TP53-deficient osteosarcoma to USP14 inhibitors - Zi-Yu Chen; Miersalijiang Yasen; Song-Yao Jiang; Zi-Yi Ye; Qin-Xin Yang; Cui-Ni Lu; Yi Shi; Xin-Yun Liu; Ting-Ting Du; Xiao-Mei Tang; Da Fu; Yu-Shui Ma; et al. (Molecular and Cellular Biochemistry, 2026)

Eliminating Microcystis aeruginosa and secondary pollutants via photo-Fenton process over Iron-MOF - Hong- Yu Chu; Zheng-Xing Liu; Jian-Feng Wang; Xuchun Qiu; Fu-Xue Wang; Shao-Long Chen; Hui-Min Yu; Fei Wang; Guang-Chi Liu; Ruo-Xuan Mei; Xin-Jie Li; Xiao-Hang Xu; et al. (Water Research, 2026)

Two unprecedented 2-(2-phenylethyl)chromone dimers from the Cambodian agarwood of Aquilaria crassna - Yan Huang; Hao Wang; Wen-Li Mei; Hui-Qin Chen; Fei Wu; Yan-Mei Wei; Wen-Ming Cheng; Hao-Fu Dai (Phytochemistry Letters, 2026)

Mercury isotope perspectives on vegetation-enhanced nickel mobilization and migration during laterite formation - Ruo-Lin Liu; Martin Yan Hei Li; Run-Sheng Yin; Mei-Fu Zhou; Jun-Hong Zhao (Geochimica et Cosmochimica Acta, 2026)

Association of arsenic exposure with adverse birth outcomes: A meta-analysis and a benchmark dose analysis - Haoqi Jia; Nan Jing; Zhaomin Zhong; Xiaole Zhu; Tongbo Jin; Qianlei Yang; Yuanjie Wei; Yuanhui Zhu; Tingxu Jin; Lan Lan; Ying Mei; Huai Hu; et al. (Environmental Research, 2026)

Energy-saving and fire/water-resistant recyclable aerogel coatings for thermal-insulating polyurethane foam - Cong-Mei Lin; Xue-Lian Chen; Fu-Rong Zeng; Li-Xiao Hao; Yu-Shi Wen; Bing-Ru Zhang; Bo-Wen Liu; Lin Zhang; Hai-Bo Zhao (Chemical Engineering Journal, 2026)

Defect passivation with Pb for high-performance Sb2S3 solar cells via vapor transport deposition - Gan Huang; Xin-Yi Cai; Hu Li; Jin-Rui Cai; Ying-Sen Xia; Zhi-Ping Huang; Li-Mei Lin; Fu-Bao Gong; Shui-Yuan Chen; Gui-Lin Chen (Chemical Engineering Journal, 2026)

Lanostane triterpenoids from the fruiting bodies of Ganoderma multipileum and their anti-inflammatory activities - Mei-Juan Li; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Jiao-Cen Guo; Hao-Fu Dai; Yan Hua; You-Xing Zhao (Natural Product Research, 2026)

The hazards and resource utilization of construction and demolition waste - Yanan Zhang; Bensen Xian; Chenchen Liao; Ruifang Lu; Wenkai Sun; Mei Wang; Shaoyuan Bai; Qin Zhang; Huili Liu; Dandan Xu; Mingming Fu (Journal of Environmental Management, 2026)

Evaluation of genetic diversity and construction of a core collection in multiploidy heterodichogamous Cyclocarya paliurus using SSR markers - Di Mei; Li Liu; Xulan Shang; Xiangxiang Fu (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

Unraveling the drivers of corn yield response to optimization fertilization in plateau acidic red soils - Zhengfa Chen; Keyu Yan; Hui Yan; Xiaohan Mei; Chi Wang; Xingwei Chen; Wanli Hu; Bin Fu; Ming Ni; Zhiwu Li; Qingsong Duan; Yanmei Hu; et al. (Field Crops Research, 2026)

Atomically dispersed Pd on WO3/WS2 nanoflowers for fast hydrogen detection - Jingyun Li; Fanfang Meng; Mei Zhu; Hao Lv; Yanlong Gong; Xiaohong Yang; Jiangcheng Li; Shixian Xiong; Haitao Fu; Xizhong An (Chemical Engineering Journal, 2026)

Phosphazene derivative synergistically reinforced flexible silicone rubber composites for extreme thermal protection at 2100 °C - Zhao Lu; Yisen Huang; Zhaohui Lu; Xiaochuang Di; Chuxiang Zhou; Hongbin Tian; Bojie Fu; Liwei Yan; Mei Liang; Yang Chen; Huawei Zou (Chemical Engineering Journal, 2026)

Traditional Chinese medicine and natural small molecules for pain treatment via voltage-gated sodium channels: a review - Zhen Zhang; Fu-Yu Xie; Yue Zhang; Meng-Xia Wu; John N. Wood; Chao-Mei Fu; Ahmed M. M. Mahmoud (Phytochemistry Reviews, 2026)

APOE Lipoprotein Particles: Pathophysiology, Therapy, and the Crosstalk in Alzheimer’s Disease and Cardiovascular Disease - Chan Liu; Juan Liu; Yan-Yang Wang; Shang-Fu Xu; Li-Mei Yu (Molecular Neurobiology, 2026)

Soil CO2-fixation by cbbL-harboring microorganisms in different types of permafrost peatlands - Yanyu Song; Xianwei Wang; Huanhuan Feng; Shouyang Luo; Jia Qi; Jiusheng Ren; Yisong Feng; Wenkai Mei; Fangcong Fu; Yiting Zhao; Changchun Song (Applied Soil Ecology, 2026)

Two new 2-(2-phenylethyl)chromone dimers from agarwood of Aquilaria malaccensis - Lin Zhang; Wei Li; Hao Wang; Jun Zeng; Wen-Hua Dong; Bei Jiang; Jing-Zhe Yuan; Fei Wu; Wen-Li Mei; Hao-Fu Dai (Phytochemistry Letters, 2025)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Enhanced degradation of pharmaceutical contaminants by medium-pressure UV irradiation in the presence of nitrate: Reactive species, toxicity and DBPs formation - Xiang-mei Zhong; Xiang Fu; Yu-qiong Gao; Yang-yang Liu; Xue-ting Ren; Ji-yue Li; Lei Li; Nai-yun Gao (Environmental Research, 2025)

Bacterial network complexity drives carbon, nitrogen and phosphorus metabolism potential under short-term soil water content changes in wetlands - Shouyang Luo; Jiabao Yuan; Yanyu Song; Jia Qi; Mengyuan Zhu; Huanhuan Feng; Yiting Zhao; Wenkai Mei; Fangcong Fu; Xiaoyu Li; Changchun Song (Environmental Research, 2025)

Climatic influences on annual and intra-annual xylem anatomical traits of four coniferous tree species in the central Hengduan Mountains, Southwest China - Ju-Mei Zhang; Zaw Zaw; Pei-Li Fu; Shankar Panthi; Jambay Dema; Tong-Liang Xu; Hui Zhang; Achim Bräuning; Ze-Xin Fan (Dendrochronologia, 2025)

Regulatory effects of organic compound L-glutamic acid on multi-scale structural characteristics of starch in high-quality wheat under post-anthesis drought stress - Gang Li; Jialian Wei; Kaiyong Fu; Mei Yan; Gelin Liu; Shiya Qu; Chunyan Li; Cheng Li (Carbohydrate Polymers, 2025)

Pluvial flood warnings in a tidally influenced basin enhanced by rainfall–tide compound indicators: Taipei case study - Mei-Ying Lin; Wen-Yih Sun; Huei-Syuan Fu; Chih-Hsin Chang; Wei-Bo Chen; Chieh-Ju Wang; Hsuan-Wei Wang; Yi-Chiang Yu; Yen-Wei Li (Stochastic Environmental Research and Risk Assessment, 2025)

Associations between parental shift work exposure and pregnancy outcomes: role of father’s shift work status - Chih-Fu Wei; Mei-Huei Chen; Ching-Chun Lin; Yueliang Leon Guo; Shio-Jean Lin; Ya-Wen Chen; Wu-Shiun Hsieh; Pau-Chung Chen (International Archives of Occupational and Environmental Health, 2025)

Pivotal epitopes for islet antigen-specific CD8+ T cell detection improve classification of suspected type 1 diabetes with the HLA-A*0201 allele - Yang Chen; Min Shen; Yong Gu; Xinyu Xu; Lingling Bian; Fan Yang; Shuang Chen; Li Ji; Jin Liu; Jing Zhu; Zheng Zhang; Qi Fu; et al. (Immunologic Research, 2025)

Correction: Effects of 12-week free sprint training and speed, agility, and quickness training (SAQT) on reaction time and lower limb muscle activation during crouch start - Yu-Hua Chang; Mei-Hsuan Wu; Kuei-Fu Lin; Kok-Hwa Tan (European Journal of Applied Physiology, 2025)

Effects of 12-week free sprint training and speed, agility, and quickness training (SAQT) on reaction time and lower limb muscle activation during crouch start - Yu-Hua Chang; Mei-Hsuan Wu; Kuei-Fu Lin; Kok-Hwa Tan (European Journal of Applied Physiology, 2025)

Rapid virus detection by primer-independent linear rolling circle amplification combined with DNA-templated silver nanoclusters - Jingpu Zhang; Fahui Dai; Yejing Shi; Peng Zou; Xiao Zhi; Mei Liu; Nannan Wu; Tie Fu Liu (Analytica Chimica Acta, 2025)

The effects of carbon-14 exposure on photosynthetic energy metabolism and carbon metabolism in microalgae - Mei Tao; Jinlong Lai; Yan Huang; Qian Fu; Yu Zhang; Xuegang Luo (Journal of Environmental Radioactivity, 2025)

Spatiotemporal evolution patterns of mining-induced overburden damage based on microseismic event response analysis - Xiao Yang; Longqing Shi; Mei Qiu; Jin Han; Xingyue Qu; Song Fu (Journal of Applied Geophysics, 2025)

Supersaturation mechanisms and regulation strategies in nucleation-induced crystallization for high-purity fluoride recovery from photovoltaic wastewater - Zhihao Fu; Yadong Wang; Xuan Shi; Danheng Zhou; Zhilin Li; Pengkang Jin; Kunhao Li; Guohua Zhang; Ang Mei; Bingjie Sun; Yun Zhang (Chemical Engineering Journal, 2025)

Androgen induces 3′UTR shortening of de novo lipogenesis genes by alternative polyadenylation in prostate cancer cells - Wei-Jie Sun; Fei Liang; Hui Zhao; Yun-Mei Wang; Zhong-Yin Zhou; Hui Xu; Hang Liu; Dong Tang; An-Long Xu; Yong-Gui Fu; Xi Li; Jun Ouyang; et al. (Science China Life Sciences, 2025)
Alternative polyadenylation (APA) is a pervasive mechanism that is emerging as a formidable player in post-transcriptional regulation. The transcriptional landscape can be altered via APA in response to various stimulating factors. Using the PacBio single-molecule long-read sequencing method, we present for the first time the 3′UTR landscape and reveal a global increase of APA events in prostate cancer (PCa) LNCaP cells in response to androgen dihydrotestosterone (DHT), a critical regulator of PCa progression. With evidence from differential gene expression analyses of Illumina RNA-sequencing data, we demonstrated that genes with DHT-induced changes in both expression and APA were enriched in lipid metabolism. These genes predominantly supported de novo fatty acid synthesis, such as FASN and ACSL3 . Furthermore, we showed that an isoform switch to the proximal poly(A) site of these genes depended on the androgen receptor, and the expression of cancer-associated genes was upregulated by the escape of miRNA-regulated repression machinery. To address the role of key gene shortening in PCa, we prepared 22RV1-FS cells missing the distal poly(A) signal of FASN in the AR + PCa cell line 22RV1 using CRISPR/Cas9 technology. As expected, the edited 22RV1-FS cells overexpressed FASN mRNA and protein and were inclined to cell proliferation in vitro and tumorigenesis in vivo . Interestingly, we found that FASN transcripts with a shortened 3′UTR were significantly increased in advanced PCa and castration-resistant prostate cancer compared with benign prostate hyperplasia, suggesting a possible association between usage of the proximal poly(A) site and disease progression. Therefore, our study highlights the importance of the APA mechanism in response to DHT stimulation in PCa cells and provides a novel regulatory mechanism through which DHT-induced APA causes altered expression of de novo lipogenesis genes, with a possible association with the progression of PCa.

DTX1 Modulates Microglial M1 Polarization and Exacerbates Neuroinflammation in Traumatic Brain Injury Model Rats through NF—κB/IRF5 - Yonghui Zhang; Zongxing Zou; Rongwei Li; Xiaochuan Fu; Ganyu Li; Lu Wang; Yan Zhang; Yuyu Chen; Zuzhi Chen; Dongfang Yang; Yan Jiao; Weiguang Zhang; et al. (Molecular Neurobiology, 2025)

Cassiterite U–Pb ages from the Tin Islands, Indonesia, the southern end of the Southeast Asian tin province - Jie-Hua Yang; Rui-Zhong Hu; Mei-Fu Zhou; Bernd Lehmann; Jun-Hong Zhao; Jing-Hua Wu; Liang Liu; Wei Mao; Zheng-Teng Cui; Mega Fatimah Rosana (Mineralium Deposita, 2025)

Constraints of in-situ elemental and B isotopic compositions of tourmaline on the origin of the Nong Sua Sn deposit, Thailand - Jie-Hua Yang; Rui-Zhong Hu; Liang Liu; Wei Mao; Ya-Zhou Fu; Mei-Fu Zhou; Heng Chen; Alongkot Fanka; Ke-Jun Hou (Mineralium Deposita, 2025)

On-chip single-cell mass spectrometry for streamlined metabolic exploration enabled by a reversibly-bonded microfluidic platform - Jiacheng You; Anqi Chen; Jianxiong Qiu; Yaling Ye; Chongchong Mei; Guanghou Fu; Baiye Jin; Luhong Wen (Analytica Chimica Acta, 2025)

Two new withanolides from Physalis minima L - Li-Jie Zhang; Mei-Lin Peng; Shi-Ying Xu; Fu-Rui Wang; Lin-Lin Yu; Qin-Feng Zhu; Shang-Gao Liao; Guo-Bo Xu (Natural Product Research, 2025)

Plastic film mulching ensures maize climate resilience: A perspective of temperature suitability and optimal sowing period window - Jing Wang; Ling Zhao; Bao-Zhong Wang; Fei Mo; Ning Wang; Shu-Tong Liu; Yuan Song; Ai-Tian Ren; Fu-Jian Mei; Yang Wang; Qi Lu; You-Cai Xiong (Soil and Tillage Research, 2025)

Two unprecedented 2-(2-phenethyl)chromone derivatives with anti-Helicobacter pylori and anti-inflammatory activities from agarwood of Aquilaria crassna - Xiao-Hong Li; Hao Wang; Wen-Li Mei; Wen-Hua Dong; Jun Zeng; Sheng-Zhuo Huang; Hui-Qin Chen; Yan-Mei Wei; Fei Wu; Zhi-Yong Guo; Hao-Fu Dai (Phytochemistry Letters, 2025)

The influence of water flow disturbance form on the granulation of algae sludge: Granulation property, treatment effect and algae biological structure - Peng-fei Yu; Ao Wang; Hai-wen Sun; Ding Wang; Xing-guan Ma; Yu-jia Wang; Bo-mei Hu; Li-yao Han; Yu-bo Fu; Dian-lin Jiang; Shi-gang Tu (Journal of Water Process Engineering, 2025)

WB-assisted activation of periodate by Fe(III) for decontamination: Periodate concentration-dependent mechanistic shift - Yulu Xu; Yu Mei; Yanjun Li; Chenye Fu; Yuantai Li; Yuheng Zhong; Junxi Song; Gang Yang; Shihuai Deng; Xiaohui Lu; Jiali Peng; Bo Lai (Journal of Hazardous Materials, 2025)

Biohybrid microneedle delivering engineered probiotics for synergistic tumor gas/photothermal-immunotherapy - Wenxin Fu; Junhong Ling; A.M. Omer; Xiao-kun Ouyang; Lin Mei; Nan Wang (Chemical Engineering Journal, 2025)

A fish-gelatin-modified multifunctional hydrogel with “salt-in-water” for dendrite-free flexible zinc-ion batteries - Wen-Long Cheng; Zi-Qiang Cheng; Zi-Zi Hu; Ming-Ming Hu; Guang-Xian Liu; Lin-Feng Yuan; Yan-Hui Fu; Xiao-Mei Sha; Zong-Cai Tu (Chemical Engineering Journal, 2025)

Enhanced selectivity of imidazolium-based anion exchange resins for technetium-99 and rhenium removal - Luyang Xie; Jie Li; Wenjuan Xue; Haifeng Zou; Jianrui Wu; Zuzhuo Zhang; Yanhua Song; Wenfu Yan; Xueqi Fu; Shuao Wang; Donghai Mei (Chemical Engineering Journal, 2025)

Elucidating CTLA-4’s role in tumor immunity: a comprehensive overview of targeted antibody therapies and clinical developments - Juan Fu; Lin Mao; Yu Jiao; Desheng Mei; Yadong Chen (Molecular Diversity, 2025)

Genetic burden and multidimensional predictors in prenatal diagnosis of fetal congenital diaphragmatic hernia - Ruibin Huang; Fang Fu; Shanshan Mei; Liyuan Liu; Wei Zhong; Jin Han; Qiuxia Yu; Hang Zhou; Chunling Ma; Li Zhen; Min Pan; Qiong Deng; et al. (Human Genetics, 2025)

Mineralogical insights into the release behaviors of potentially toxic elements from the indigenous Zn smelting slags dumping sites - Ze-Lin Xu; Mei-Chun Zhou; Jin-Hui Miao; Wen-Chu Zhao; Rong-Bing Fu; Da-Mao Xu (Process Safety and Environmental Protection, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Remobilization of Ni in framboidal pyrite within sulfide nodules in Early Cambrian nickeliferous black shales - Xu-Yang Liu; Ya-Fei Wu; Daniel D. Gregory; Katy Evans; Anthony E. Williams-Jones; Wen Zhang; Mei-Fu Zhou; Jian-Wei Li (Chemical Geology, 2025)

Spatial distribution, phase partitioning, and ecological risk assessment of typical pesticides in Yangtze River Basin - Chengcheng Bu; Chong Chen; Xitong Fu; Weiwei Zhang; Ru Zhang; Yu Hua; Ruolan Jia; Yuefei Ruan; Kenneth Mei Yee Leung; Limin Ma (Journal of Hazardous Materials, 2025)

Weakening plasticulture boosts maize productivity while improving environmental benefits in drying east African Plateau - Fu-Jian Mei; Qing-Hui Wen; Yang Wang; Alex Ndolo Munyasya; Sylvia Ngaira Indoshi; Wesly Kiprotich Cheruiyot; Wei Wang; David Mwehia Mburu; Aggrey Bernard Nyende; Levis Kavagi; You-Cai Xiong (Journal of Cleaner Production, 2025)

Scandium and gallium in weathered basalts as unconventional resources - Mei-Fu Zhou; Wen Winston Zhao; Zhenchao Wang; Min Wang; Shengbiao Yang; Lei Meng; Liang Qi; Guangfu Xing; Xiang Li; Dai Zhou (Journal of Asian Earth Sciences, 2025)

Self-organizational origin of oscillatory zoning in pyrite: A coupled diffusion–reaction model and pH-dependent As adsorption feedback mechanism - Wenhong Johnson Qiu; Mei-Fu Zhou (Geochimica et Cosmochimica Acta, 2025)

Z-scheme MIL-88A(Fe)/LaFeO3 heterostructured photocatalyst: Boosting photo-Fenton activity for enhanced organic pollutant detoxification - Ruo-Xuan Mei; Peng Wang; Fu-Xue Wang; Zi-Chen Zhang; Xiao-Hong Yi; Zi-Yu Jia; Ke-Xin Li; Chong-Chen Wang (Environmental Research, 2025)

Combining network pharmacology and RNA sequencing to reveal the mechanism of emodin for the treatment of human neuroblastoma - Hai-mei Jiang; Shang-yi Huang; Dan Huang; Yan Zhao; Yi Yuan; Hai-fu Huang; Ying Tang; Jin-fang Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Origin of the giant Devonian Daxigou sedimentary siderite deposit, Central China - Yuanjun Jonathan Lyu; Mei-Fu Zhou; Rui-Zhong Hu; Zerui Ray Liu; Yanfeng Zhao (Mineralium Deposita, 2025)

Establishment of an efficient in vitro regeneration protocol for Dendrobium primulinum Lindl. by one-step seedling formation - Cheng-Li Liu; Jie-Mei Deng; Shun Peng; Heng-Yu Huang; Fu-Rong Xu (In Vitro Cellular & Developmental Biology - Plant, 2025)

Inhibitory effects of flavonoids and alkaloids from the traditional antihyperglycemic herb Polygonatum kingianum var. grandifolium on α-glucosidase activity - Qing-Dong Ma; Xu-Juan Fu; Xiao-Qin Xiong; Dong-Mei Liu; Zhuo-Jun Li; Wei Gong; Dong-Qin Guo; Dong-Yang Yi (Natural Product Research, 2025)

Quantitative analysis of anthocyanins and flavonoids in purple and green leaves of Eleutherococcus senticosus by UPLC-MS/MS techniques - Mei Hua; Meng Meng; Yu-pin Fu; Yun-qin Li (Natural Product Research, 2025)

Quantifying the effect of key factors on the shedding and decay rates of eDNA from the golden mussel - Yao Yang; Jiahao Zhang; Zhibing Chang; Mei Liu; Mengzhen Xu; Xinyi Zhou; Xudong Fu (Journal of Environmental Management, 2025)

Upper Jurassic radiolarian assemblages and chert geochemistry of the Shiquanhe ophiolite, NW Tibet: Implications for the evolution of the Meso–Tethyan ocean - Xiaohui Cui; Yichun Zhang; Xin Li; Jonathan C. Aitchison; Mei-Fu Zhou; Qinggao Zeng; Guangying Ren; Hui Luo (Gondwana Research, 2025)

Highly sensitive, anti-freezing and stretchable hydrogels with modified MXene for multifunctional applications - Xiang-Shu Hu; Xin Jing; Jing-Wen Mei; Fu-Xiang Liu; Pei-Yong Feng; Jiayi Xu; Yue-Jun Liu (Food Chemistry, 2025)

Tetrahedral framework nucleic acid-based delivery of microRNA-29b: A precision nanotherapeutic strategy for oral submucous fibrosis - Xiao Fu; Mei Zhang; Chenpeng Chen; Xin Qin; Qianqian He; Yichen Yang; Siqi Xu; Guanjun Chen; Haiyu Xian; Guanyu Sun; Yao He; Yunfeng Lin; et al. (Chemical Engineering Journal, 2025)

Integrated omics and functional insights into BjMYB90-mediated regulation of BjGSTF12 for enhanced anthocyanin biosynthesis in mustard (Brassica juncea) - Umer Karamat; Juxian Guo; Shizheng Jiang; Imran Khan; Mengting Lu; Guihua Li; Mei Fu (Plant Cell Reports, 2025)

Triaxial loading mechanical properties and differential failure mechanisms of damaged sandstone under pore water pressure changes - Xiang Fu; Han Su; Qiang Xie; Kuang Dong; Hao Mei; Yuxin Ban (Bulletin of Engineering Geology and the Environment, 2025)

Selective salt separation and resource recovery via nanofiltration in coal-to-ethylene glycol wastewater - Zheng-Jun Fu; Bo-Zhi Chen; Kai Yu; Jian-Guo Hu; Pengli Chen; Hui-Qin Zhang; Mei-Ling Liu; Shi-Peng Sun (Journal of Water Process Engineering, 2025)

Composition characteristics, source analysis and risk assessment of PAHs in surface waters of Lipu - Jun Luo; Gui-Bin Huang; Mei Wang; Ya-Nan Zhang; Zi-Xuan Liu; Qin Zhang; Shao-Yuan Bai; Dan-Dan Xu; Hui-Li Liu; Sheng-Peng Mo; Xiao-Bin Zhou; Ming-Ming Fu (Journal of Hazardous Materials, 2025)

Enhanced cathodic performance for simultaneous removal of Cr (VI) and norfloxacin: The synergistic effect and electron transfer triggered by high-entropy spinel oxide - Yu-Xin Guo; De-Wang Wei; Shang-Mei Fu; Ling-Zhen Miao; Lu Ying; Lei Wu; Jie Zhu (Journal of Environmental Chemical Engineering, 2025)

A novel four-species microbial consortium for nutritional value improvement of rapeseed meal - Kunqiang Hong; Han Zhang; Mei Han; Xuejiao Nie; Xiaomeng Fu; Fenfen Lei; Dongping He (Food Chemistry, 2025)

Lightweight deep learning model for embedded systems efficiently predicts oil and protein content in rapeseed - Mengshuai Guo; Huifang Ma; Xin Lv; Dan Wang; Li Fu; Ping He; Desheng Mei; Hong Chen; Fang Wei (Food Chemistry, 2025)

Untargeted metabolomics and network pharmacology reveal the uric acid-lowering effects of alcohol extract of Gnaphalium affine and its extracts in hyperuricemic rats - Chen Wang; Xinchao He; Lijuan Rao; Jiajing Liao; Jin Qian; Xuefeng Yu; Sen Mei; Suqin Lin; Linqian Xu; Guiming Fu; Yin Wan (Food Bioscience, 2025)

Climate suitability determines optimal yielding of dryland maize: A validation on timely sowing as an ancient wisdom - Jing Wang; Ling Zhao; Meng Hao; Ning Wang; Qing-Hui Wen; Fu-Jian Mei; Aziz Khan; Bao-Zhong Wang; Xiao-Lin Zhang; Wei Wang; Chang-Lang Yang; Fei Mo; et al. (Field Crops Research, 2025)

Pixel array-based urine biosensor for detection of trimethylamine N-oxide and glucose for early detection of diabetic kidney disease - Mei-Ching Yu; Chi-Jen Lo; Wei-Cheng Lin; Wei-Lun Yen; Yun-Yu Hsieh; Bing-Hong Chen; Fu-Sung Lo (Analytica Chimica Acta, 2025)

Unlocking Parkinson’s disease: the role of microRNAs in regulation, diagnosis, and therapy - Xiaodong Li; Qiang Fu; Mei Guo; Yang Du; Yong Cheng (Apoptosis, 2025)

Wind Direction and Strength Determine the Genetic Structure of an Insect‐Pollinated Plant Across Heterogeneous Landscape - Jun‐Yin Deng; Rong‐Hua Fu; Stephen G. Compton; Chuan Yuan; Matthew M. Kling; Xiao‐Yong Chen; Yao‐Bin Song; Kai Jiang; Mei Liu; Jaco M. Greeff; Yan Chen (Journal of Biogeography, 2025)
Aim Dispersal of plant propagules and their genes is crucial for plant responses to landscape heterogeneities, yet the mechanisms behind this dispersal remain unclear. Ficus species depend on wind‐borne fig wasps for pollination, but research on airflow effects on Ficus genetic structure has produced conflicting results. Our study aims to clarify the role of wind in shaping the genetic structure of such plants with wind‐borne insect pollinators by examining how geomorphological complexity interacts with air movements to influence genetic structures. Location Southwest China: Sichuan, Yunnan, Guangxi and Guizhou provinces. Taxon Ficus tikoua Bur., Ficus , Moraceae. Methods We sampled 56 F. tikoua sites across southwest China, characterised by high geomorphologic complexity. River basins and predominant winds were visualised across the sampled regions. Wind connectivity between sampled sites during the main pollination season was modelled based on hourly daily wind data. The maternal and biparental genetic structure of sites were reconstructed using chloroplast DNA (cpDNA) and nuclear SSR (nuSSR) markers. Links between genetic structure, location, and wind parameters were estimated by Mantel or partial Mantel tests. Results The plant's maternal genetic structure was defined by river systems, with two distinct cpDNA groups located in the Yangtze and Pearl River basins, respectively. The boundaries for nuclear variation were less clearly delimited geographically. Sites with mixtures of nuSSR groups were concentrated where prevailing winds arrived from several directions. Stronger between‐site air flows increased nuSSR geneflow and genetic similarities, while populations receiving more wind flow were also more genetically variable. Main Conclusions Our study reveals how plant gene dispersal reflects air and water movements that in turn respond to geomorphologic complexity, thereby directly demonstrating the effects of wind on gene flow of plants with wind‐borne insect pollinators. Wind data matching pollinator flight times and large sample sizes are crucial for testing wind effects.

Deciphering the effective substances of mangrove plant Acanthus ilicifolius Linn. against liver injury - Qing Zhao; Shu-Yue Song; Han Fang; Yao-Yao Zheng; Meng-Qi Zhang; Xia Ren; Ya-Hui Zhang; Xiu-Mei Fu; Xin Li; Chang-Yun Wang (Natural Product Research, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Insights into atrazine degradation by a halotolerant bacterium Arthrobacter sp. PSC in high-salt aquatic environments: degradation pathway and halotolerance mechanism elucidation - Yifan Jiang; Chunqing Fu; Bingwen Xu; Xinmei Fu; Liang Tan; Mei Jin (Journal of Water Process Engineering, 2025)

N-acyl homoserine lactones - Modified anode improves carbamazepine removal in microbial fuel cells: Effect of electrogenic biofilm - Jing Fu; Xiang Li; Hao Chen; Jingting Mei; Liang Tang (Journal of Water Process Engineering, 2025)

Development of weakly euxinic basin environments in the Phanerozoic oxic ocean: Insights from Fe speciation and Mo isotopes of Devonian pyrite-bearing black shales, Dajiangping pyrite mine, South China - Wenhong Johnson Qiu; Mei-Fu Zhou; John Malpas; Jie Li; Zerui Ray Liu; Yafei Wu (Global and Planetary Change, 2025)

Two new compounds from Pentadesma butyracea and their biological activities - Yue Yang; Li Hua Gong; Fu Hua Peng; Tao Jiang; Jian Guo Hu; Hong Dong Liu; Bin Li; Yin Xia Yang; Jing Ying Peng; Xue Mei Gao (Phytochemistry Letters, 2025)

Two new phenolic glycosides from Cyathula officinalis and their relaxant effects on uterine smooth muscle - Mei-Ji Sun; Rui Zhao; Min Wen; Chun-Wang Meng; Hai-Guo Su; Fu-Xin Mi; Cheng Peng; Juan Liu; Liang Xiong (Phytochemistry Letters, 2025)

Three new dimeric 2-(2-phenethyl)chromones from the agarwood of Aquilaria malaccensis - Xian-Yun Yan; Wei Li; Hao Wang; Wen-Hua Dong; Jun Zeng; Fei Wu; Wen-Li Mei; Lin-Fu Liang; Hao-Fu Dai (Phytochemistry Letters, 2025)

Based on metabolomics and fourier transforms near infrared spectroscopy characterization of Lanxangia tsaoko chemical profile differences among fruit types and development of rapid identification and nutrient prediction models - Deng-Ke Fu; Wei-Ze Yang; Mei-Quan Yang; Tian-Mei Yang; Yuan-Zhong Wang; Jin-Yu Zhang (Food Bioscience, 2025)

Dietary pyridoxine promoted muscle protein deposition relating to PI3K/AKT/TOR pathway and the ubiquitin proteasome system in grass carp (Ctenopharyngodon idella) - Li-Fu Gong; Xiao-Qiu Zhou; Lin Feng; Pei Wu; Wei-Dan Jiang; Yao-Bin Ma; Xiao-Wan Jin; Hong-Mei Ren; Jia-Yong Tang; Fa-Li Wu; Yang Liu (Food Bioscience, 2025)

The combined effects of soil moisture and salinity on the spatial differences of soil humification intensity in the Yangtze River estuarine wetlands - Haoyu Dong; Wenxuan Mei; Liwei Qian; Xiaoyu Gao; Haoting Liu; Xiaohua Fu; Lei Wang (Journal of Soils and Sediments, 2025)

Cracking behavior and deterioration of strength characteristics of silty clay under drying-wetting cycles - Mei Dong; Yunpeng Deng; YuHan Fu (Bulletin of Engineering Geology and the Environment, 2025)

Response of key nitrogen removal processes in estuarine salt marshes to different plant harvesting patterns varies significantly across different time scales - Wenxuan Mei; Haoyu Dong; Xiaoyu Gao; Haoting Liu; Liwei Qian; Xiaohua Fu; Lei Wang (Journal of Environmental Management, 2025)

Decoding the end-Devonian Hangenberg oceanic anoxia event: Insights from ironstones in South China - Yuanjun Jonathan Lyu; Mei-Fu Zhou; Ying Cui; Rui-Zhong Hu; Zerui Ray Liu; Xiyao Li (Earth and Planetary Science Letters, 2025)

Hypertonic stress affects the expression of clock protein CmFRQ in Cordyceps militaris and remodels the morphology of fruiting body - Jing-Mei Peng; Dan-Dan Zhang; Ming-Jia Fu (Biologia, 2025)

Straw incorporating in shallow soil layer improves field productivity by impacting soil hydrothermal conditions and maize reproductive allocation in semiarid east African Plateau - Sylvia Ngaira Indoshi; Wesly Kiprotich Cheruiyot; Muhammad Maqsood Ur Rehman; Fu-Jian Mei; Qing-Hui Wen; Alex Ndolo Munyasya; Kiprotich Koskei; David Mwehia Mburu; Aggrey Bernard Nyende; Levis Kavagi; Delphine Nyanchera Gisacho; Eliyas Feyisa Sori; et al. (Soil and Tillage Research, 2025)

Petrogenesis of the > 2.90 Ga komatiite in the Sujiagou region of the North China Craton: Implications for Archean mantle source and geodynamic setting - Rui Zuo; Xiaoping Long; Bin Wu; Mei-Fu Zhou (Precambrian Research, 2025)

Experimental validation and mechanistic elucidation of crack division and two-phase flow-mediated sealing in coalbed methane extraction boreholes - Dezhi Ran; Jianwei Cheng; Yejiao Liu; Qiang Fu; Zhiyuan Ma; Jing Mei (International Journal of Rock Mechanics and Mining Sciences, 2025)

All-solid-state wire-shaped micro-supercapacitors: A microfluidic approach to core-shell structured bacterial cellulose-GN/PPy fibers - Yue Jiao; Yao Wang; Huining Xiao; Jian Li; Changtong Mei; Qiliang Fu; Jingquan Han (Carbohydrate Polymers, 2025)

A Finite Element Analysis Comparing an Additive Manufacturing Lattice-Structured PEEK Implant to a Commercial Ball-and-Socket Design for Cervical Total Disc Replacement - Ming-Kai Hsieh; Fu-Cheng Kao; Yun-Da Li; De-Mei Lee; Hui Jin; Ching-Lung Tai; Tsung-Ting Tsai; Po-Liang Lai; Weng-Pin Chen (Journal of Medical and Biological Engineering, 2025)
Purpose Cervical total disc replacement (TDR) is commonly performed to treat degenerative cervical spondylosis, but it often faces challenges such as implant wear and migration. This study aimed to develop and evaluate a novel 3D-printed TDR featuring a titanium endplate and a lattice-structured poly-ether-ether-ketone (PEEK) design. The primary objective was to replicate the natural motion of the cervical disc while addressing complications associated with conventional TDRs. Methods The novel implant was created using additive manufacturing techniques, incorporating three lattice-structured PEEK designs (Cross, Octet, and Ventiles) for the nucleus pulposus and annulus fibrosus components. A finite element analysis was conducted to compare the biomechanical performance of the novel TDR with an intact cervical disc and a commercially available TDR (Baguera®C, Spineart SA, Geneva, Switzerland). Key parameters, including maximal von Mises stresses, range of motion, paths of the instantaneous center of rotation, and facet joint stresses, were evaluated under physiological loads (100 N follower load and 1.5 Nm pure moments). Results The novel 3D-printed TDR maintained structural integrity, with stresses remaining within the yield strength of PEEK. The biomechanical performance closely resembled that of an intact cervical disc, demonstrating similar ranges of motion, instantaneous center of rotation paths, and facet joint stress distributions. Conclusion The findings indicate that the innovative 3D-printed TDR may restore normal cervical spinal kinematics more effectively than existing commercial options, potentially reducing the risk of post-operative facet joint syndrome. Further experimental and clinical studies are recommended to validate these results.

Cynbungenins A-K, structurally diverse steroids with cytotoxic activity from the roots of Cynanchum bungei Decne - Xiao-San Li; Ming-Shang Liu; Wan-Bi Feng; Yu-Hao Luo; Wei-Bin Yuan; Ting-Ting Li; Xiao-Fu Peng; Yong-Mei Huang; Xue-Mei Yang; Hui Luo (Phytochemistry, 2025)

Can biodegradable film replace polyethylene film to obtain similar mulching effects on soil functions and maize productivity in irrigation region? A three-year experimental appraisal - Xiao-Bin Xiong; Peng-Yang Wang; Ze-Ying Zhao; Jing Wang; Shu-Tong Liu; Fu-Jian Mei; Wen-Ying Wang; Yi-Bo Wang; Xiang-Wen Fang; Ying Zhu; Jin-Lin Zhang; Ning Wang; et al. (Journal of Cleaner Production, 2025)

Spatial pattern of critical wetland patches and its influencing factors in a coastal area, North China - Ziyuan Zhang; Jintong Liu; Hui Gao; Feng Wang; Baijun Shang; Mei Zhang; Tonggang Fu (Journal of Environmental Management, 2025)

Comprehensive physicochemical indicators analysis and quality evaluation model construction for the post-harvest ripening rapeseeds - Qiuhui Xu; Jie Wang; Dan Wang; Xin Lv; Li Fu; Ping He; Desheng Mei; Hong Chen; Fang Wei (Food Chemistry, 2025)

Elevated CO2 alters antibiotic resistome in soil amended with sulfamethazine via chemical-organic fertilization - Fen Xu; Qian Xiang; Mei-Ling Xu; Laura J. Carter; Wen-Chao Du; Chun-Wu Zhu; Fu-Xun Ai; Ying Yin; Rong Ji; Hong-Yan Guo (Environmental Research, 2025)

Calibration of the Solar X-ray Detector on-board the Macao Science Satellite-1B for Soft X-ray Detection - Man-Hei Ng; Xiaoping Zhang; Jianwu Chen; Yongqiang Shi; Fuchang Zuo; Wenxi Peng; Weichun Fu; Liansheng Li; Pengwei Luo; Chi-Long Tang; Guozheng Zhang; Zhiwu Mei; et al. (Science China Earth Sciences, 2025)

Activation of 5-HT6 Receptors in the Ventrolateral Orbital Cortex Produces Anti-Anxiodepressive Effects in a Rat Model of Neuropathic Pain - Yu-Long Zhao; Hui-Yuan Yi; Sani Sa’idu Baba; Yi-Xiao Guo; Xiao-Cui Yuan; Xue-Mei Hou; Ling-Li Liang; Fu-Quan Huo (Molecular Neurobiology, 2025)

Enhanced removal of tetracycline using three-dimensional electrochemical system with Fe/N/S co-doped coffee grounds biochar particle electrodes: Performance and mechanism - Peixin Tang; Xu Ren; Jiahao Mei; Yucheng Liu; Kai Song; Haifeng Fu; Xin Peng; Li Zeng; Qiang Ma; Zhicheng Pan (Process Safety and Environmental Protection, 2024)

Constraints of in-situ elemental compositions and U–Pb ages of cassiterite on the origin of the Cretaceous Gejiu and Dulong tin deposits, SW China: Implications for the linkage of tin belts in SE Asia - Zhi Zhang; Jie-Hua Yang; Rui-Zhong Hu; Bin Fu; Qian Hu; Mei-Fu Zhou (Lithos, 2024)

Ecological response mechanism of alkaline wastewater periphytic biofilms to pH alteration - Mei Zhong; Li Cao; Chunyan Li; Hansen Xu; Qi Li; Wanying Fu; Ying Lu; Yanjie Zhang; Xia Luo; Xinyou Liu (Journal of Water Process Engineering, 2024)

Metal–organic framework-based SERS chips enable in situ and sensitive detection of dissolved hydrogen sulfide in natural water: Towards a bring-back-chip mode for field analysis - Meiyu Si; Yunqing Wang; Rongchao Mei; Xizhen Zhao; Qi Yuan; Longwen Fu; Yixuan Wu; Abbas Ostovan; Maryam Arabi; Shanshan Wang; Lingxin Chen (Journal of Hazardous Materials, 2024)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

Characterization of regolith-hosted rare earth element deposits using reflectance spectroscopy: Framework towards an efficient and reliable field exploration tool - Martin Yan Hei Li; Jiacheng Liu; Wei Tan; Jia-Xi Zhou; Mei-Fu Zhou (Journal of Geochemical Exploration, 2024)

Particle size is an important factor influencing the effects of biochar return to woodland soils: An evaluation from the perspective of sapling growth and soil microbial carbon processes - Xiaoyu Gao; Haoting Liu; Wenxuan Mei; Wenwen Zhang; Haoyu Dong; Xiaohua Fu; Mengdi Xie; Yujie Han; Lei Wang (Journal of Environmental Management, 2024)

Optimizing starch content prediction in kudzu: Integrating hyperspectral imaging and deep learning with WGAN-GP - Huiqiang Hu; Yunlong Mei; Yiming Zhou; Yuping Zhao; Ling Fu; Huaxing Xu; Xiaobo Mao; Luqi Huang (Food Control, 2024)

Stable carbon isotope reveals high impact of fishing ship activities on total carbon from PM2.5 in Qingdao, China - Yao Wang; Hong-Wei Xiao; Mei-Ju Yin; Qi-Bin Sun; Fei Fu; Ji-Hua Tao; Hua-Yun Xiao (Environmental Pollution, 2024)

Estuarine wetland tidal organic carbon activates microbial carbon pump and increases long-term soil carbon stability - Mengdi Xie; Haoyu Dong; Xiaolu Tang; Liwei Qian; Wenxuan Mei; Jianfang Yan; Xiaohua Fu; Yu Hu; Lei Wang (CATENA, 2024)

Clay composition heterogeneity in sediments from mountainous catchments with contrasting bedrock lithology in SE China coast - Ling Wang; Xing Jian; Haowei Mei; Xiaotian Shen; Hanjing Fu (CATENA, 2024)

Linkage of Mineral Inclusions and Zoning of Magnetite with Fluid Evolution of Hydrothermal Systems: A Case Study of the Fenghuangshan Cu-Fe-Au Skarn Deposit, Eastern China - Xiao-Wen Huang; Yiping Yang; Mei-Fu Zhou; Yu-Miao Meng; Jian-Feng Gao; Liang Qi (Journal of Earth Science, 2024)

Life cycle environmental impacts of urban water systems in China - Hao Xu; Guangtao Fu; Qian Ye; Mei Lyu; Xiaoyu Yan (Water Research, 2024)

Short-term sedimentary evidence for increasing diatoms in Arctic fjords in a warming world - Fu-Tao Fang; Zhuo-Yi Zhu; Fred Wenger; Jian-Zhong Ge; Jin-Zhou Du; Bing Deng; Hong-Mei Ma; Rui-Feng Zhang; Yu Zhang (Science of The Total Environment, 2024)

DTTR: Encoding and decoding monthly runoff prediction model based on deep temporal attention convolution and multimodal fusion - Wen-chuan Wang; Wei-can Tian; Xiao-xue Hu; Yang-hao Hong; Fu-xin Chai; Dong-mei Xu (Journal of Hydrology, 2024)

Biofilm enhanced the mitigations of antibiotics and resistome in sulfadiazine and trimethoprim co-contaminated soils - Zhi Mei; Fang Wang; Yuhao Fu; Yu Liu; Syed A. Hashsham; Yu Wang; Jean Damascene Harindintwali; Qingyuan Dou; Marko Virta; Xin Jiang; Yu Deng; Tong Zhang; et al. (Journal of Hazardous Materials, 2024)

Contrasting dynamics of marine bacterial-algal communities between the two main pulses of the Late Ordovician Mass Extinction - Yu Liang; Zerui Ray Liu; Thomas J. Algeo; Lei Meng; Chengdong Ming; Jun Wang; Bowen Song; Zhonghui Liu; Mei-Fu Zhou (Earth and Planetary Science Letters, 2024)

Green massive mechanical synthesis of highly efficient Zn-Doped Cs3Cu2I5 for LED and X-ray imaging applications - Qi-Hua Yang; Gui-Hua Li; Yu-Chen Ao; Shu-Juan Zhao; Han-Qi Wei; Le Fu; Zhi-Wei Luo; Tian-Liang Zhou; Chu-Jie Wang; Ge-Mei Cai (Chemical Engineering Journal, 2024)

Six element high-entropy Prussian blue analogue cathode enabling high cycle stability for sodium-ion batteries - Zhe Qian; Rui-Jie Luo; Cui Ma; Chong-Yu Du; Jie Zeng; Xuan Xu; Zhe Mei; Zi-Ting Zhou; Zheng-Wen Fu; Yong-Ning Zhou (Chemical Engineering Journal, 2024)

A novel temperature-responsive biphasic deep eutectic solvent-based solvent system: Integrated efficient extraction, enrichment and recovery of phytochemicals - Zi-Hui Cai; Xin-Yue Dong; Li-Tao Wang; Wan-Mei Zhou; Ya-Ning Wang; Jie Yang; Yu-Jie Fu (Chemical Engineering Journal, 2024)

NUS1 Variants Cause Lennox-Gastaut Syndrome Related to Unfolded Protein Reaction Activation - Nan-Xiang Shen; Xiao-Chong Qu; Jing Yu; Cui-Xia Fan; Fu-Li Min; Ling-Ying Li; Ming-Rui Zhang; Bing-Mei Li; Jie Wang; Na He; Wei-Ping Liao; Yi-Wu Shi; et al. (Molecular Neurobiology, 2024)

Manure sterilization reduced antibiotic resistance genes in lettuce endophytes - Qingyuan Dou; Ying Liang; Yuhao Fu; Zhi Mei; Leilei Xiang; Rehan Ahmad; Wei Zhao; Xin Jiang; Syed A. Hashsham; James M. Tiedje; Fang Wang (Journal of Cleaner Production, 2024)

Disorder–order structure of a-CeO2/SnFe2O4 heterojunction with enhanced exciton dissociation for the NIR-driven photocatalysis - Hao Jiang; Mei Yan; Hao Chen; Yutuo Fu; Chongshen Guo (Chemical Engineering Journal, 2024)

Micro/nano system-mediated local treatment in conjunction with immune checkpoint inhibitor against advanced-Stage malignant melanoma - Lu Tang; Hening Liu; Yue Yin; Ting Pan; Cong Fu; Yuqi Cao; Yijun Mei; Qiaqia Xiao; Ziwei Yan; Yi Yao; Haijuan Dong; Wei Wang (Chemical Engineering Journal, 2024)

Interpenetrating LiB/Li3BN2 phases enabling stable composite lithium metal anode - Piao Qing; Shaozhen Huang; Tuoya Naren; Quan Li; Haifeng Huang; Kecheng Long; Zhijian Liu; Lin Mei; Fu Sun; Weifeng Wei; Yu Zhang; Jianmin Ma; et al. (Science Bulletin, 2024)

Integrated metal carbonate thermal decomposition with in-situ CO2 conversion: Review and perspective - Bo Jin; Dongtao Fu; Xiaoju Xiang; Haibo Zhao; Haiyan Zhang; Daofeng Mei; Zhiwu Liang (Gas Science and Engineering, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Genetic analysis of Discogobio (Cypriniformes: Cyprinidae) in the Central Yunnan Basin: Effects of geological events and conservation perspectives - Xing‐Jin Che; Yuan‐Wei Zhang; An‐Li Wu; Li‐Mei Zhang; Xiao‐Fu Pan; Mo Wang; Jun‐Xing Yang; Xiao‐Ai Wang (Zoologica Scripta, 2024)
Geological events can have a major effect on the genetic structure and differentiation of fish populations. The relative importance of key geological events on the distribution and genetic structure of endemic fish of the genus Discogobio in the Yunnan–Guizhou Plateau has not yet been evaluated. Studies of the phylogeography of Discogobio fishes could provide insights into spatial and temporal changes in their population size, dispersal history, and extent of geographical isolation, and the data acquired in such studies can be used to aid their conservation. Here, we used single‐nucleotide polymorphisms (SNP) to characterize the phylogeography of Discogobio fishes. Our analysis supports the endemicity of Discogobio . However, Discogobio samples from different regions contained multiple ancestral components, including admixed and diversified genetic components. This might stem from polymorphism of the ancestors themselves or the infiltration of genes caused by hybridization between Discogobio species. We estimated that the most recent common ancestor (MRCA) of Discogobio fish in the Central Yunnan Basin was approximately 4.63–3.83 million years ago (Ma). We also inferred that the evolution of Discogobio in the Central Yunnan Basin was closely related to the expansion and contraction of the lake basin around 2.59–0.13 Ma. We proposed measures that could be implemented to conserve remaining populations and their corresponding habitats to prevent further declines and preserve the biodiversity of this unique genus.

Dynamics of green macroalgal micro-propagules and the influencing factors in the southern Yellow Sea, China - Xiaojun Ma; Xiaoxiang Miao; Shiliang Fan; Yu Zang; Baotang Zhang; Mei Li; Xuelei Zhang; Mingzhu Fu; Zongling Wang; Jie Xiao (Science of The Total Environment, 2024)

Synergistic mechanism and toxicity reduction potential in medium-pressure UV/chlorine/TiO2 system for metronidazole removal - Yu-qiong Gao; Xiang-mei Zhong; Xue-ting Ren; Fu-xiang Tian; Nai-yun Gao; Cong Li (Journal of Water Process Engineering, 2024)

Ultrathin-flexible multifunctional MXene composite hydrogels with good mechanical properties-high strain sensitivity and ultra-broadband EMI shielding performances - Wenchong Ouyang; Lin Mei; Qi Liu; Chengbiao Ding; Yanming Liu; Chengwei Zhao; Limin Xu; Fu Lu; Dongpeng Luo; Chunguang Miao; Yu Bai; Quanming Lu; et al. (Chemical Engineering Journal, 2024)

Promoting the systematic utilization of reclaimed asphalt pavement (RAP) through waste asphalt-derived carbon in batteries applications - Danqing Li; Xin He; Hu Fu; Wenqi Tan; Shigang Lu; Linlin Wang; Mei Ding; Chunhui Gao; Chuankun Jia (Chemical Engineering Journal, 2024)

The emerging and legacy persistent organic contaminants in corals of the South China Sea - Yao-Wen Qiu; Jun Li; Mei-Xia Zhao; Ke-Fu Yu; Gan Zhang (Chemosphere, 2024)

Risk assessment of e-waste - Liquid Crystal Monomers re-suspension caused by coastal dredging operations - Chang He; Alessandro Stocchino; Yuhe He; Kenneth Mei Yee Leung; Francesco De Leo; Zhen-Yu Yin; Yin-Fu Jin (Science of The Total Environment, 2024)

New insights into the influences of firework combustion on molecular composition and formation of sulfur- and halogen-containing organic compounds - Caiqing Yan; Haibiao Chen; Fei Xu; Qinglong Fu; Ying Zhou; Ruizhi Zhou; Ruiyu Li; Mei Zheng; Mingjie Xie; Bin Jiang; Zhisheng Zhang; He Meng; et al. (Science of The Total Environment, 2024)

Structurally diverse isoquinoline alkaloids from the barks of Alangium salviifolium (L. f.) Wangerin and their cytotoxicity - Yan-Mei Wei; Xuan Zhang; Fu-Ling Cen; Yi-Yi Du; Yuan-Ling Liu; Qiao-Yuan Han; Zhang-Xin Yu; Guang-Ying Chen (Phytochemistry, 2024)

Characterization of an agmatine N-acetyltransferase from Bactrocera dorsalis that modulates ovary development - Fei-yue Teng; Ji-mei Feng; Fu-cai Ma; Zhuo-xin Wang; Yong-yue Lu; Yi-xiang Qi (Insect Biochemistry and Molecular Biology, 2024)

A novel fluorescence platform for specific detection of tetracycline antibiotics based on [MQDA-Eu3+] system - Jia-Mei Ran; Liu Yang; Chun-Tong Liu; Qiu-Huan Liu; Yu-Long Liu; Shi-Jie Li; Ying Fu; Fei Ye (Science of The Total Environment, 2024)

Bi-2-(2-phenethyl)chromone derivatives from agarwood of Aquilaria filaria in the Philippines - Hong-Run Yang; Hao Wang; Pei Wang; Fang-Zheng Liu; Hong-Xing Chai; Cai-Hong Cai; Li Yang; Jing-Zhe Yuan; Bei Jiang; Wen-Li Mei; Hao-Fu Dai (Phytochemistry, 2024)

Genomic analysis of Cobetia sp. D5 reveals its role in marine sulfur cycling - Xiao-Mei Geng; Shi-Ning Cai; Hai-Xia Zhu; Zhi-Gang Tang; Chun-Yang Li; Hui-Hui Fu; Yi Zhang; Hai-Yan Cao; Peng Wang; Mei-Ling Sun (Marine Genomics, 2024)

Elevated nitrogen loadings facilitate carbon dioxide emissions from urban inland waters - Yong-Mei Hou; Fu-Jun Yue; Si-Liang Li; Xiao-Long Liu (Journal of Environmental Management, 2024)

Using Hg isotopes and trace elements to constrain the origin of the Ordovician Xiangquan Tl deposit, South China - Lei Meng; Mei-Fu Zhou; Wei Terry Chen (Journal of Asian Earth Sciences, 2024)

GC/MS-based untargeted metabolomics reveals the differential metabolites for discriminating vintage of Chenxiang-type baijiu - Na Wang; Lili Zhang; Li Fu; Mei Wang; Hui Zhang; Xiaoyu Jiang; Xiaohui Liu; Zhen Zhang; Xuejiao Ren (Food Research International, 2024)

Early evaluation of aflatoxin occurrence risk using an ultra-sensitive immunoassay for pre-aflatoxin protein biomarker detection - Jiayun Fu; Mei Gu; Xiaoqian Tang; Qi Zhang; Peiwu Li (Food Control, 2024)

Behavioral responses of Nesidiocoris tenuis (Reuter) to different monochromatic lights and light intensities - Zhen Chen; Wen Fu; Chun-Fu Zhang; Hong-Mei Li; Jun-Jun Zhang; Deng-Ji Lou; Kai-Fei Guo (Journal of Plant Diseases and Protection, 2024)

Identification of volatile compounds and their bioactivities from unpolar fraction of Alpinia oxyphylla Miq. and mining key genes of nootkatone biosynthesis - Fapetu Kemi Busayo; Jin-Ling Yang; Xu-Po Ding; Ya-Li Wang; Cui-Juan Gai; Fei Wu; Hao-Fu Dai; Wen-Li Mei; Hui-Qin Chen (Natural Product Research, 2024)

Combining colloid milling and twin screw pressing for oleosome extraction - Chenqiang Qin; Rao Fu; Yaxin Mei; Xin Wen; Yuanying Ni; Remko Marcel Boom; Constantinos V. Nikiforidis (Journal of Food Engineering, 2024)

Evaluation and diagnosis for the pedestrian quality of service in urban riverfront streets - Dong Sun; Xiang Ji; Mei Lyu; Yao Fu; Weijun Gao (Journal of Cleaner Production, 2024)

Recycling of crustal Os in nascent subduction zones revealed by ophiolitic boninites - Wen-Jun Hu; Mei-Fu Zhou; Chao Li; John Malpas; Zhen-Chao Wang; Jun-Jie Xu (Geochimica et Cosmochimica Acta, 2024)

Geochemical indications of hydrothermal fluid through sediments within the Geolin Mounds and Mienhua Volcano hydrothermal fields, southernmost Okinawa Trough - Feng-Hsin Hsu; Chih-Chieh Su; Yu-Shih Lin; Hsiao-Fen Lee; Mei-Fei Chu; Tefang Lan; Shein-Fu Wu; Song-Chuen Chen (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Green manure substitution for potassium fertilizer promotes agro-ecosystem multifunctionality via triggering interactions among soil, plant and rhizosphere microbiome - Qing Zeng; Mei Yin; Li-Bo Fu; Brajesh K. Singh; Si-Yi Liu; Hua Chen; An-Hui Ge; Li-Li Han; Li-Mei Zhang (Plant and Soil, 2024)

Integrated metabolome and transcriptome analysis provides insight into the leaf color change of Cymbidium ensifolium - Huan Mei; Xiaoying Zhang; Fukang Zhao; Ruoxin Ruan; Qiaojuan Fu (Acta Physiologiae Plantarum, 2024)

Unveiling combined ecotoxicity: Interactions and impacts of engineered nanoparticles and PPCPs - Xiang Li; Liyan Li; Liang Tang; Jingting Mei; Jing Fu (Science of The Total Environment, 2024)

Outer membrane vesicles of avian pathogenic Escherichia coli induce necroptosis and NF-κB activation in chicken macrophages via RIPK1 mediation - Zhe Li; Wenbin Shang; Ting Mei; Dandan Fu; Feng Xi; Ying Shao; Xiangjun Song; Zhenyu Wang; Kezong Qi; Jian Tu (Research in Veterinary Science, 2024)

Two unprecedented neuroprotective 2-(2-phenylethyl)chromone derivatives from cultivated “Qi-Nan” agarwood of Aquilaria sinensis - Lin Zhang; Hao Wang; Wen-Hua Dong; Jun Zeng; Li Yang; Wei Li; Hui-Qin Chen; Jing-Zhe Yuan; Cai-Hong Cai; Zhen-Yu Li; Wen-Li Mei; Hao-Fu Dai (Phytochemistry Letters, 2024)

Analysis of novel In2S3/polyimide Z-scheme heterojunctions with enhanced photocatalytic target compound degradation efficiency - Min Fu; Mei Yang; Jinwu Bai; Yi Li; Meng Fang; Peng Lu; Xue Kuang (Journal of Environmental Chemical Engineering, 2024)

Novel material to enhance the integrity of CCUS cement sheath: Exploration and application of calcium aluminate cement - Peng Gong; Huacai Fu; Dan He; Yuanpeng Wu; Kaiyuan Mei; Chunmei Zhang; Xin He; Tao Liu; Shangdong Li; Xiaowei Cheng (Gas Science and Engineering, 2024)

Self-Healing and shape memory reconfigurable Poly(urethane-urea-amide) elastomers containing multiple dynamic bonds for improving performance of 4D printout - Zhen Li; Ziwei Cao; Qianlong Zhao; Shuxiang Mei; Yuancheng Zhang; Wei Zhao; Xin Li; Xiaomeng Zhang; Zhe Cui; Peng Fu; Xinchang Pang; Minying Liu (Chemical Engineering Journal, 2024)

Evaluation of weak genotoxicity of hydroxychloroquine in human TK6 cells - Xilin Li; Yuan Le; Yuxi Li; Si Chen; Lei Guo; Xin Fu; Mugimane G. Manjanatha; Nan Mei (Toxicology Letters, 2024)

Combined analysis of transcriptomics and metabolomics provide insights into the antibacterial mechanism of bacteriocin XJS01 against multidrug-resistant Staphylococcus aureus - Jian-Ping Ying; Chao-Min Fu; Yan-Chun Wu; Ya-Mei Chen; Xiao-Yu Liu; Qi-Lin Zhang; Hui Liu; Ming-Zhong Liang (Science of The Total Environment, 2024)

Timing of India-Asia suturing: Evidence from a remnant peripheral foreland basin in Xigaze, South Tibet - Xu-Dong Guo; Lin Ding; Qiu-yun Guan; Deng Zeng; Chao Wang; Gui-zhen Guo; Hou-Qi Wang; Mei-Yu Liu; Xiang-Li Ding; Muhammad Qasim; Ya-Hui Yue; Jing Xie; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Zinc isotopes revealed the role of ore-hosting carbonate rocks in the formation of MVT deposits: A case study of the Huize Pb Zn deposit, SW China - Hao Zhang; Jia-Xi Zhou; Mei-Fu Zhou; Zheng-Peng Yue; Ye He (Journal of Geochemical Exploration, 2024)

Late Ordovician lingulid brachiopods from the Pingliang Formation (Shaanxi Province, North China): Morphological and ecological implications - Yue Liang; Rao Fu; Yazhou Hu; Fan Liu; Baopeng Song; Mei Luo; Xinyi Ren; Jiayue Wang; Caibin Zhang; Ruisen Fang; Xuan Yang; Lars E. Holmer; et al. (Journal of Asian Earth Sciences, 2024)

Devonian stratiform ironstone deposits in South China formed in a shallow marine environment of a passive continental margin - Mei-Fu Zhou; Yuanjun Jonathan Lyu; Zerui Ray Liu; Ping-Ping Liu; Lei Meng; Wenhong Johnson Qiu; Wen Winston Zhao (Journal of Asian Earth Sciences, 2024)

Emplacement and ore potential of the Permian Pobei mafic–ultramafic complex, NE Tarim, NW China - Sheng-Hong Yang; Mei-Fu Zhou; Christina Yan Wang; Changyi Jiang (Journal of Asian Earth Sciences, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

The level of CmFRQ is associated with the degeneration and rejuvenation of Cordyceps militaris fruiting body - Ming-Jia Fu; Dan-Dan Zhang; Jing-Mei Peng; Lei Feng; Zi-Hai Yang; Zi-Yan Huang (Biologia, 2024)

Vertical variation of source-apportioned PM2.5 and selected volatile organic compounds near an elevated expressway in an urban area - Ho-Tang Liao; Chien-Mei Yen; Yu-Rui Chen; Jyun-De Wu; Shih-Wei Tsai; Chang-Fu Wu (Environmental Science and Pollution Research, 2024)

Diisoprenyl-cyclohexene-type meroterpenoids from a mangrove endophytic fungus Aspergillus sp. GXNU-Y65 and their anti-nonalcoholic steatohepatitis activity in AML12 cells - Feng Qin; Li Luo; Yu-Chen Liu; Xiang-Long Bo; Fu-Rong Wu; Fan-Fan Wang; Mei-Jing Tan; You-Quan Wei; Xiao-Bing Dou; Cai Yi Wang; Xi-Shan Huang; Heng-Shan Wang (Phytochemistry, 2024)

Two unprecedented 2-(2-phenethyl)chromone dimers from red soil agarwood of Aquilaria crassna - Hong-Xing Chai; Hao Wang; Jun Zeng; Wen-Hua Dong; Wen-Li Mei; Bei Jiang; Wei Li; Hao-Fu Dai (Phytochemistry Letters, 2024)

Homoerythrina-type alkaloids with neuroprotective activity from the branches of Cephalotaxus hainanensis Li - Hao Yan; Hao Wang; Peng-Wei Chen; Li Yang; Hui-Qin Chen; Fei Wu; Pei Wang; Hao-Fu Dai; Xiao-Long Huang; Shuang-Qing Zhou; Wen-Li Mei (Phytochemistry Letters, 2024)

Causes of low mercury levels in fish from the Three Gorges Reservoir, China - Yulei Zhou; Qing Xie; Yongmin Wang; Hongjian Lü; Mei Fu; Dingyong Wang; Jiajia Li (Journal of Hazardous Materials, 2024)

Synergy of Fenton-like property and self-oxygen supply for realizing enhanced near-infrared-driven integrated wastewater treatment - Hao Jiang; Mei Yan; Hao Chen; Yutuo Fu; Chongshen Guo (Fuel, 2024)

Effects of tillage practices on soil organic carbon, microbial community and necromass in a double rice cropping system - Jian-Ying Qi; Xiang-Bin Yao; Xue-Chan Zhang; Mei-Yi Fan; Jian-Fu Xue; Jun-Li Cao; Ahmad Latif Virk; Sheng-Gang Pan; Xiang-Ru Tang (Applied Soil Ecology, 2024)

Synthesis and cytotoxic activity of ethyl ferulate derivatives as potent anti-inflammatory agents - Dan-ni Fu; Zi-yi Kong; Wen Sun; Chun-mei Bai; Yun Wu; Ming Bian; Qian-qian Ma (Natural Product Research, 2024)

The dynamic mechanism of scientific and technological innovation in China’s marine biomedical industry - Xiu-Mei Fu; Yan-Xin Tan; Ying Liu; Ying-Hui Han; Qiao-Qiao Qi; Jing-Hang Li; Chun-Yu Lin (Frontiers in Marine Science, 2024)
As one of the important forces promoting the development of the marine economy, the marine biomedical industry (MBI) shows typical knowledge and technology-intensive characteristics. It is of great significance to explore the industrial innovation dynamic mechanism for breaking through the bottleneck of innovative development as well as achieving high-quality development. This paper constructed a system dynamics model for scientific and technological innovation (STI) in the MBI and then explored the dynamic mechanism of STI in the industry through simulation. The study found that, in the innovation environment subsystem, the two factors of the intellectual property protection intensity and the government’s scientific research funding input had the most significant positive driving effects on STI of the MBI; the promotion of government education funding input showed a significant strengthening trend over time, while the marine environmental regulation intensity had comparatively little effect on the level of STI. In the subsystem of innovation input, both innovation funding input and innovation personnel input were the direct driving forces for the improvement of the STI level. And enterprises played a dominant role in STI because the STI level of the MBI was more sensitive to the changes in enterprise innovation input. Compared with the individual factor input, the synergistic promotion effect of multiple factors is more significant. In addition, it was found that there was a low conversion rate of scientific research achievements in China’s MBI by analyzing the influence of various factors changing on technological output and economic output. Based on the research results, this paper puts forward corresponding policy suggestions in order to provide theoretical support and a practical basis for promoting the technological innovation level of China’s MBI as well as references for other countries.

Surface and subsurface runoff generation processes and their influencing factors on a hillslope in northern China - Tonggang Fu; Jintong Liu; Hui Gao; Fei Qi; Feng Wang; Mei Zhang (Science of The Total Environment, 2024)

Soil properties and organochlorine compounds co-shape the microbial community structure: A case study of an obsolete site - Yu Liu; Fang Wang; Ziquan Wang; Leilei Xiang; Yuhao Fu; Zhiliang Zhao; Fredrick Orori Kengara; Zhi Mei; Chao He; Yongrong Bian; Ravi Naidu; Xin Jiang (Environmental Research, 2024)

Trace element systematics of magnetite from alkaline mafic–ultramafic intrusions of the Permian Emeishan large igneous province, SW China - Zhen-Chao Wang; Xiao-Wen Huang; Ping-Ping Liu; Mei-Fu Zhou (Contributions to Mineralogy and Petrology, 2024)

The data as a production factor: nonlinear effects of factor efficiency on haze pollution - Mei-Rui Zhong; Jia-Yu Fu; Han Zou (Environment, Development and Sustainability, 2023)

A comprehensive review on shale studies with emphasis on nuclear magnetic resonance (NMR) technique - Yujie Yuan; Reza Rezaee; Mei-Fu Zhou; Stefan Iglauer (Gas Science and Engineering, 2023)

Development and characterization of self-emulsifying high internal phase emulsions using endogenous phospholipids from Antarctic krill oil - Dong-wen Fu; Jing-jing Li; Dong-mei Dai; Da-yong Zhou; Bei-wei Zhu; Liang Song (Food Chemistry, 2023)

CDK6 is a novel predictive and prognosis biomarker correlated with immune infiltrates in multiple human neoplasms, including small cell lung carcinoma - Guo-Sheng Li; Zhi-Guang Huang; Dong-Ming Li; Yu-Lu Tang; Jin-Hua Zheng; Lin Yang; Yue Feng; Jun-Xi Peng; Jing-Xiao Li; Yu-Xing Tang; Neng-Yong Zeng; Mei-Hua Jin; et al. (Functional & Integrative Genomics, 2023)

Editorial Expression of Concern: Induction of Human Bone Marrow Mesenchymal Stem Cells Differentiation into Neural-Like Cells Using Cerebrospinal Fluid - Ying Ye; Yin-Ming Zeng; Mei-Rong Wan; Xian-Fu Lu (Cell Biochemistry and Biophysics, 2023)

Numerical study of double-chambered perforated caisson with a top cover based on SPH method - Xiaocheng Tang; Huayu Liu; Lili Mei; Pengshuai Fu; Dongrui Song; Hongzhou Chen (Frontiers in Marine Science, 2023)
The Smoothed Particle Hydrodynamics (SPH) method modified by Corrective Smoothed Particle Method (CSPM) and Riemann solution is employed to simulate the interaction between double-chambered perforated caissons and waves. The accuracy and applicability of the numerical method are verified by the theoretical values and experimental data through comparisons. The effects of the top cover height s , the width of the wave dissipation chamber B and the perforated rate μ on the wave surface η or wave pressure p of the caisson are numerically analysis. The results show that under the calculated wave conditions, the top cover height s and perforated rate μ are significant factors affecting the wave dissipation performance of the caisson, while the width of the wave dissipation chamber B has little effect on the wave surface η . In the meanwhile, with the increase of the top cover height s , the wave pressure p on the front perforated plate and the back wall at the static water level gradually decreases, and the wave pressure p on the back perforated plate first decreases and then increases. In addition, the modified SPH method is also used to explore the changes of the pressure field and the velocity field of water particles, tracing the instantaneous velocity of water particles at different positions at different time, and describe the motion state of water particles, which provides effective facilitates for investigating the interaction between double-chambered perforated caissons and waves.

The impact of cooperative innovation network on innovation output of China's marine biomedical industry - Xiu-Mei Fu; Ying-Hui Han; Ying Liu; Qiao-Qiao Qi; Yan-Xin Tan; Meng Gao; Chun-Yu Lin (Ocean & Coastal Management, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

Cretaceous Nb-enriched basalts in the western Gan-Hang belt, South China: A response to slab window opening during the Paleo-Pacific ridge subduction - Qiong Chen; Mei-Fu Zhou; Min Sun; Hao Cheng; Ping-Ping Liu (Lithos, 2023)

Ophiolites and Earth's mantle ophiolites, podiform chromitites and deep mantle recycling - Paul T. Robinson; Mei-Fu Zhou; Jingsui Yang; Fahui Xiong; Peng-Fei Zhang (Lithos, 2023)

Generational effects and abnormalities in craniofacial chondrogenesis in zebrafish (Danio rerio) embryos upon maternal exposure to estrogen endocrine disrupting chemicals - Yu-Jen Tseng; Fu-I Lu; Su Mei Wu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Magnetic biochar/quaternary phosphonium salt reduced antibiotic resistome and pathobiome on pakchoi leaves - Zhi Mei; Yuhao Fu; Fang Wang; Leilei Xiang; Fang Hu; Jean Damascene Harindintwali; Mingyi Wang; Marko Virta; Syed A. Hashsham; Xin Jiang; James M. Tiedje (Journal of Hazardous Materials, 2023)

Impact of environmental characteristics on children's gut microbiota – A pilot study in assessing the role of indoor microbiome and metabolites - Mei Zhang; Hao Tang; Yang Chen; Zhuoru Chen; Yanyi Xu; Xi Fu; Yu Sun; Zhuohui Zhao (Environmental Research, 2023)

Semiconductors modified gourd-shaped hollow PtNi and their directional electron and mass transfer effects - Fu-Fei Pu; Yu-Xuan Xiao; Xiong Yang; Fei Yu; Lei Xia; Jiang-Bo Chen; Lu Wu; Jing-Jing Xie; Wen-Ying Zhao; Yu Liu; Li-Ying Wang; Jie Ying; et al. (Chemical Engineering Journal, 2023)

Optical properties and molecular composition of wintertime atmospheric water-soluble organic carbon in different coastal cities of eastern China - Haibiao Chen; Caiqing Yan; Qinglong Fu; Xinfeng Wang; Jiao Tang; Bin Jiang; Honglei Sun; Tiancheng Luan; Qiaoyun Yang; Qianbiao Zhao; Jun Li; Gan Zhang; et al. (Science of The Total Environment, 2023)

Variations of PM2.5-bound elements and their associated effects during long-distance transport of dust storms: Insights from multi-sites observations - Qingpeng Meng; Caiqing Yan; Ruiyu Li; Tianle Zhang; Mei Zheng; Yue Liu; Miao Zhang; Guixia Wang; Yuming Du; Chunlin Shang; Peng Fu (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Hg bioaccumulation in the aquatic food web from tributaries of the Three Gorges Reservoir, China and potential consumption advisories - Xueheng Wang; Qing Xie; Yongmin Wang; Hongjian Lü; Mei Fu; Dingyong Wang; Jiajia Li (Journal of Hazardous Materials, 2023)

Efficient electrochemical CO2 reduction via CuAg doped CeO2 - Mei Luo; Xiangmin Fu; Shuo Geng; Ziwei Li; Min Li (Fuel, 2023)

A novel bacteriocin RSQ01 with antibacterial activity and its application and metabolomic mechanism in milk preservation - Yan-Mei Zhang; Lin-Yu Yang; Jian-Ping Ying; Chao-Min Fu; Gang Wu; Xiao-Ran Li; Qi-Lin Zhang (Food Control, 2023)

Maternal di-(2-ethylhexyl) phthalate exposure elicits offspring IFN-λ upregulation: Insights from birth cohort, murine model, and in vitro mechanistic analysis - Fu-Chen Kuo; Mei-Lan Tsai; Shin-Ting Wu; Sih-Syuan Li; Chia-Fang Wu; Shu-Lin Wang; Michael W.Y. Chan; Jau-Ling Suen; Ming-Tsang Wu; Chih-Hsing Hung (Food and Chemical Toxicology, 2023)

Magnesium–oxygen isotope constraints on the origin of rodingites in oceanic lithosphere - Mei-Shan Zhao; Yi-Xiang Chen; Jia-Wei Xiong; Xin-Yue Qiao; Yong-Fei Zheng; Wen-Yong Duan; Fang Huang; Zi-Fu Zhao (Chemical Geology, 2023)

Design method of combined stiffened pressure hulls with variable-curvature characteristic - Xiao Fu; Zhiyuan Mei; Shuo Wang; Xuefei Bai; Er Zhang; Guotao Chen; Huadong Li (Ocean Engineering, 2023)

Genomic analysis of Marinomonas algicola SM1966T reveals its role in marine sulfur cycling - Min Zhang; Xiao-Di Wang; Yue Lin; Shu-Yan Wang; Shan Zhang; Jin Cheng; Mei-Ling Sun; Peng Wang; Hui-Hui Fu; Chun-Yang Li; Nan Zhang (Marine Genomics, 2023)

Potentially important regolith-hosted Sc deposits related to alkaline igneous complexes of the Permian Emeishan large igneous Province, SW China - Wen Winston Zhao; Mei-Fu Zhou; Zhengchao Wang; Yan Hei Martin Li; Liang Qi; Wei Terry Chen; Yu Shen (Journal of Asian Earth Sciences, 2023)

Antibiotic resistance genes in food production systems support One Health opinions - James M. Tiedje; Yuhao Fu; Zhi Mei; Andreas Schäffer; Qingyuan Dou; Wulf Amelung; Martin Elsner; Joseph Adu-Gyamfi; Lee Heng; Marko Virta; Xin Jiang; Hauke Smidt; et al. (Current Opinion in Environmental Science & Health, 2023)

A triple-cycle amplification biosensor for colorimetric detection of mutant PIK3CAE545K based on cascade-driven DNA walker and branched hybridization strand reaction - Mei Yang; He Zhang; Wenjie Ma; Qiong Liu; Xin Fu; Yu Fu (Analytica Chimica Acta, 2023)

Health Risk Assessment of Organophosphate Flame Retardants in Soil Across China Based on Monte Carlo Simulation - Mei-Hong Chen; Shi-Ming Jia; Pu-Fei Yang; Fu-Jie Zhu; Wan-Li Ma (Archives of Environmental Contamination and Toxicology, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

Integration profiling of transcriptome and metabolome reveals the effect of hydrogen peroxide on nucleic acid metabolism in postharvest broccoli during storage - Yuxiao Zhang; Ying Chen; Yanyin Guo; Mei Yang; Ruiqing Fu; Yupeng Sun; Zhengli Wang; Yunqiao Wang; Lingxing Guan; Xinhua Song (Postharvest Biology and Technology, 2023)

Bisabolane-type sesquiterpenoids with potential anti-inflammatory and anti-HIV activities from the stems and leaves of Morinda citrifolia - Ying-Ying Zhao; Yu-Jie Li; Xiao-Mei Yu; Qin-Ting Su; Li-Wen Wang; Yu-Shu Zhu; Yan-Hui Fu; Guang-Ying Chen; Yan-Ping Liu (Natural Product Research, 2023)

Cytotoxic steroids from the stems of Strophanthus divaricatus - Hong-Ling Ran; Sheng-Zhuo Huang; Hao Wang; Li Yang; Cui-Juan Gai; Rui-Jun Duan; Hao-Fu Dai; Ya-Li Guan; Wen-Li Mei (Phytochemistry, 2023)

Colletotrins A-C, three new sesquiterpenes from the endophytic fungus Colletotrichum iris strain S11 - Ning Chen; Shi-Yu Qiu; Song-Mei Lu; Shi-Wei Chen; Ji-Rui Wei; Fu-Wen Yang; Hui-Chun Geng; Min Zhou (Phytochemistry Letters, 2023)

Complete genome sequence of Bacillus cereus 2-6A, a marine exopolysaccharide-producing bacterium isolated from deep-sea hydrothermal sediment of the Pacific Ocean - Xuan Zou; Chuan-Lei Suo; Xiao-Mei Geng; Chun-Yang Li; Hui-Hui Fu; Yi Zhang; Peng Wang; Mei-Ling Sun (Marine Genomics, 2023)

Hydrochromic wood biocomposites for humidity and moisture detection - Yujie Chen; Chaozheng Liu; Zhaolun Liang; Lei Ye; Lin Liu; Zhipeng Liu; Xinhao Feng; Lloyd Donaldson; Tripti Singh; Xianxu Zhan; Jingquan Han; Qiliang Fu; et al. (Chemical Engineering Journal, 2023)

Impact of particle size of cell carrier on caproate fermentation in a cell immobilized system: Focusing on the improvement of caproate production in batch and continuous operation modes - Yuxuan Sun; Jiaqi Fu; Yan Liu; Wenhui Zhang; Chengmei Li; Hossain M. Zabed; Mei Zhao; Weimin Liu; Shuhao Huo; Cunsheng Zhang; Xianghui Qi (Chemical Engineering Journal, 2023)

Li and O isotopes of mantle xenoliths from deep fault-related Cenozoic basalts in eastern China: The role of subducted components in the generation of the heterogeneous lithospheric mantle - Qiong Chen; Mei-Fu Zhou; Xiao-Ping Xia; Ping-Ping Liu (Chemical Geology, 2023)

The Na+/H+ antiporter GbSOS1 interacts with SIP5 and regulates salt tolerance in Gossypium barbadense - Fu-Chun Xu; Mei-Juan Wang; Ya-Wei Guo; Jie Song; Wei Gao; Lu Long (Plant Science, 2023)

Di-(2-ethylhexyl) phthalate impairs angiogenesis and hematopoiesis via suppressing VEGF signaling in zebrafish - Yang-Xi Hu; Bo-Wen Hu; Ya-Sha Chen; Hong-Min You; Mei-Rong Bai; Lu-Jun Zhang; Zhi-Fu Guo; Chun Liang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Two new indole alkaloids isolated from a mangrove-derived fungus Colletotrichum sp. HD-1 - Dan He; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Hong-Juan Zhu; Hao-Fu Dai; You-Gen Wu; Dong-Mei Yang; You-Xing Zhao (Phytochemistry Letters, 2023)

Quantifying and assessing the infiltration potential of green infrastructure in urban areas using a layered hydrological model - Xiaoran Fu; Jiahong Liu; Zhonggen Wang; Dong Wang; Weiwei Shao; Chao Mei; Jia Wang; Yan-fang Sang (Journal of Hydrology, 2023)

Egg-yolk-derived carbon dots@albumin bio-nanocomposite as multifunctional coating and its application in quality maintenance of fresh litchi fruit during storage - Xianjie Su; Hetong Lin; Bofei Fu; Shanshan Mei; Mengshi Lin; Hongbin Chen; Zongping Zheng; Hangyu Bo; Da-Peng Yang; Yifen Lin (Food Chemistry, 2023)

Ecological value of mariculture shellfish resources in China: Assessment and management - Chun-Yu Lin; Gui-Lin Dai; Yang Liu; Meng-Qi Zhang; Ying Liu; Wen Jiang; Xiu-Mei Fu; Han-Xue Chen (Marine Policy, 2023)

A new phragmalin-type limonoid from the roots of Trichilia sinensis - Shou-Bai Liu; Jin-Ling Yang; Hui-Qin Chen; Cheng-min Yang; Hao Wang; Cai-Hong Cai; Jing-Zhe Yuan; Wen-Li Mei; Hao-Fu Dai (Phytochemistry Letters, 2023)

Effect of etching and reduction time on the structure, performance, and stability of GO-based membrane for water purification - Fan-xin Kong; Lian You; Jia-mei Cao; Qian Liu; Ping Xia; Jin-fu Chen (Journal of Environmental Chemical Engineering, 2023)

Detection of polycyclic aromatic hydrocarbons using a high performance-single particle aerosol mass spectrometer - Yao Zhang; Chenglei Pei; Jinwen Zhang; Chunlei Cheng; Xiufeng Lian; Mubai Chen; Bo Huang; Zhong Fu; Zhen Zhou; Mei Li (Journal of Environmental Sciences, 2023)

Purifying Metallurgical-Grade Silicon to 4N with 3D Porous Structure by Integrated Metallurgy-Materials Phase Separation - Jian Song; Yifan Liu; Shixiong Mei; Ben Xiang; Jijiang Fu; Siguang Guo; Weili An; Xuming Zhang; Biao Gao; Paul K Chu; Kaifu Huo (Chemical Engineering Journal, 2023)

Phosphorus availability mediates plant–plant interaction and field productivity in maize-grass pea intercropping system: Field experiment and its global validation - Shuang-Guo Zhu; Hong-Yan Tao; Wen-Bo Li; Rui Zhou; Yan-Wen Gui; Li Zhu; Xiao-Lin Zhang; Wei Wang; Bao-Zhong Wang; Fu-Jian Mei; Hao Zhu; You-Cai Xiong (Agricultural Systems, 2023)

Monitoring of tree tilt motion using lorawan-based wireless tree sensing system (IoTT) during super typhoon Mangkhut - Wai Yi Chau; Yu-Hsing Wang; Siu Wai Chiu; Pin Siang Tan; Mei Ling Leung; Hoi Lun Lui; Jimmy Wu; Yun Man Lau; Kuan-Fu Liu; Billy Chi Hang Hau (Agricultural and Forest Meteorology, 2023)

Proteomics revealed the effects of nucleic acid metabolism, transcription and translation on postharvest broccoli senescence under elevated O2 stress - Yuxiao Zhang; Ying Chen; Yanyin Guo; Yangli Ma; Mei Yang; Ruiqing Fu; Yupeng Sun; Jing Qin (Postharvest Biology and Technology, 2023)

Thermodynamic characteristics of methane hydrate formation in high-pressure microcalorimeter under different reaction kinetics - Juan Fu; Jia-Mei Mo; Shi-Jun Liu; Wen-Zhe Yi; Yi-Song Yu; Neng-You Wu; Xiao-Li Chen; Qiu-Cheng Su; Xiao-Sen Li (Fuel, 2023)

Doping engineering of carrier transporting layers for ambient-air-stable lead-free rudorffite solar cells prepared by thermal-assisted doctor blade coating - Kai-Chi Hsiao; Yen-Fu Yu; Ching-Mei Ho; Meng-Huan Jao; Yu-Hsiang Chang; Shih-Hsuan Chen; Yin-Hsuan Chang; Wei-Fang Su; Kun-Mu Lee; Ming-Chung Wu (Chemical Engineering Journal, 2023)

New insights about the origin of the Shilu Fe-Cu-Co deposit, Hainan Island, South China, with emphasis on the regional metallogeny - Wei Terry Chen; Mei-Fu Zhou; Yanwen Tang (Mineralium Deposita, 2022)

Germanium enrichment in sphalerite with acicular and euhedral textures: an example from the Zhulingou carbonate-hosted Zn(-Ge) deposit, South China - Kai Luo; Alexandre Cugerone; Mei-Fu Zhou; Jia-Xi Zhou; Guo-Tao Sun; Jing Xu; Kang-Jian He; Mao-Da Lu (Mineralium Deposita, 2022)

Plasma Matrix Metalloproeteinase-9 Is Associated with Seizure and Angioarchitecture Changes in Brain Arteriovenous Malformations - Yo-Tsen Liu; Cheng-Chia Lee; Chun-Fu Lin; Hsiu-Mei Wu; Wan-Yuo Guo; Huai-Che Yang; Feng-Chi Chang; Kang-Du Liou; Chung-Jung Lin (Molecular Neurobiology, 2022)

The safety degree evaluation of marine biodiversity in China - Xiu-Mei Fu; Wan-Yu Wu; Fang Yang; Shan-Shan Jiang; Shi-Qi Wang; Xiao-Yan Li; Hui-Ying Tang; Ying Liu; Chang-Yun Wang (Journal of Coastal Conservation, 2022)

Case series of congenital pseudarthrosis of the tibia unfulfilling neurofibromatosis type 1 diagnosis: 21% with somatic NF1 haploinsufficiency in the periosteum - Yu Zheng; Guanghui Zhu; Yaoxi Liu; Weihua Zhao; Yongjia Yang; Zhenqing Luo; Yuyan Fu; Haibo Mei; Zhengmao Hu (Human Genetics, 2022)

Vertical patterns of chlorophyll a in the euphotic layer are related to mesoscale eddies in the South China Sea - Mei-Lin Wu; You-Shao Wang; Yu-Tu Wang; Fu-Lin Sun; Xiaomei Li; Fang-Fang Gu; Jing-Chang Xiang (Frontiers in Marine Science, 2022)
Phytoplankton closely connects with the hydrodynamics and biogeochemical environment of the ocean. While research focusing on both the physiochemical factors and hydrodynamics regulating phytoplankton has already been conducted, the coupling mechanism between mesoscale eddies and the vertical distribution of phyto plankton in the South China Sea (SCS) is still not well understood. Here, phytoplankton was studied under one weak-cold and two warm eddies along the 18°N transect in the SCS. The results show that the vertical distribution of chlorophyll (chl- a ) presented a similar pattern at all four sampling stations. The mixed layer is less than 50 m. It is the same as the meridional salinity gradients that may be distinguished above a depth of 60 m. The subsurface chlorophyll maximum at the edge of a warm (WI) and cold eddy (CI) at E413 and E411 was shallower than that at the edge of a warm eddy (WII) at E407 and E409, indicating that temperature and salinity may be the important driving factors. On the whole, mesoscale eddies had a significant influence on the vertical pattern of chl- a in the SCS during the study period.

Ectomycorrhizal synthesis between two Tuber species and six tree species: are different host-fungus combinations having dissimilar impacts on host plant growth? - Lan-Lan Huang; Yan-Liang Wang; Alexis Guerin-Laguette; Ran Wang; Peng Zhang; Yong-Mei Li; Fu-Qiang Yu (Mycorrhiza, 2022)

Cadinane-type sesquiterpenes with potential anti-inflammatory and anti-HIV activities from the stems and leaves of Mappianthus iodoides - Yan-Ping Liu; Xiao-Mei Yu; Ze-Hua Qiao; Bo Jiang; Lan Xie; Hao-Xuan Tang; Xiao Liang; Yan-Hui Fu (Natural Product Research, 2022)

An ortholog of the MADS-box gene SEPALLATA3 regulates stamen development in the woody plant Jatropha curcas - Mei-Li Zhao; Zhi-Fang Zhou; Mao-Sheng Chen; Chuan-Jia Xu; Zeng-Fu Xu (Planta, 2022)

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

Three-dimensional modelling of stress relaxation of soft clay under complex loading conditions - Jian Li; Dong-Mei Zhang; Pierre-Yves Hicher; Chang-Fu Wei (European Journal of Environmental and Civil Engineering, 2022)

Phenolic compounds from the sclerotia of Inonotus obliquus - Yan-Mei Wei; Li Yang; Wen-Li Mei; Hui-Qin Chen; Cai-Hong Cai; Wei Li; Wen-Hua Dong; Zhi-Bao Chen; Hao-Fu Dai (Natural Product Research, 2022)

Diel variation in anti-predation behavior of a ground squirrel and relationships between vigilance and escape - Ling-Ying Shuai; Mei-Ting Liu; A.-Ping Zhu; Yuan-Yuan Cao; Fu-Shun Zhang (Behavioral Ecology and Sociobiology, 2022)

A new picrotoxane-type sesquiterpene from Dendrobium nobile Lindl - Pei Wang; Xin Chen; Cai-Hong Cai; Fan-Dong Kong; Sheng-Zhuo Huang; Jing-Zhe Yuan; Xing-Lian Xu; Wen-Li Mei; Hao-Fu Dai (Natural Product Research, 2022)

Synthesis, antifungal activity and 3D-QSAR study of novel acyl thiourea compounds containing gem-dimethylcyclopropane ring - Mei Huang; Min Huang; Xiu Wang; Wen-Gui Duan; Gui-Shan Lin; Fu-Hou Lei (Molecular Diversity, 2022)

Development and validation of a 30-day death nomogram in patients with spontaneous cerebral hemorrhage: a retrospective cohort study - Qian Han; Mei Li; Dongpo Su; Aijun Fu; Lin Li; Tong Chen (Acta Neurologica Belgica, 2022)

Distribution of Coomassie Blue Stainable Particles in the Pearl River Estuary, China, Insight Into the Nitrogen Cycling in Estuarine System - Cui-Ci Sun; Wei-Zhong Yue; You-Shao Wang; Wei-Hong He; Yi-Guo Hong; Fu-Lin Sun; Hao Cheng; Mei-Lin Wu; Zhao-Yu Jiang; Fei Jiao; Yu-Tu Wang (Frontiers in Marine Science, 2022)
Distributions of Coomassie Blue stainable particles (CSP), the sources and transports, as well as their implications for nitrogen biogeochemical cycles in the Pearl River estuary (PRE) were investigated during two cruises in August 2016 and January 2017. CSP color concentrations (CSP concentration determined spectrophotometrically) were 73.7–685.3 μg BSA eq L –1 [μg Bovine serum albumin (BSA) equivalent liter –1 ] in August 2016 and 100.6–396.4 μg BSA eq L –1 in January 2017, respectively. CSP concentrations were high in low-salinity waters (<5), and declined from the river to the middle estuary by 80% in the wet season and 55.6% in the dry season, respectively, then increased again in the lower estuary due to high primary production. CSP concentrations were mainly associated with chlorophyll a (Chl a ) concentration except for the turbid mixing zone, suggesting that autochthonous phytoplankton production served as the primary source of CSP in the PRE. The concentrations of nitrogen (N) as CSP in the PRE were comparable to the nitrogen content of particulate hydrolysable amino acids (PHAA). Pictures of CSP taken by microscopy and the correlation between composition of PHAA and the ratio of Chl a /CSP color showed that CSP were relatively degraded due to delivery of old terrestrial protein to river section and extensive microbial degradation during mixing at the upper and middle parts of the estuary, whereas CSP in lower estuary appeared to be more labile due to higher fresh algal production. The contribution of CSP nitrogen (CSP-N) to the particulate nitrogen (PN) pool was 34.98% in summer and 30.8% in winter. The conservative estimate of CSP-N input flux in the Pearl River Delta was about 6 × 10 6 mol N d –1 . These results suggested that CSP was a significant pool of organic nitrogen in the PRE. The study of CSP composition in terms of nitrogen provides new insight into the roles of CSP on nitrogen biogeochemical processes in the turbid and productive estuarine system.

Biogeography of culturable marine bacteria from both poles reveals that ‘everything is not everywhere’ at the genomic level - Qi‐Long Qin; Zhi‐Bin Wang; Qian‐Qian Cha; Sha‐Sha Liu; Xue‐Bing Ren; Hui‐Hui Fu; Mei‐Ling Sun; Dian‐Li Zhao; Andrew McMinn; Yin Chen; Xiu‐Lan Chen; Yu‐Zhong Zhang; et al. (Environmental Microbiology, 2022)
Summary Based on 16S rRNA gene analyses, the same bacterial operational taxonomic units (OTUs) are common to both the Arctic and Antarctic oceans, supporting the concept ‘everything is everywhere’. However, whether the same OTUs from both poles have identical genomes, i.e. whether ‘everything is still everywhere’ at the genomic level has not yet been examined systematically. Here, we isolated, sequenced and compared the genomes of 45 culturable marine bacteria belonging to three genera of Salinibacterium , Psychrobacter and Pseudoalteromonas from both polar oceans. The bacterial strains with identical 16S rRNA genes were common to both poles in every genus, and four identical genomes were detected in the genus Salinibacterium from the Arctic region. However, no identical genomes were observed from opposite poles in this study. Our data, therefore, suggest that ‘everything is not everywhere’ at the genomic level. The divergence time between bacteria is hypothesized to exert a strong impact on the bacterial biogeography at the genomic level. The geographical isolation between poles was observed for recently diverged, highly similar genomes, but not for moderately similar genomes. This study thus improves our understanding of the factors affecting the genomic‐level biogeography of marine microorganisms isolated from distant locations.

Chemical constituents from the barks of Melia azedarach and their PTP1B inhibitory activity - Sheng-Nan Zhang; Lin Huang; Rui-Jing Ma; Mei-Feng Yang; Ben-Fu Wei; Hong-Zhi Song; Heng-Shan Wang; Qin-Gang Tan (Natural Product Research, 2021)

New phenolic acids from the whole herb of Elephantopus scaber Linn. and their anti-inflammatory activity - Lu Fu; Di Pei; Meng Yu; Hai Shang; Jin-Guang Si; Hong-Wu Zhang; Tao Zhang; Zhong-Mei Zou (Natural Product Research, 2021)

Three new dimeric 2-(2-phenylethyl)chromones from artificial agarwood of Aquilaria sinensis - Pan Xiang; Wen-Hua Dong; Cai-Hong Cai; Wei Li; Li-Man Zhou; Hao-Fu Dai; Hui-Qin Chen; Wen-Li Mei (Natural Product Research, 2021)

Do China’s coal-to-gas policies improve regional environmental quality? A case of Beijing - Jianliang Wang; Zonghan Li; Hongkai Ye; Yingdan Mei; Jiaxin Fu; Qi Li (Environmental Science and Pollution Research, 2021)

Bacterial community variations in the South China Sea driven by different chemical conditions - Fu-lin Sun; You-Shao Wang; Mei-Lin Wu; Cui-Ci Sun; Zhao-Yu Jiang; Hao Cheng; Jiao Fei (Ecotoxicology, 2021)

Differential metabolism-associated gene expression of duck pancreatic cells in response to two strains of duck hepatitis A virus type 1 - Zhen Chen; Shao-hua Shi; Yu Huang; Cui-qin Huang; Rong-chang Liu; Long-fei Cheng; Guang-hua Fu; Hong-mei Chen; Chun-he Wan; Qiu-ling Fu (Archives of Virology, 2021)
Several outbreaks of duck hepatitis A virus type 1 (DHAV-1), which were characterized by yellow coloration and hemorrhage in pancreatic tissues, have occurred in China. The causative agent is called pancreatitis-associated DHAV-1. The mechanisms involved in pancreatitis-associated DHAV-1 infection are still unclear. Transcriptome analysis of duck pancreas infected with classical-type DHAV-1 and pancreatitis-associated DHAV-1 was carried out. Deep sequencing with Illumina-Solexa resulted in a total of 53.9 Gb of clean data from the cDNA library of the pancreas, and a total of 29,597 unigenes with an average length of 993.43 bp were generated by de novo sequence assembly. The expression levels of D-3-phosphoglycerate dehydrogenase, phosphoserine aminotransferase, and phosphoserine phosphatase, which are involved in glycine, serine, and threonine metabolism pathways, were significantly downregulated in ducks infected with pancreatitis-associated DHAV-1 compared with those infected with classical-type DHAV-1. These findings provide information regarding differences in expression levels of metabolism-associated genes between ducks infected with pancreatitis-associated DHAV-1 and those infected with classical-type DHAV-1, indicating that intensive metabolism disorders may contribute to the different phenotypes of DHAV-1-infection.

A new ergostane derivative from the leaves of Heynea trijuga Roxburgh - Shou-Bai Liu; Zheng Cui; Hui-Qin Chen; Hao Wang; Wen-Hua Dong; Cai-Hong Cai; Wen-Li Mei; Hao-Fu Dai (Natural Product Research, 2021)

Genome-Wide Identification and Expression Profiling of the bHLH Transcription Factor Gene Family in Saccharum spontaneum Under Bacterial Pathogen Stimuli - Ahmad Ali; Talha Javed; Uroosa Zaheer; Jing-Ru Zhou; Mei-Ting Huang; Hua-Ying Fu; San-Ji Gao (Tropical Plant Biology, 2021)

Triterpene saponins from tea seed pomace ( Camellia oleifera Abel) and their cytotoxic activity on MCF-7 cells in vitro - Xin-Fu Zhang; Ying-Ying Han; Tai-Mei Di; Li-Ping Gao; Tao Xia (Natural Product Research, 2021)

Resource status and protection strategies of mangroves in China - Xiu-Mei Fu; Hui-Ying Tang; Yang Liu; Meng-Qi Zhang; Shan-Shan Jiang; Fang Yang; Xiao-Yan Li; Chang-Yun Wang (Journal of Coastal Conservation, 2021)
Mangrove is a typical natural landscape with great ecological, social and economic functions and values, and should be highly valued and protected. However, in the past few decades, mangrove resources have suffered serious damage, and there are also many deficiencies in mangrove protection. Chinese mangroves, as an important part of the global mangroves, are of great research value. In the present study, the status and historical dynamic process of Chinese mangrove resources were investigated and discussed to illustrate the problems of resources from three aspects, including mangrove distribution, area and plant species. Based on field research, literature research and data analysis, it was revealed that Chinese mangroves are distributed in eight provinces and regions along the southeast coast with an area of 35,749.25 hm 2 , 38 species and 40 nature reserves. The protection situation and deficiencies were analyzed from the establishment and management of nature reserves. Based on the resource status and problems, reasonable strategies were proposed to protect and manage mangroves mainly from four aspects, including publicity and education, resources restoration and protection technology, legal system establishment, and comprehensive protection and management.

Three new 5,6,7,8-tetrahydro-2-(2-phenylethyl)chromones and one new dimeric 2-(2-phenylethyl)chromone from agarwood of Aquilaria crassna Pierre ex Lecomte in Laos - Yang-Mei Zhao; Li Yang; Fan-Dong Kong; Wen-Hua Dong; Wei Li; Hui-Qin Chen; Hao Wang; Cai-Hong Cai; Cui-Juan Gai; Wen-Li Mei; Hao-Fu Dai (Natural Product Research, 2021)

Kynurenine pathway as alternative biosynthetic pathway for fusaric acid in Fusarium oxysporum f.sp. cubense - Tao Zeng; Hui-Cai Zeng; Mei-Ying Fu; Kai-Kun Huang; Jian-Chun Guo; Xin-Wen Hu (Australasian Plant Pathology, 2021)

Marinifaba aquimaris gen. nov., sp. nov., a novel chitin‐degrading gammaproteobacterium in the family Alteromonadaceae isolated from seawater of the Mariana Trench - Xin Sui; Xiao-yan He; Ning-hua Liu; Yan-ru Dang; Qian-qian Cha; Mei-ling Sun; Chun-yang Li; Hui-hui Fu; Xiao-yan Song; Qi-long Qin; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

Tritonibacter aquimaris sp. nov. and Tritonibacter litoralis sp. nov., two novel members of the Roseobacter group isolated from coastal seawater - Na Li; Xiao-yan He; Ning-hua Liu; Tie-ji Gu; Jian Li; Yu-hui Geng; Shan Zhang; Peng Wang; Hui-hui Fu; Mei Shi; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

Spatial prediction of soil calcium carbonate content based on Bayesian maximum entropy using environmental variables - Mei Shan; Shuang Liang; Hongchen Fu; Xiaoli Li; Yu Teng; Jingwen Zhao; Yaxin Liu; Chen Cui; Li Chen; Hai Yu; Shunbang Yu; Yanling Sun; et al. (Nutrient Cycling in Agroecosystems, 2021)

TAPP1 Represses the Differentiation of Oligodendrocyte and its Deficiency Accelerates Myelin Regeneration after Demyelinating Injuries - Ruyi Mei; Jiaying Fu; Chunxia Jiang; Junlin Yang; Kang Zheng; Aifen Yang; Mengsheng Qiu; Xiaofeng Zhao (Neuroscience Bulletin, 2021)

The substrate‐dependent regulatory effects of the AfeI /R system in Acidithiobacillus ferrooxidans reveals the novel regulation strategy of quorum sensing in acidophiles - Xue‐Yan Gao; Chang‐Ai Fu; Likai Hao; Xiu‐Feng Gu; Rui Wang; Jian‐Qiang Lin; Xiang‐Mei Liu; Xin Pang; Cheng‐Jia Zhang; Jian‐Qun Lin; Lin‐Xu Chen (Environmental Microbiology, 2021)
Summary A LuxI/R‐like quorum sensing (QS) system (AfeI/R) has been reported in the acidophilic and chemoautotrophic Acidithiobacillus spp. However, the function of AfeI/R remains unclear because of the difficulties in the genetic manipulation of these bacteria. Here, we constructed different afeI mutants of the sulfur‐ and iron‐oxidizer A . ferrooxidans , identified the N‐acyl homoserine lactones (acyl‐HSLs) synthesized by AfeI, and determined the regulatory effects of AfeI/R on genes expression, extracellular polymeric substance synthesis, energy metabolism, cell growth and population density of A . ferrooxidans in different energy substrates. Acyl‐HSLs‐mediated distinct regulation strategies were employed to influence bacterial metabolism and cell growth of A . ferrooxidans cultivated in either sulfur or ferrous iron. Based on these findings, an energy‐substrate‐dependent regulation mode of AfeI/R in A . ferrooxidans was illuminated that AfeI/R could produce different types of acyl‐HSLs and employ specific acyl‐HSLs to regulate specific genes in response to different energy substrates. The discovery of the AfeI/R‐mediated substrate‐dependent regulatory mode expands our knowledge on the function of QS system in the chemoautotrophic sulfur‐ and ferrous iron‐oxidizing bacteria, and provides new insights in understanding energy metabolism modulation, population control, bacteria‐driven bioleaching process, and the coevolution between the acidophiles and their acidic habitats.

Cosmosporasides F–H, three new sugar alcohol conjugated acyclic sesquiterpenes from a Fusarium oxysporum fungus - Ying Fu; Ping Wu; Jinghua Xue; Mei Zhang; Xiaoyi Wei (Natural Product Research, 2020)

Comparative transcriptome analysis of gynoecious and monoecious inflorescences reveals regulators involved in male flower development in the woody perennial plant Jatropha curcas - Mei-Li Zhao; Mao-Sheng Chen; Jun Ni; Chuan-Jia Xu; Qing Yang; Zeng-Fu Xu (Plant Reproduction, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Whether the carbon emission from green roofs can be effectively mitigated by recycling waste building material as green roof substrate during five-year operation? - Liangqian Fan; Jingting Wang; Xiaoling Liu; Hongbing Luo; Ke Zhang; Xiaoying Fu; Mei Li; Xiaoting Li; Bing Jiang; Jia Chen; Shuzhi Fu; You Mo; et al. (Environmental Science and Pollution Research, 2020)

Characteristics of methane emissions in the Living Water Garden in Chengdu City from 2012 to 2017 - Ru Xue; Xiaoling Liu; Xiaoying Fu; Hongbing Luo; Ke Zhang; Bruce C. Anderson; Mei Li; Bo Huang; Lijuan Yu; Xiaoting Li; Shuzhi Fu; Aiping Pu; et al. (Environmental Science and Pollution Research, 2020)

Sauchinone: a prospective therapeutic agent-mediated EIF4EBP1 down-regulation suppresses proliferation, invasion and migration of lung adenocarcinoma cells - Sheng-Qian Li; Jing Feng; Ming Yang; Xiao-Peng Ai; Mei He; Fu Liu (Journal of Natural Medicines, 2020)

Dynamics of radial oxygen loss in mangroves subjected to waterlogging - Hao Cheng; Mei-Lin Wu; Chang-Da Li; Fu-Lin Sun; Cui-Ci Sun; You-Shao Wang (Ecotoxicology, 2020)

Distribution patterns and source identification for heavy metals in Mirs Bay of Hong Kong in China - Mei-Lin Wu; Hao Cheng; Hui Zhao; Fu-Lin Sun; Yu-Tu Wang; Jian-Ping Yin; Jiao Fei; Cui-Ci Sun; You-Shao Wang (Ecotoxicology, 2020)

Phytoplankton community, structure and succession delineated by partial least square regression in Daya Bay, South China Sea - Mei-Lin Wu; Yu-Tu Wang; Hao Cheng; Fu-lin Sun; Jiao Fei; Cui-Ci Sun; Jian-Ping Yin; Hui Zhao; You-Shao Wang (Ecotoxicology, 2020)

Evaluation of dynamic stability and analysis of reinforcement measures of a landslide under seismic action: a case study on the Yanyangcun landslide - Xiaodong Fu; Qian Sheng; Wenjie Du; Hongru Mei; He Chen; Yuxiang Du (Bulletin of Engineering Geology and the Environment, 2020)

Spatial Pattern of Female Non-agricultural Employment and Its Driving Forces in Guangdong Province, China: A Perspective of Individual and Family-level - Zhanhui Fu; Lin Mei; Yanjun Liu; Junfeng Tian; Rumin Zheng; Jing Tian (Chinese Geographical Science, 2020)

Postprandial proximal gastric acid pocket and its association with gastroesophageal acid reflux in patients with short-segment Barrett’s esophagus - Yuan-yuan Nian; Xian-mei Meng; Jing Wu; Fu-chu Jing; Xue-qin Wang; Tong Dang; Jun Zhang (Journal of Zhejiang University-SCIENCE B, 2020)

Effects of prenatal exposure to NO2 on children’s neurodevelopment: a systematic review and meta-analysis - Li Shang; Liren Yang; Wenfang Yang; Liyan Huang; Cuifang Qi; Zixuan Yang; Zhuxuan Fu; Mei Chun Chung (Environmental Science and Pollution Research, 2020)
The neurotoxicity of NO 2 exposure is well-known and potentially causes impaired of neural functions. This review aimed to estimate associations between prenatal NO 2 exposure and neurodevelopment for children. Articles published until May 2019 reported prenatal NO 2 exposure and children’s cognition, psychomotor, language, attention, IQ, and behavior function were searched according to all related terms. The main databases we retrieved included PubMed, Web of Science, Embase, and Cochrane Library. Coefficient was extracted, conversed, and synthesized by random effects meta-analysis. Meanwhile, qualitatively describe would be used for some studies which cannot be synthesized quantitatively for lack of quantity or methods inconsistency. Finally, a total of 3848 citations were searched, and only 10 studies were included. We estimated that per 10 μg/m 3 increase of NO 2 during pregnancy was associated with a − 0.76 point decrease in global psychomotor (95% CI, − 1.34, − 0.18) and a − 0.62 point decrease in fine psychomotor for children (95% CI, − 1.09, − 0.16). But no significant association found in general cognitive and language. In addition, through the literature review, it seemed that prenatal exposure to NO 2 might cause adverse impacts on children’s attention, IQ, and different behaviors, but this requires confirmation from further researches. Our study indicated that prenatal exposure to NO 2 seems to be associated with impaired neural development for children, especially for fine psychomotor. However, further studies are needed for determining the effects of prenatal air pollution exposure on attention, IQ, and behavior.

Evoked-potential audiogram variability in a group of wild Yangtze finless porpoises (Neophocaena asiaeorientalis asiaeorientalis) - Zhi-Tao Wang; Jiao Li; Peng-Xiang Duan; Zhi-Gang Mei; Fu-Qiang Niu; Tomonari Akamatsu; Pei-Yu Lei; Lu Zhou; Jing Yuan; Yu-Wei Chen; Alexander Ya Supin; Ding Wang; et al. (Journal of Comparative Physiology A, 2020)

3D-QSAR, HQSAR, molecular docking, and new compound design study of 1,3,6-trisubstituted 1,4-diazepan-7-ones as human KLK7 inhibitors - Le Fu; Yi Chen; Chun-mei Xu; Tao Wu; Hong-mei Guo; Zhi-hua Lin; Rui Wang; Mao Shu (Medicinal Chemistry Research, 2020)

SNX-2112, an Hsp90 inhibitor, suppresses cervical cancer cells proliferation, migration, and invasion by inhibiting the Akt/mTOR signaling pathway - Liang-Shun Fu; Hong-Hong Qiu; Min Liu; Liu-Bing Hu; Yan Wang; Peng-Chao Zhang; Man-Mei Li; Yi-Fei Wang; Zhong Liu (Medicinal Chemistry Research, 2020)

Automatic Striatal ROI Delineation for Semi-quantitative Analysis of 99mTc-TRODAT-1 Brain SPECT Imaging - Bang-Hung Yang; Kang-Ping Lin; Mei-Fen Chen; Jui-Hung Weng; Pan-Fu Kao; Wen-Chen Lin; Ren-Shyan Liu (Journal of Medical and Biological Engineering, 2020)

Epidemiology and HBGA-susceptibility investigation of a G9P[8] rotavirus outbreak in a school in Lechang, China - Lun-Ai Guo; Meng Zhang; Yu-zhen Hou; Haitao Hu; Ling Fang; Ming Tan; Qiong Huang; Hui Li; Li-Mei Sun; Xi Jiang; Wen-Fang Tan; Shixing Tang; et al. (Archives of Virology, 2020)

Correction to: Nucleoporin Nup98 participates in flowering regulation in a CONSTANS-independent mode - Shanshan Jiang; Long Xiao; Penghui Huang; Zhiyuan Cheng; Fulu Chen; Yuchen Miao; Yong-Fu Fu; Qingshan Chen; Xiao-Mei Zhang (Plant Cell Reports, 2020)

Environmental policy, tax, and the target of sustainable development - Jie Yang; Mei-Lan Chen; Chung-Yuan Fu; Xi-Ding Chen (Environmental Science and Pollution Research, 2020)

Elevated Hs-CRP Levels Are Associated with Higher Risk of Intracranial Arterial Stenosis - Bing-Jie Su; Yi Dong; Chen-Chen Tan; Xiao-He Hou; Wei Xu; Fu-Rong Sun; Mei Cui; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Sky islands as foci for divergence of fig trees and their pollinators in southwest China - Jun‐Yin Deng; Rong‐Hua Fu; Stephen G. Compton; Mei Liu; Qin Wang; Chuan Yuan; Lu‐Shui Zhang; Yan Chen (Molecular Ecology, 2020)
The dynamics of populations and their divergence over time have shaped current levels of biodiversity and in the case of the “sky islands” of mountainous southwest (SW) China have resulted in an area of exceptional botanical diversity. Ficus tikoua is a prostrate fig tree subendemic to the area that displays unique intraspecific diversity, producing figs typical of different pollination modes in different parts of its range. By combining climate models, genetic variation in populations of the tree's obligate fig wasp pollinators and distributions of the different plant phenotypes, we examined how this unusual situation may have developed. We identified three genetically distinct groups of a single Ceratosolen pollinator species that have largely parapatric distributions. The complex topography of the region contributed to genetic divergence among the pollinators by facilitating geographical isolation and providing refugia. Migration along elevations in response to climate oscillations further enhanced genetic differentiation of the three pollinator groups. Their distributions loosely correspond to the distributions of the functionally significant morphological differences in the male figs of their host plants, but postglacial expansion of one group has not been matched by spread of its associated plant phenotype, possibly due to a major river barrier. The results highlight how interplay between the complex topography of the “sky island” complex and climate change has shaped intraspecies differentiation and relationships between the plant and its pollinator. Similar processes may explain the exceptional botanical diversity of SW China.

Marking Fish with Fluorochrome Dyes - Hongjian Lü; Mei Fu; Zhixin Zhang; Shengqi Su; Weizhi Yao (Reviews in Fisheries Science & Aquaculture, 2020)

Toxicity and metabolism of 3-bromopyruvate in Caenorhabditis elegans - Qiao-ling Gu; Yan Zhang; Xi-mei Fu; Zhao-lian Lu; Yao Yu; Gen Chen; Rong Ma; Wei Kou; Yong-mei Lan (Journal of Zhejiang University-SCIENCE B, 2020)

Se Regulates the Contractile Ability of Uterine Smooth Musclevia Selenoprotein N, Selenoprotein T, and Selenoprotein Win Mice - Fu-han Wang; Xiao Peng; Yu Chen; Ying Wang; Mei Yang; Meng-yao Guo (Biological Trace Element Research, 2019)

Purification and characterization of an endo-xylanase from Trichoderma sp., with xylobiose as the main product from xylan hydrolysis - Li-Hao Fu; Nan Jiang; Cheng-Xi Li; Xue-Mei Luo; Shuai Zhao; Jia-Xun Feng (World Journal of Microbiology and Biotechnology, 2019)

Breast milk concentration of hydroxychloroquine in Chinese lactating women with connective tissue diseases - Wenxiu Peng; Rongji Liu; Lejia Zhang; Qiang Fu; Dan Mei; Xiaoli Du (European Journal of Clinical Pharmacology, 2019)

Interferon gamma inhibits transmissible gastroenteritis virus infection mediated by an IRF1 signaling pathway - Lingling Shan; Fang Fu; Mei Xue; Xiangdong Zhu; Liang Li; Li Feng; Pinghuang Liu (Archives of Virology, 2019)

Nucleoporin Nup98 participates in flowering regulation in a CONSTANS-independent mode - Shanshan Jiang; Long Xiao; Penghui Huang; Zhiyuan Cheng; Fulu Chen; Yuchen Miao; Yong-Fu Fu; Qingshan Chen; Xiao-Mei Zhang (Plant Cell Reports, 2019)

Evaluation of Coherence Between ECG and PPG Derived Parameters on Heart Rate Variability and Respiration in Healthy Volunteers With/Without Controlled Breathing - Hao-Yu Jan; Mei-Fen Chen; Tieh-Cheng Fu; Wen-Chen Lin; Cheng-Lun Tsai; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2019)

Carbon Monoxide Attenuates High Salt-Induced Hypertension While Reducing Pro-inflammatory Cytokines and Oxidative Stress in the Paraventricular Nucleus - Dong-Dong Zhang; Yan-Feng Liang; Jie Qi; Kai B. Kang; Xiao-Jing Yu; Hong-Li Gao; Kai-Li Liu; Yan-Mei Chen; Xiao-Lian Shi; Guo-Rui Xin; Li-Yan Fu; Yu-Ming Kang; et al. (Cardiovascular Toxicology, 2019)

Gangliosides profiling in serum of breast cancer patient: GM3 as a potential diagnostic biomarker - Qinying Li; Mei Sun; Mingsheng Yu; Qianyun Fu; Hao Jiang; Guangli Yu; Guoyun Li (Glycoconjugate Journal, 2019)

The orphan nuclear receptor NUR77 promotes trophoblast invasion at early pregnancy through paracrine placental growth factor - Xiao-Cui Li; Xiang-Jie Yin; Wei Hong; Jie Liu; Feng Jin; Bei-Ying Wang; Yu-Mei Wang; Fu-Ju Tian (Journal of Molecular Medicine, 2019)

Protective Effects of 1-Methylnicotinamide on Aβ1–42-Induced Cognitive Deficits, Neuroinflammation and Apoptosis in Mice - Lili Fu; Caihong Liu; Liang Chen; Yangge Lv; Guoliang Meng; Mei Hu; Yan Long; Hao Hong; Susu Tang (Journal of Neuroimmune Pharmacology, 2019)

Recent research progress in geochemical properties and restoration of heavy metals in contaminated soil by phytoremediation - Jiang-tao Fu; Dong-mei Yu; Xi Chen; Ying Su; Cai-hong Li; Yong-ping Wei (Journal of Mountain Science, 2019)

Progressive multifocal leukoencephalopathy in a renal transplant patient - Tsu-Chen Lin; Mei-Yi Wu; Hui-Tzung Luh; Shiou-Fu Lin; Chien-Min Lin; Ying-Chi Tseng; Yung-Ching Liu; Mai-Szu Wu (Journal of NeuroVirology, 2019)

In situ Pb-Pb isotopic dating of sulfides from hydrothermal deposits: a case study of the Lala Fe-Cu deposit, SW China - Wei Terry Chen; Mei-Fu Zhou; Xiaochun Li; Jian-Feng Gao; Zhian Bao; Honglin Yuan (Mineralium Deposita, 2019)

Influences of soil moisture and salt content on loess shear strength in the Xining Basin, northeastern Qinghai-Tibet Plateau - Jiang-tao Fu; Xia-song Hu; Xi-lai Li; Dong-mei Yu; Ya-bin Liu; You-Qing Yang; Zhao-xin Qi; Shu-xia Li (Journal of Mountain Science, 2019)

Successful Treatment of Eczema-Like Mucormycosis in a Child by Combination of Intravenous Drip and Percutaneous Injection Amphotericin B - Mei-hua Fu; Jia Liu; Guan-zhao Liang; Cheng-rang Li; Xiao-mei Zhu; Le Wang; Hao Chen; Wen-long Hu; Gui-xia Lv; Wei-da Liu (Mycopathologia, 2019)

Timing and genesis of Cu–(Au) mineralization in the Khetri Copper Belt, northwestern India: constraints from in situ U–Pb ages and Sm–Nd isotopes of monazite-(Ce) - Xiao-Chun Li; Mei-Fu Zhou; A. E. Williams-Jones; Yue-Heng Yang; Jian-Feng Gao (Mineralium Deposita, 2019)

Coupled evolution of Neoproterozoic arc mafic magmatism and mantle wedge in the western margin of the South China Craton - Jun-Hong Zhao; Mei-Fu Zhou; Yuan-Bao Wu; Jian-Ping Zheng; Wei Wang (Contributions to Mineralogy and Petrology, 2019)

Exploration for native parasitoids of Drosophila suzukii in China reveals a diversity of parasitoid species and narrow host range of the dominant parasitoid - Massimo Giorgini; Xin-Geng Wang; Yan Wang; Fu-Shou Chen; Evelyne Hougardy; Hong-Mei Zhang; Zong-Qi Chen; Hong-Yin Chen; Chen-Xi Liu; Pasquale Cascone; Giorgio Formisano; Gislaine A. Carvalho; et al. (Journal of Pest Science, 2019)

A collision fragmentation model for predicting the distal reach of brittle fragmentable rock initiated from a cliff - Gang Luo; Hu Xiewen; Du Yingjin; Fu Jiankang; Mei Xuefeng (Bulletin of Engineering Geology and the Environment, 2019)

Luminescence chronology of the Palaeolithic–Neolithic transition in the Yujiagou site at the Nihewan Basin, northern China - Xue Rui; Yu‐Jie Guo; Jia‐Fu Zhang; Yue Hu; Hui‐Jie Mei; You‐Ping Wang; Fei Xie; Bo Li (Journal of Quaternary Science, 2019)
The relationship between the Palaeolithic–Neolithic cultural transition and environmental changes is important for understanding human history. However, the timing and nature of human behaviour at the transition, and their relationship to local environmental conditions, remain poorly understood. The Yujiagou archaeological site in the Nihewan Basin, northern China, provides valuable chronological and archaeological information about cultural changes in northern China due to its continuous archaeological sequence of cultural layers from the Palaeolithic to Neolithic. In this study, we apply post‐infrared infrared stimulated luminescence (pIRIR) dating on individual feldspar grains to date the Yujiagou deposits. We provide a revised chronology for the archaeological sequence at the site. We combine these results with multi‐proxy climatic indicators to gain insights into palaeoenvironmental changes in the region. The results show that the age of the artefact‐bearing deposits ranges from 13.5 to 9.7 ka. Polished stones and pottery begin to occur in the archaeological layer around 13 ka, corresponding to a transitional period when the local climate changed from cold to warm. This site provides evidence for understanding the process that led to the regional transition from hunter‐gathering to farming.

Cystobasidium keelungensis sp. nov., a novel mycosporine producing carotenogenic yeast isolated from the sea surface microlayer in Taiwan - Chin-Feng Chang; Ching-Fu Lee; Shiu-Mei Liu (Archives of Microbiology, 2019)

A new insecticidal havanensin-type limonoid from the roots of Trichilia sinensis Bentv. - Shou-Bai Liu; Hui-Qin Chen; Gang Feng; Zhi-Kai Guo; Cai-hong Cai; Jun Wang; Wen-Li Mei; Hao-Fu Dai (Natural Product Research, 2018)

Saikosaponin-d inhibits proliferation by up-regulating autophagy via the CaMKKβ–AMPK–mTOR pathway in ADPKD cells - Weiwei Shi; Dechao Xu; Junhui Gu; Cheng Xue; Bo Yang; Lili Fu; Shuwei Song; Dongmei Liu; Wei Zhou; Jiayi Lv; Ke Sun; Meihan Chen; et al. (Molecular and Cellular Biochemistry, 2018)

Analyzing Influencing Factors of Rural Poverty in Typical Poverty Areas of Hainan Province: A Case Study of Lingao County - Jinping Zhang; Feng Zuo; Yanmei Zhou; Mengxiao Zhai; Lin Mei; Yidi Fu; Yeqing Cheng (Chinese Geographical Science, 2018)

Origin of the volcanic-hosted Yamansu Fe deposit, Eastern Tianshan, NW China: constraints from pyrite Re-Os isotopes, stable isotopes, and in situ magnetite trace elements - Xiao-Wen Huang; Mei-Fu Zhou; Georges Beaudoin; Jian-Feng Gao; Liang Qi; Chuan Lyu (Mineralium Deposita, 2018)

High-resolution melting-based TILLING of γ ray-induced mutations in rice - Shan Li; Song-mei Liu; Hao-wei Fu; Jian-zhong Huang; Qing-yao Shu (Journal of Zhejiang University-SCIENCE B, 2018)

Variable hydrological effects of herbs and shrubs in the arid northeastern Qinghai-Tibet Plateau, China - Ya-bin Liu; Ying Zhang; Jiang-tao Fu; Dong-mei Yu; Xia-song Hu; Xi-lai Li; Zhao-xin Qi; Shu-xia Li (Journal of Mountain Science, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Prodigiosin stimulates endoplasmic reticulum stress and induces autophagic cell death in glioblastoma cells - Shu-Yu Cheng; Nan-Fu Chen; Hsiao-Mei Kuo; San-Nan Yang; Chun-Sung Sung; Ping-Jyun Sung; Zhi-Hong Wen; Wu-Fu Chen (Apoptosis, 2018)

Impact of mixed anthropogenic and natural emissions on air quality and eco-environment—the major water-soluble components in aerosols from northwest to offshore isle - Yilun Jiang; Guoshun Zhuang; Qiongzhen Wang; Kan Huang; Congrui Deng; Guangyuan Yu; Chang Xu; Qingyan Fu; Yanfen Lin; Joshua S. Fu; Mei Li; Zhen Zhou (Air Quality, Atmosphere & Health, 2018)

Comparisons of cadmium bioaccumulation potentials and resistance physiology of Microsorum pteropus and Echinodorus grisebachii - Yun-Yun Yan; Jun-Jun Wang; Xin-Yu Lan; Qing-Mei Wang; Fu-Liu Xu (Environmental Science and Pollution Research, 2018)

Identification, characterization and expression analysis of genes involved in steroidal saponin biosynthesis in Dracaena cambodiana - Jia-Hong Zhu; Hui-Liang Li; Dong Guo; Ying Wang; Hao-Fu Dai; Wen-Li Mei; Shi-Qing Peng (Journal of Plant Research, 2018)

Spatiotemporal variability of precipitation during 1961–2014 across the Mongolian Plateau - Fu-ying Qin; Gen-suo Jia; Jie Yang; Yin-tai Na; Mei-ting Hou; Narenmandula (Journal of Mountain Science, 2018)

Automatic 40Ar/39Ar Dating Techniques Using Multicollector ARGUS VI Noble Gas Mass Spectrometer with Self-Made Peripheral Apparatus - Xiu-Juan Bai; Hua-Ning Qiu; Wen-Gui Liu; Lian-Fu Mei (Journal of Earth Science, 2018)

Uranium-lead dating of hydrothermal zircon and monazite from the Sin Quyen Fe-Cu-REE-Au-(U) deposit, northwestern Vietnam - Xiao-Chun Li; Mei-Fu Zhou; Wei Terry Chen; Xin-Fu Zhao; MyDung Tran (Mineralium Deposita, 2018)

Tamoxifen usage correlates with increased risk of Parkinson’s disease in older women with breast cancer: a case–control study in Taiwan - Hsien-Feng Lin; Kuan-Fu Liao; Ching-Mei Chang; Cheng-Li Lin; Shih-Wei Lai (European Journal of Clinical Pharmacology, 2018)

Association of use of selective serotonin reuptake inhibitors with risk of acute pancreatitis: a case-control study in Taiwan - Hsien-Feng Lin; Kuan-Fu Liao; Ching-Mei Chang; Cheng-Li Lin; Shih-Wei Lai (European Journal of Clinical Pharmacology, 2017)

Fiber-type distribution and expression of myosin heavy chain isoforms in newborn heterozygous myostatin-knockout pigs - Xiao-Xu Xing; Mei-Fu Xuan; Long Jin; Qing Guo; Zhao-Bo Luo; Jun-Xia Wang; Qi-Rong Luo; Guang-Lei Zhang; Cheng-Du Cui; Zheng-Yun Cui; Jin-Dan Kang; Xi-Jun Yin (Biotechnology Letters, 2017)

A new wortmannine derivative from a Tripterygium wilfordii endophytic fungus Talaromyces wortmannii LGT-4 - Jing-Yun Sun; Zhong-Duo Yang; Guang-Chao Fu; Yong-Gang Wang; Hong-Yan Xue; Zong-Mei Shu (Natural Product Research, 2017)

Global changes of 5-hydroxymethylcytosine and 5-methylcytosine from normal to tumor tissues are associated with carcinogenesis and prognosis in colorectal cancer - Yi-ping Tian; Ai-fen Lin; Mei-fu Gan; Hao Wang; Dan Yu; Chong Lai; Dan-dan Zhang; Yi-min Zhu; Mao-de Lai (Journal of Zhejiang University-SCIENCE B, 2017)

Can calcein and alizarin complexone be used for double immersion marking of juvenile qingbo Spinibarbus sinensis? - Hongjian Lü; Andrew Chapelsky; Zhixin Zhang; Ruijiao Li; Wanxiu Rao; Mei Fu (Fisheries Science, 2017)

Molecular cloning, characterization, and promoter analysis of the isochorismate synthase (AaICS1) gene from Artemisia annua - Lu-yao Wang; Ying Zhang; Xue-qing Fu; Ting-ting Zhang; Jia-wei Ma; Li-da Zhang; Hong-mei Qian; Ke-xuan Tang; Shan Li; Jing-ya Zhao (Journal of Zhejiang University-SCIENCE B, 2017)

Correlation between proton pump inhibitors and risk of pyogenic liver abscess - Hsien-Feng Lin; Kuan-Fu Liao; Ching-Mei Chang; Cheng-Li Lin; Shih-Wei Lai (European Journal of Clinical Pharmacology, 2017)

The role of solubility on the rejection of trace organics by nanofiltration membrane: exemplified with disinfection by-products - Fan-xin Kong; Xiao-mao Wang; Hong-wei Yang; Jin-fu Chen; Chun-mei Guo; Tong Zhang; Yuefeng F. Xie (Environmental Science and Pollution Research, 2017)

CDK inhibitor SU9516 induces tetraploid blastocyst formation from parthenogenetically activated porcine embryos - Qing Guo; Long Jin; Hai-Ying Zhu; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Guang-Lei Zhang; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Jin-Dan Kang; et al. (Biotechnology Letters, 2017)

Coupled carbon and sulfur isotope behaviors and other geochemical perspectives into marine methane seepage - Lihua Liu; Shaoying Fu; Mei Zhang; Hongxiang Guan; Nengyou Wu (Acta Oceanologica Sinica, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Genome-wide identification and functional analysis of S-RNase involved in the self-incompatibility of citrus - Mei Liang; Wei Yang; Shiying Su; Lili Fu; Hualin Yi; Chuanwu Chen; Xiuxin Deng; Lijun Chai (Molecular Genetics and Genomics, 2017)

Constitutive expression of a plant ferredoxin-like protein (pflp) enhances capacity of photosynthetic carbon assimilation in rice (Oryza sativa) - Hsiang Chang; Hsiang-En Huang; Chin-Fu Cheng; Mei-Hsuan Ho; Mang-Jye Ger (Transgenic Research, 2017)

Effects of salinity on cold tolerance of Malaysian red tilapia - Yan-fu He; Lan-mei Wang; Wen-bin Zhu; Zai-jie Dong; Nian Liu (Aquaculture International, 2017)

Rapamycin Effectively Impedes Melamine-Induced Impairments of Cognition and Synaptic Plasticity in Wistar Rats - Jingxuan Fu; Hui Wang; Jing Gao; Mei Yu; Rubin Wang; Zhuo Yang; Tao Zhang (Molecular Neurobiology, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Improvement of FK506 production by synthetic biology approaches - Li-Feng Fu; Yang Tao; Mei-Ying Jin; Hui Jiang (Biotechnology Letters, 2016)

Identification of novel polymorphic microsatellite loci in the endangered Chinese sucker (Myxocyprinus asiaticus) - NIAN XU; DONG-MEI XU; YAN-FU QUE; FANG SHI; MEI-HUA XIONG; KE SHAO; WEI-TAO LI; BIN ZHU; ZHONG YANG (Journal of Genetics, 2016)

Subinhibitory concentrations of phloretin repress the virulence of Salmonella typhimurium and protect against Salmonella typhimurium infection - Wu Shuai-Cheng; Fu Ben-Dong; Chu Xiu-Ling; Su Jian-Qing; Fu Yun-Xing; Cui Zhen-Qiang; Xu Dao-Xiu; Wu Zong-Mei (Antonie van Leeuwenhoek, 2016)

Transcriptome analysis of sika deer in China - Bo-Yin Jia; Heng-Xing Ba; Gui-Wu Wang; Ying Yang; Xue-Zhe Cui; Ying-Hua Peng; Jun-Jun Zheng; Xiu-Mei Xing; Fu-He Yang (Molecular Genetics and Genomics, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Antidepressant-like effects of standardized gypenosides: involvement of brain-derived neurotrophic factor signaling in hippocampus - Rong-Hao Mu; Xiao-Yan Fang; Shuang-Shuang Wang; Cheng-Fu Li; Shao-Mei Chen; Xue-Mei Chen; Qing Liu; Yu-Cheng Li; Li-Tao Yi (Psychopharmacology, 2016)

PCI-24781 can improve in vitro and in vivo developmental capacity of pig somatic cell nuclear transfer embryos - Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Yu-Chen Zhang; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Xi-Jun Yin; Jin-Dan Kang (Biotechnology Letters, 2016)

Smoking and Serum Lipid Profiles in Schizophrenia - Hui-Mei An; Yun-Long Tan; Shu-ping Tan; Jing Shi; Zhi-Ren Wang; Fu-De Yang; Xu-Feng Huang; Jair C. Soars; Thomas R. Kosten; Xiang-Yang Zhang (Neuroscience Bulletin, 2016)

Long-Acting Phospholipid Gel of Exenatide for Long-Term Therapy of Type II Diabetes - Mei Hu; Yu Zhang; Nanxi Xiang; Ying Zhong; Tao Gong; Zhi-Rong Zhang; Yao Fu (Pharmaceutical Research, 2016)

Current status and historical variations of phthalate ester (PAE) contamination in the sediments from a large Chinese lake (Lake Chaohu) - Lei Kang; Qing-Mei Wang; Qi-Shuang He; Wei He; Wen-Xiu Liu; Xiang-Zhen Kong; Bin Yang; Chen Yang; Yu-Jiao Jiang; Fu-Liu Xu (Environmental Science and Pollution Research, 2016)

Sorghum and Switchgrass as Biofuel Feedstocks on Marginal Lands in Northern China - Hai Mei Fu; Fan Yu Meng; R. L. Molatudi; Bao Gui Zhang (BioEnergy Research, 2016)

Extraction and speciation analysis of roxarsone and its metabolites from soils with different physicochemical properties - Qing-Long Fu; Jian-Zhou He; Hua Gong; Lee Blaney; Dong-Mei Zhou (Journal of Soils and Sediments, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Response of the fine root production, phenology, and turnover rate of six shrub species from a subtropical forest to a soil moisture gradient and shading - Xiaoli Fu; Junlong Wang; Huimin Wang; Xiaoqin Dai; Fengting Yang; Mei Zhao (Plant and Soil, 2016)

PGC-1α regulates the cell cycle through ATP and ROS in CH1 cells - Xu-feng Fu; Kun Yao; Xing Du; Yan Li; Xiu-yu Yang; Min Yu; Mei-zhang Li; Qing-hua Cui (Journal of Zhejiang University-SCIENCE B, 2016)

Assessing flood risk using reservoir flood control rules - Xiang Fu; Yadong Mei; Zhihuai Xiao (Journal of Earth Science, 2016)

Cloning, expression, and characterization of Pseudomonas vesicularis MA103 β-1,3-xylanase in Escherichia coli ClearColi BL21(DE3) - Wen-Sing Liang; Tsuei-Yun Fang; Hong-Ting Lin; Tristan C. Liu; Wen-Jung Lu; Wen-Shyong Tzou; Shye-Jye Tang; Fu-Pang Lin; Shiu-Mei Liu; Chorng-Liang Pan (Fisheries Science, 2015)

Cytological and molecular analysis of Nsa CMS in Brassica napus L. - Jia Liu; Ruiyong Xiang; Weiming Wang; Desheng Mei; Yunchang Li; Annaliese S. Mason; Li Fu; Qiong Hu (Euphytica, 2015)
Nsa cytoplasmic male sterility (CMS) is a novel Brassica napus male sterility system derived from Sinapis arvensis cytoplasm. Nsa CMS results in defective pollen production due to S. arvensis mitochondrial gene failure/incompatibility in the anthers, requiring nuclear genes to restore fertility. From ultramicroscopic observation of anther sections, we concluded that the induction of sterility begins at the pollen (microspore) mother cell stage. Most pollen mother cells do not undergo the first meiotic division and dissociate before the tetrad stage. At the tetrad stage, abortion was observed for all uninucleate pollen. Dysfunction of mitchondrial gene(s) leads to cell vacuolization in the anther tapetum and middle layer cells. Early programmed cell death (PCD) of the tapetum and anther middle layer cells is the main reason for pollen mother cell abortion. Due to this early pollen abortion, the sterility of Nsa CMS is stable and complete. Southern blotting of DNA from the Nsa male-sterile line, its maintainer and restorer lines, as well as the two parental lines ( B. napus cv. Zhongshuang 4 and S. arvensis var. Yeyou 18) involved in the somatic hybridization, suggested that the cytoplasm of the Nsa CMS line was from S. arvensis and that of the restorer line was a rearrangement of both parental lines. Nsa CMS shows great potential for hybrid seed production in rapeseed. Our results provide clues to identify novel male-sterility ( S ) and restorer ( R ) genes as well as elucidate the mechanism underlying interactions between the S and R genes.

The small GTP ase MoYpt 7 is required for membrane fusion in autophagy and pathogenicity of M agnaporthe oryzae - Xiao‐Hong Liu; Si‐Miao Chen; Hui‐Min Gao; Guo‐Ao Ning; Huan‐Bin Shi; Yao Wang; Bo Dong; Yao‐Yao Qi; Dong‐Mei Zhang; Guo‐Dong Lu; Zong‐Hua Wang; Jie Zhou; et al. (Environmental Microbiology, 2015)
Summary R ab GTP ases are required for vesicle–vacuolar fusion during vacuolar biogenesis in fungi. To date, little is known about the biological functions of the R ab small GTP ase components in M agnaporthe oryzae . In this study, we investigated MoYpt 7 of M . oryzae , a homologue of the small R as‐like GTP ase Ypt7 in S accharomyces cerevisiae . Cellular localization assays showed that MoYpt 7 was predominantly localized to vacuolar membranes. Using a targeted gene disruption strategy, a Δ MoYPT7 mutant was generated that exhibited defects in mycelial growth and production of conidia. The conidia of the Δ MoYPT7 mutant were malformed and defective in the formation of appressoria. Consequently, the Δ MoYPT7 mutant failed to cause disease in rice and barley. Furthermore, the Δ MoYPT7 mutant showed impairment in autophagy, breached cell wall integrity, and higher sensitivity to both calcium and heavy metal stress. Transformants constitutively expressing an active MoYPT7 allele ( MoYPT7 ‐ CA , G ln67 L eu) exhibited distinct phenotypes from the Δ MoYPT7 mutant. Expression of MoYPT7 ‐ CA in MoYpt 7 reduced pathogenicity and produced more appressoria‐forming single‐septum conidia. These results indicate that MoYPT7 is required for fungal morphogenesis, vacuole fusion, autophagy, stress resistance and pathogenicity in M . oryzae .

Inhibition of hyperactivity and impulsivity by carbonic anhydrase inhibitors in spontaneously hypertensive rats, an animal model of ADHD - Ming-Tao Yang; Dai-Hua Lu; Jui-Ching Chen; Wen-Mei Fu (Psychopharmacology, 2015)

In situ Sr isotope analysis of apatite by LA-MC-ICPMS: constraints on the evolution of ore fluids of the Yinachang Fe-Cu-REE deposit, Southwest China - Xin-Fu Zhao; Mei-Fu Zhou; Jian-Feng Gao; Xiao-Chun Li; Jian-Wei Li (Mineralium Deposita, 2015)

Geochemistry of magnetite from Proterozoic Fe-Cu deposits in the Kangdian metallogenic province, SW China - Wei Terry Chen; Mei-Fu Zhou; Jian-Feng Gao; Ruizhong Hu (Mineralium Deposita, 2015)

Behavior, metabolism and swimming physiology in juvenile Spinibarbus sinensis exposed to PFOS under different temperatures - Ji-Gang Xia; Li-Juan Nie; Xia-Mei Mi; Wei-Zhen Wang; Yi-Jie Ma; Zhen-Dong Cao; Shi-Jian Fu (Fish Physiology and Biochemistry, 2015)

Spatial and vertical distribution of bacterial community in the northern South China Sea - Fu-Lin Sun; You-Shao Wang; Mei-Lin Wu; Cui-Ci Sun; Hao Cheng (Ecotoxicology, 2015)

Longitudinal changes of dopamine transporters in heroin users during abstinence - Shasha Xu; Ying Liu; Yu Li; Yangping Deng; Yiyun Huang; Jie Yuan; Rongbin Lv; Yuankai Wang; Guangming Zhang; Zhirui Guo; Mei Han; Xingdang Liu; et al. (Psychopharmacology, 2015)

Effects of Fluoride on DNA Damage and Caspase-Mediated Apoptosis in the Liver of Rats - Guo Hua Song; Fu Bing Huang; Ji Ping Gao; Mao Lin Liu; Wen Biao Pang; Wei bin Li; Xiao Yan Yan; Mei Jun Huo; Xia Yang (Biological Trace Element Research, 2015)

Experimental evaluation of calcein and alizarin red S for immersion marking grass carp Ctenopharyngodon idellus - Hongjian Lü; Hongjun Chen; Mei Fu; Xiwen Peng; Dan Xi; Zhixin Zhang (Fisheries Science, 2015)

Development of genic cleavage markers in association with seed glucosinolate content in canola - Ying Fu; Kun Lu; Lunwen Qian; Jiaqin Mei; Dayong Wei; Xuhui Peng; Xinfu Xu; Jiana Li; Martin Frauen; Felix Dreyer; Rod J. Snowdon; Wei Qian (Theoretical and Applied Genetics, 2015)

Protective Effects of Sesaminol on BEAS-2B Cells Impaired by Cigarette Smoke Extract - Ping Dong; Xiao Fu; Xiang Wang; Wen-mei Wang; Wen-ming Cao; Wei-yun Zhang (Cell Biochemistry and Biophysics, 2015)

Genetic analysis of litchi (Litchi chinensis Sonn.) in southern China by improved random amplified polymorphic DNA (RAPD) and inter-simple sequence repeat (ISSR) - Yan Long; Jingliang Cheng; Zhiqiang Mei; Ling Zhao; Chunli Wei; Shelly Fu; Md. Asaduzzaman Khan; Junjiang Fu (Molecular Biology Reports, 2015)

The Bifunctional Liposomes Constructed by Poly(2-ethyl-oxazoline)-cholesteryl Methyl Carbonate: an Effectual Approach to Enhance Liposomal Circulation Time, pH-Sensitivity and Endosomal Escape - Huan Xu; Wei Zhang; Yan Li; Fei F. Ye; Peng P. Yin; Xiu Yu; Mei N. Hu; Yuan S. Fu; Che Wang; De J. Shang (Pharmaceutical Research, 2014)

Modified high-intensity interval training increases peak cardiac power output in patients with heart failure - Shu-Chun Huang; Mei-Kuen Wong; Pyng-Jing Lin; Feng-Chun Tsai; Tieh-cheng Fu; Ming-Shien Wen; Chi-Tai Kuo; Jong-Shyan Wang (European Journal of Applied Physiology, 2014)

Two new eunicellin-based diterpenoids from the South China Sea gorgonian Muricella sibogae Nutting - Yuan-Ming Zhou; Min Chen; Xiu-Mei Fu; Yu-Chun Fang; Chang-Yun Wang (Natural Product Research, 2014)

Interaction network analysis revealed biomarkers in myocardial infarction - Tong Zhang; Li-Li Zhao; Zhuo-Ran Zhang; Pei-De Fu; Zhen-Dong Su; Li-Chun Qi; Xue-Qi Li; Yu-Mei Dong (Molecular Biology Reports, 2014)

Ages and compositions of primary and secondary allanite from the Lala Fe–Cu deposit, SW China: implications for multiple episodes of hydrothermal events - Wei Terry Chen; Mei-Fu Zhou (Contributions to Mineralogy and Petrology, 2014)

Nucleoside derivatives from the marine-derived fungus Aspergillus versicolor - Min Chen; Xiu-Mei Fu; Chui-Jian Kong; Chang-Yun Wang (Natural Product Research, 2014)

Antithrombotic Peptides from Scolopendra subspinipes mutilans Hydrolysates - Yi Kong; Shuai Li; Yu Shao; Zhi-long He; Mei-mei Chen; Xin Ming; Ji-fu Wei (International Journal of Peptide Research and Therapeutics, 2014)

Mapping of QTL associated with waterlogging tolerance and drought resistance during the seedling stage in oilseed rape (Brassica napus) - Zhen Li; Shufang Mei; Zhong Mei; Xianglei Liu; Tingdong Fu; Guangsheng Zhou; Jinxing Tu (Euphytica, 2014)

A dwarfing mutant caused by deactivation function of alpha subunit of the heterotrimeric G-protein in rice - De-wei Yang; Xiang-hua Zheng; Chao-ping Cheng; Wen-da Wang; Deng-hui Xing; Li-bin Lu; Chen-de Liu; Ning Ye; Mei-juan Zeng; Xin-fu Ye (Euphytica, 2014)

Heavy metals levels in fish from aquaculture farms and risk assessment in Lhasa, Tibetan Autonomous Region of China - Dongsheng Jiang; Zhenzhen Hu; Feng Liu; Rongfei Zhang; Bu Duo; Jianjie Fu; Yibin Cui; Mei Li (Ecotoxicology, 2014)

Tumor-Suppressing Effects of miR451 in Human Osteosarcoma - Haidong Xu; Qiang Mei; Luxia Shi; Jiajia Lu; Jianning Zhao; Qiang Fu (Cell Biochemistry and Biophysics, 2014)

Clodronate liposomes reduce excessive scar formation in a mouse model of burn injury by reducing collagen deposition and TGF-β1 expression - Shao-wei Lu; Xing-mei Zhang; Hong-min Luo; Yu-cai Fu; Ming-yan Xu; Shi-jie Tang (Molecular Biology Reports, 2014)

Geochronology and geochemistry of the Late Triassic Longtan pluton in South China: termination of the crustal melting and Indosinian orogenesis - Liang Qiu; Dan-Ping Yan; Mei-Fu Zhou; Nicholas T. Arndt; Shuang-Li Tang; Liang Qi (International Journal of Earth Sciences, 2014)

Fluid inclusion and H–O–C isotope geochemistry of the Yaochong porphyry Mo deposit in Dabie Shan, China: a case study of porphyry systems in continental collision orogens - Pin Wang; Yan-Jing Chen; Bin Fu; Yong-Fei Yang; Mei Mi; Zhong-Lie Li (International Journal of Earth Sciences, 2014)

Geochemical and geochronological constraints on Late Jurassic volcanic rocks at Tuen Mun, Hong Kong, with implications for the Palaeo-Pacific subduction - Yan Hei Martin Li; Mei-Fu Zhou; Kuen Wai Lai; Lung Sang Chan; Wei Terry Chen (International Geology Review, 2014)

Primordial follicle assembly was regulated by notch signaling pathway in the mice - Chun-Lei Chen; Xia-Fei Fu; Lin-Qing Wang; Jun-Jie Wang; Hua-Gang Ma; Shun-Feng Cheng; Zhu-Mei Hou; Jin-Mei Ma; Guo-Bo Quan; Wei Shen; Lan Li (Molecular Biology Reports, 2014)

Re–Os isotope and platinum-group element geochemistry of the Pobei Ni–Cu sulfide-bearing mafic–ultramafic complex in the northeastern part of the Tarim Craton - Sheng-Hong Yang; Mei-Fu Zhou; Peter C. Lightfoot; Ji-Feng Xu; Christina Yan Wang; Chang-Yi Jiang; Wen-Jun Qu (Mineralium Deposita, 2014)

Socio-demographic and clinical characteristics of heavy and non-heavy smokers among schizophrenia inpatients in a Chinese Han population - Xiang Yang Zhang; Da Chun Chen; Yun Long Tan; Mei Hong Xiu; Jingyi Cui; Li Hui; Fu De Yang; Thomas R Kosten (Psychopharmacology, 2014)

MicroRNA Expression Aberration in Chinese Patients with Relapsing Remitting Multiple Sclerosis - Dan Yang; Wei-Zhi Wang; Xue-Mei Zhang; Hui Yue; Bing Li; Lin Lin; Jin Fu (Journal of Molecular Neuroscience, 2014)

Organochlorine pesticides in the dust fall around Lake Chaohu, the fifth largest lake in China - Hui-Ling Ouyang; Qing-Mei Wang; Wei He; Ning Qin; Xiang-Zhen Kong; Wen-Xiu Liu; Qi-Shuang He; Yu-Jiao Jiang; Chen Yang; Bin Yang; Fu-Liu Xu (Environmental Monitoring and Assessment, 2014)

The phytochrome gene family in soybean and a dominant negative effect of a soybean PHYA transgene on endogenous Arabidopsis PHYA - Fa-Qiang Wu; Cheng-Ming Fan; Xiao-Mei Zhang; Yong-Fu Fu (Plant Cell Reports, 2013)

Molecular characterization and expression analysis of a KIFC1-like kinesin gene in the testis of Eumeces chinensis - Jian-Rao Hu; Mei Liu; Da-Hui Wang; Yan-Jun Hu; Fu-Qing Tan; Wan-Xi Yang (Molecular Biology Reports, 2013)

Re–Os isotopic ages of pyrite and chemical composition of magnetite from the Cihai magmatic–hydrothermal Fe deposit, NW China - Xiao-Wen Huang; Mei-Fu Zhou; Liang Qi; Jian-Feng Gao; Yu-Wang Wang (Mineralium Deposita, 2013)

Genetic variation in alkaloid accumulation in leaves of Nicotiana - Bo Sun; Fen Zhang; Guo-jun Zhou; Guo-hai Chu; Fang-fang Huang; Qiao-mei Wang; Li-feng Jin; Fu-cheng Lin; Jun Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Identifying and characterizing Yarrowia keelungensis sp. nov., an oil-degrading yeast isolated from the sea surface microlayer - Chin-Feng Chang; Chih-Chen Chen; Ching-Fu Lee; Shiu-Mei Liu (Antonie van Leeuwenhoek, 2013)

New 18-oxygenated polyhydroxy steroid from a South China Sea soft coral Sarcophyton sp. - Ling-Ling Sun; Xiu-Mei Fu; Xiu-Bao Li; Qian Xing; Chang-Yun Wang (Natural Product Research, 2013)

Constraints from zircon U–Pb ages, O and Hf isotopic compositions on the origin of Neoproterozoic peraluminous granitoids from the Jiangnan Fold Belt, South China - Jun-Hong Zhao; Mei-Fu Zhou; Jian-Ping Zheng (Contributions to Mineralogy and Petrology, 2013)

Local neuronal circuits that may shape the discharge patterns of inferior collicular neurons - Zi-Ying Fu; Hui-Xian Mei; Liang Cheng; Jing Bai; Jia Tang; Philip Hung-Sun Jen; Qi-Cai Chen (Neuroscience Bulletin, 2013)

Genetic characterization and authentication of Lonicera japonica Thunb. by using improved RAPD analysis - Junjiang Fu; Luquan Yang; Md. Asaduzzaman Khan; Zhiqiang Mei (Molecular Biology Reports, 2013)

Characterization of Phoma adonidicola causing a spot blight on Adonis palaestina - Yan Li; Chunsheng Zheng; Zhihui Zhao; Guozhong Lu; Xuechi Fu; Ruhong Mei; Jinqin Li; Qi Wang (European Journal of Plant Pathology, 2013)

Distribution of platinum-group elements in magmatic and altered ores in the Jinchuan intrusion, China: an example of selenium remobilization by postmagmatic fluids - Hazel M. Prichard; Robert D. Knight; Peter C. Fisher; Iain McDonald; Mei-Fu Zhou; Christina Y. Wang (Mineralium Deposita, 2013)

New textural and mineralogical constraints on the origin of the Hongge Fe-Ti-V oxide deposit, SW China - Christina Yan Wang; Mei-Fu Zhou (Mineralium Deposita, 2013)

Geology, mineralization, and geochronology of the Qianhe gold deposit, Xiong’ershan area, southern North China Craton - Ke-Fei Tang; Jian-Wei Li; David Selby; Mei-Fu Zhou; Shi-Jian Bi; Xiao-Dong Deng (Mineralium Deposita, 2013)

Overexpression of TFAM Protects 3T3-L1 Adipocytes from NYGGF4 (PID1) Overexpression-Induced Insulin Resistance and Mitochondrial Dysfunction - Chun-Mei Shi; Guang-Feng Xu; Lei Yang; Zi-Yi Fu; Ling Chen; Hai-Long Fu; Ya-Hui Shen; Lu Zhu; Chen-Bo Ji; Xi-Rong Guo (Cell Biochemistry and Biophysics, 2013)

Differentiation of nelsonitic magmas in the formation of the ~1.74 Ga Damiao Fe–Ti–P ore deposit, North China - Wei Terry Chen; Mei-Fu Zhou; Tai-Ping Zhao (Contributions to Mineralogy and Petrology, 2013)

Intergeneric hybrid between Chrysanthemum × morifolium and Artemisia japonica achieved via embryo rescue shows salt tolerance - Wen-ying Zhu; Jia-fu Jiang; Su-mei Chen; Liang Wang; Li-li Xu; Hai-bin Wang; Pei-ling Li; Zhi-yong Guan; Fa-di Chen (Euphytica, 2013)

Water–gas exchange of organochlorine pesticides at Lake Chaohu, a large Chinese lake - Hui-Ling Ouyang; Wei He; Ning Qin; Xiang-Zhen Kong; Wen-Xiu Liu; Qi-Shuang He; Chen Yang; Yu-Jiao Jiang; Qing-Mei Wang; Bin Yang; Fu-Liu Xu (Environmental Science and Pollution Research, 2013)

Successful establishment and evaluation of a new animal model for studying the hepatitis B virus YVDD mutant - Yan-Xiu Ma; Zhi-Wei Song; Xu Teng; Li-Juan Fu; Mei-Li Hao; Si-Jia Chen; Wei-Zhen Xu; Hong-Xi Gu (Archives of Virology, 2013)

Ventral medial prefrontal functional connectivity and emotion regulation in chronic schizophrenia: A pilot study - Feng-Mei Fan; Shu-Ping Tan; Fu-De Yang; Yun-Long Tan; Yan-Li Zhao; Nan Chen; Bin-Bin Li; Chong-Sheng Song; Yun-Hui Wang; Zhen Jin; Dong-Feng Zhou; Michael P. Milham; et al. (Neuroscience Bulletin, 2013)

Fluid evolution of the Jiawula Ag–Pb–Zn deposit, Inner Mongolia: mineralogical, fluid inclusion, and stable isotopic evidence - De-Gao Zhai; Jia-Jun Liu; Jian-Ping Wang; Mei-Juan Yao; Sheng-Hua Wu; Chao Fu; Zhen-Jiang Liu; Shou-Guang Wang; Yu-Xi Li (International Geology Review, 2013)

Late Paleoproterozoic sedimentary rock-hosted stratiform copper deposits in South China: their possible link to the supercontinent cycle - Xin-Fu Zhao; Mei-Fu Zhou; Jian-Wei Li; Liang Qi (Mineralium Deposita, 2013)

Endothelial progenitor cells: the promise of cell-based therapies for acute lung injury - Mei Mao; Xilin Xu; Yong Zhang; Bo Zhang; Zu-hong Fu (Inflammation Research, 2013)

Measuring δ 13 C values of atmospheric acetaldehyde via sodium bisulfite adsorption and cysteamine derivatisation - Songjun Guo; Mei Chen; Sheng Wen; Guoying Sheng; Jiamo Fu (Isotopes in Environmental and Health Studies, 2012)

Isolation of marine bacteria with antimicrobial activities from cultured and field-collected soft corals - Yu-Hsin Chen; Jimmy Kuo; Ping-Jung Sung; Yu-Chia Chang; Mei-Chin Lu; Tit-Yee Wong; Jong-Kang Liu; Ching-Feng Weng; Wen-Hung Twan; Fu-Wen Kuo (World Journal of Microbiology and Biotechnology, 2012)

Tetrodotoxin attenuates isoproterenol-induced hypertrophy in H9c2 rat cardiac myocytes - Ming-Zi Chen; Qing-Ting Bu; Shu-Chao Pang; Feng-Lan Li; Mei-Na Sun; Er-Fu Chu; Hui Li (Molecular and Cellular Biochemistry, 2012)

A novel lignan glycoside with antioxidant activity from Tinospora sagittata var. yunnanensis - Xiang-Zhong Huang; Chun-Mei Cheng; Yun Dai; Guang-Miao Fu; Jun-Ming Guo; Hui Liang; Chao Wang (Natural Product Research, 2012)

Erratum to: Validation of reference genes for real-time quantitative PCR normalization in soybean developmental and germinating seeds - Qing Li; Cheng-Ming Fan; Xiao-Mei Zhang; Yong-Fu Fu (Plant Cell Reports, 2012)

Validation of reference genes for real-time quantitative PCR normalization in soybean developmental and germinating seeds - Qing Li; Cheng-Ming Fan; Xiao-Mei Zhang; Yong-Fu Fu (Plant Cell Reports, 2012)

Heterogeneous Os isotope compositions in the Kalatongke sulfide deposit, NW China: the role of crustal contamination - Jian-Feng Gao; Mei-Fu Zhou; Peter C. Lightfoot; Wenjun Qu (Mineralium Deposita, 2012)

Structural determination of two new triterpenoid saponins acylated with monoterpenic acid from Gymnocladus chinensis Baill. - Wen Qi; Dan Yuan; Lian-Mei Yang; Ke-Hui Xie; Tian-Zhi Cai; Rong Yang; Hong-Zheng Fu (Natural Product Research, 2012)

Multiple Mesozoic mineralization events in South China—an introduction to the thematic issue - Rui-Zhong Hu; Mei-Fu Zhou (Mineralium Deposita, 2012)

Spatial variation of bacterial community structure of the Northern South China Sea in relation to water chemistry - Juan Ling; Jun-De Dong; You-Shao Wang; Yan-Ying Zhang; Chao Deng; Li Lin; Mei-Lin Wu; Fu-Lin Sun (Ecotoxicology, 2012)

Differentiation, crustal contamination and emplacement of magmas in the formation of the Nantianwan mafic intrusion of the ~260 Ma Emeishan large igneous province, SW China - Christina Yan Wang; Mei-Fu Zhou; Yali Sun; Nicholas T. Arndt (Contributions to Mineralogy and Petrology, 2012)

Low BDNF is associated with cognitive impairment in chronic patients with schizophrenia - Xiang Yang Zhang; Jun Liang; Da Chun Chen; Mei Hong Xiu; Fu De Yang; Therese A. Kosten; Thomas R. Kosten (Psychopharmacology, 2012)

Celecoxib inhibits growth of human autosomal dominant polycystic kidney cyst-lining epithelial cells through the VEGF/Raf/MAPK/ERK signaling pathway - Tao Xu; Nian-Song Wang; Li-Li Fu; Chao-Yang Ye; Sheng-Qiang Yu; Chang-Lin Mei (Molecular Biology Reports, 2012)

Analysis of 2,297 expressed sequence tags (ESTs) from a cDNA library of flax (Linum ustitatissimum L.) bark tissue - Song-Hua Long; Xin Deng; Yu-Fu Wang; Xiang Li; Rui-Qing Qiao; Cai-Sheng Qiu; Yuan Guo; Dong-Mei Hao; Wan-Qi Jia; Xin-Bo Chen (Molecular Biology Reports, 2012)

Quantifying the Effects of Conservation Practices on Soil, Water, and Nutrients in the Loess Mesa Ravine Region of the Loess Plateau, China - Xiang-Zhou Xu; Mei-Juan Li; Bin Liu; Shang-Fu Kuang; Shi-Guo Xu (Environmental Management, 2012)

Heterogeneous mantle source and magma differentiation of quaternary arc-like volcanic rocks from Tengchong, SE margin of the Tibetan Plateau - Mei-Fu Zhou; Paul T. Robinson; Christina Yan Wang; Jun-Hong Zhao; Dan-Ping Yan; Jian-Feng Gao; John Malpas (Contributions to Mineralogy and Petrology, 2012)

Constraining the mid-crustal channel flow beneath the Tibetan Plateau: data from the Nielaxiongbo gneiss dome, SE Tibet - Dan-Ping Yan; Mei-Fu Zhou; Paul T. Robinson; Djordje Grujic; John Malpas; Allen Kennedy; Peter H. Reynolds (International Geology Review, 2012)

Molecular characterization of a KIF3A-like kinesin gene in the testis of the Chinese fire-bellied newt Cynops orientalis - Jian-Rao Hu; Na Xu; Fu-Qing Tan; Da-Hui Wang; Mei Liu; Wan-Xi Yang (Molecular Biology Reports, 2012)

A spatial aggregation index for effective fallow decision in paddy irrigation demand planning - Ming-Daw Su; Mei-Chun Lin; Chun-Hung Lin; Shih-Fu Wang; Tzai-Hung Wen; Hsin-I Hsieh (Paddy and Water Environment, 2012)

Molecular cloning and functional analysis of one ZEITLUPE homolog GmZTL3 in soybean - Zheng-Gang Xue; Xiao-Mei Zhang; Chen-Fang Lei; Xin-Jian Chen; Yong-Fu Fu (Molecular Biology Reports, 2012)

Effect of dirhamnolipid on the removal of phenol catalyzed by laccase in aqueous solution - Zhi-Feng Liu; Guang-Ming Zeng; Hua Zhong; Xing-Zhong Yuan; Hai-Yan Fu; Mei-Fang Zhou; Xiao-Ling Ma; Hui Li; Jian-Bing Li (World Journal of Microbiology and Biotechnology, 2012)

Gold distribution in As-deficient pyrite and telluride mineralogy of the Yangzhaiyu gold deposit, Xiaoqinling district, southern North China craton - Shi-Jian Bi; Jian-Wei Li; Mei-Fu Zhou; Zhan-Ke Li (Mineralium Deposita, 2011)

Potent inhibition of protein tyrosine phosphatases by copper complexes with multi-benzimidazole derivatives - Ying Li; Liping Lu; Miaoli Zhu; Qingming Wang; Caixia Yuan; Shu Xing; Xueqi Fu; Yuhua Mei (BioMetals, 2011)

Fe–Cu deposits in the Kangdian region, SW China: a Proterozoic IOCG (iron-oxide–copper–gold) metallogenic province - Xin-Fu Zhao; Mei-Fu Zhou (Mineralium Deposita, 2011)

Acetylcholinesterase inhibitors from Corydalis yanhusuo - Hai-Tao Xiao; Jiao Peng; Yan Liang; Jie Yang; Xue Bai; Xiao-Yan Hao; Fu-Mei Yang; Qian-Yun Sun (Natural Product Research, 2011)

A double-blind, placebo-controlled study of traditional Chinese medicine sarsasapogenin added to risperidone in patients with negative symptoms dominated schizophrenia - Shi-Fu Xiao; Hai-Bo Xue; Xia Li; Chao Chen; Guan-Jun Li; Cheng-Mei Yuan; Ming-Yuan Zhang (Neuroscience Bulletin, 2011)

Spatial heterogeneity of bacterial community structure in the sediments of the Pearl River estuary - Fu-Lin Sun; You-Shao Wang; Mei-Lin Wu; Yu-Tu Wang; Qian P. Li (Biologia, 2011)

QTL mapping of sheath blight resistance in a deep-water rice cultivar - Dong Fu; Liang Chen; Guohui Yu; Yi Liu; Qiaojun Lou; Hanwei Mei; Liang Xiong; Mingshou Li; Xiaoyan Xu; Lijun Luo (Euphytica, 2011)

Characterization of a salt-tolerant xylanase from Thermoanaerobacterium saccharolyticum NTOU1 - Kuo-Sheng Hung; Shiu-Mei Liu; Tsuei-Yun Fang; Wen-Shyong Tzou; Fu-Pang Lin; Kuang-Hui Sun; Shye-Jye Tang (Biotechnology Letters, 2011)

Induction of lactadherin mediates the apoptosis of endothelial cells in response to advanced glycation end products and protective effects of grape seed procyanidin B2 and resveratrol - Bao-ying Li; Xiao-li Li; Qian Cai; Hai-qing Gao; Mei Cheng; Jian-hua Zhang; Jun-fu Wang; Fei Yu; Rui-hai Zhou (Apoptosis, 2011)

Combination of Hyaluronic Acid Hydrogel Scaffold and PLGA Microspheres for Supporting Survival of Neural Stem Cells - Ying Wang; Yue Teng Wei; Zhao Hui Zu; Rong Kai Ju; Mu Yao Guo; Xiu Mei Wang; Qun Yuan Xu; Fu Zhai Cui (Pharmaceutical Research, 2011)

Identification and expression of caspase-1 gene under heat stress in insecticide-susceptible and -resistant Plutella xylostella (Lepidoptera: Plutellidae) - Hua Mei Zhuang; Kuan Fu Wang; Tadashi Miyata; Zu Jian Wu; Gang Wu; Lian Hui Xie (Molecular Biology Reports, 2011)

Induction of Human Bone Marrow Mesenchymal Stem Cells Differentiation into Neural-Like Cells Using Cerebrospinal Fluid - Ying Ye; Yin-Ming Zeng; Mei-Rong Wan; Xian-Fu Lu (Cell Biochemistry and Biophysics, 2011)

Generation of transgenic watermelon resistant to Zucchini yellow mosaic virus and Papaya ringspot virus type W - Tsong-Ann Yu; Chu-Hui Chiang; Hui-Wen Wu; Chin-Mei Li; Ching-Fu Yang; Jun-Han Chen; Yu-Wen Chen; Shyi-Dong Yeh (Plant Cell Reports, 2011)

Chalcophile element geochemistry and petrogenesis of high-Ti and low-Ti magmas in the Permian Emeishan large igneous province, SW China - Christina Yan Wang; Mei-Fu Zhou; Liang Qi (Contributions to Mineralogy and Petrology, 2011)

Carbon and nitrogen storage in plant and soil as related to nitrogen and water amendment in a temperate steppe of northern China - Fu-Mei Lü; Xiao-Tao Lü; Wei Liu; Xu Han; Guang-Ming Zhang; De-Liang Kong; Xing-Guo Han (Biology and Fertility of Soils, 2011)

Quantitative trait loci analysis for rice seed vigor during the germination stage - Zhou-fei Wang; Jian-fei Wang; Yong-mei Bao; Fu-hua Wang; Hong-sheng Zhang (Journal of Zhejiang University-SCIENCE B, 2010)

Nicotine dependence and serum BDNF levels in male patients with schizophrenia - Xiang Yang Zhang; Mei Hong Xiu; Da Chun Chen; Fu De Yang; Gui Ying Wu; Lin Lu; Therese A. Kosten; Thomas R. Kosten (Psychopharmacology, 2010)

Spatio-Temporal Variability of Soil Respiration of Forest Ecosystems in China: Influencing Factors and Evaluation Model - Ze-Mei Zheng; Gui-Rui Yu; Xiao-Min Sun; Sheng-Gong Li; Yue-Si Wang; Ying-Hong Wang; Yu-Ling Fu; Qiu-Feng Wang (Environmental Management, 2010)

A spontaneous high expression of heat shock cognate 70 (HSC 70) in zebrafish Danio rerio larvae arising from tissue-specific translation of preexisting mRNA - Lung-Yin Hsu; Fu-Lung Yeh; Tun-Yuan Cheng; You-Hsin Chang; Shiu-Mei Liu; Todd Hsu (Fisheries Science, 2010)

Rational design for over-production of desirable microbial metabolites by precision engineering - Hong Gao; Xianlong Zhou; Zhongxuan Gou; Ying Zhuo; Chengzhang Fu; Mei Liu; Fuhang Song; Elizabeth Ashforth; Lixin Zhang (Antonie van Leeuwenhoek, 2010)

A new cytotoxic iridoid from Callicarpa nudiflora - Wen-Li Mei; Zhuang Han; Hai-Bin Cui; You-Xing Zhao; Yuan-Yuan Deng; Hao-Fu Dai (Natural Product Research, 2010)

The efficacy of FMD vaccine reduced non-structural proteins with a mAb against 3B protein - Dong Li; Zai-Xin Liu; Pu Sun; Yong-Liang Li; Zeng-Jun Lu; Mei-Na Tian; Ying-Li Chen; Bao-Xia Xie; Hui-Fang Bao; Yuan-Fang Fu; Yi-Mei Cao; Ping-Hua Li; et al. (Veterinary Research Communications, 2010)

Fluorescent Property of the Gd3+-Doped Terbium Complexes and Crystal Structure of [Tb(TPTZ)(H2O)6]Cl3·3H2O - Yan-Fang Zhao; Yong-Liang Zhao; Feng Bai; Xiao-yan Wei; Yong-sheng Zhou; Mei-na Shan; Huan-huan Li; Rui-jun Ma; Xiao-tao Fu; Yan Du (Journal of Fluorescence, 2010)

Arsenic-Induced QT Dispersion is Associated with Atherosclerotic Diseases and Predicts Long-Term Cardiovascular Mortality in Subjects with Previous Exposure to Arsenic: A 17-Year Follow-Up Study - Chih-Hao Wang; Chi-Ling Chen; Chuhsing Kate Hsiao; Fu-Tien Chiang; Ling-I Hsu; Hung-Yi Chiou; Yu-Mei Hsueh; Meei-Maan Wu; Chien-Jen Chen (Cardiovascular Toxicology, 2010)

Enrichment of PGE through interaction of evolved boninitic magmas with early formed cumulates in a gabbro–breccia zone of the Mesoarchean Nuasahi massif (eastern India) - Sisir K. Mondal; Mei-Fu Zhou (Mineralium Deposita, 2010)

Magnesium sulfate enhances exercise performance and manipulates dynamic changes in peripheral glucose utilization - Shiu-Min Cheng; Lin-Lan Yang; Sy-Huah Chen; Mei-Hsiang Hsu; I-Ju Chen; Fu-Chou Cheng (European Journal of Applied Physiology, 2010)

Candida neustonensis sp. nov., a novel ascomycetous yeast isolated from the sea surface microlayer in Taiwan - Chin-Feng Chang; Ching-Fu Lee; Shiu-Mei Liu (Antonie van Leeuwenhoek, 2010)

Prostasin inhibits cell invasion in human choriocarcinomal JEG-3 cells - Xiao-jie Ma; Ya-yuan Fu; Yu-xia Li; Li-mei Chen; Karl Chai; Yan-ling Wang (Histochemistry and Cell Biology, 2009)

Combined Effects of Repeated Administration of 2,3,7,8-Tetrachlorodibenzo-p-dioxin and Polychlorinated Biphenyls on Kidneys of Male Rats - Chun-Feng Lu; Yi-Mei Wang; Shuang-Qing Peng; Li-Bo Zou; De-Hong Tan; Gang Liu; Ze Fu; Qiao-Xu Wang; Jing Zhao (Archives of Environmental Contamination and Toxicology, 2009)

Infection and replication of avian influenza H5N1 virus in an infected human - Jing-Jiao Zhou; Dan-Yun Fang; Jie Fu; Jiang Tian; Jun-Mei Zhou; Hui-Jun Yan; Yu Liang; Li-Fang Jiang (Virus Genes, 2009)

The Avoidance Responses of Daphnia magna to the Exposure of Organophosphorus Pesticides in an On-Line Biomonitoring System - Zong-Ming Ren; Zhi-Liang Li; Jin-Miao Zha; Kai-feng Rao; Mei Ma; Zijian Wang; Rong-Shu Fu (Environmental Modeling & Assessment, 2009)

Quantification of silkworm coactivator of MBF1 mRNA by SYBR Green I real-time RT-PCR reveals tissue- and stage-specific transcription levels - Guang-li Li; Bhaskar Roy; Xing-hua Li; Wan-fu Yue; Xiao-feng Wu; Jian-mei Liu; Chuan-xi Zhang; Yun-gen Miao (Molecular Biology Reports, 2009)

Late Mesozoic magmatism from the Daye region, eastern China: U–Pb ages, petrogenesis, and geodynamic implications - Jian-Wei Li; Xin-Fu Zhao; Mei-Fu Zhou; Chang-Qian Ma; Zorano Sérgio de Souza; Paulo Vasconcelos (Contributions to Mineralogy and Petrology, 2009)

Behavioral Responses of Daphnia Magna to Stresses of Chemicals with Different Toxic Characteristics - Zongming Ren; Zhiliang Li; Mei Ma; Zijian Wang; Rongshu Fu (Bulletin of Environmental Contamination and Toxicology, 2009)

High-level expression of orange fluorescent protein in the silkworm larvae by the Bac-to-Bac system - Jian-mei Liu; Wan Chi Cheong David; Denis Tsz-Ming Ip; Xing-hua Li; Guang-li Li; Xiao-feng Wu; Wan-fu Yue; Chuan-xi Zhang; Yun-gen Miao (Molecular Biology Reports, 2009)

Silkworm powder containing manganese superoxide dismutase regulated the immunity and inhibited the growth of Hepatoma 22 cell in mice - Wan-Fu Yue; Wen Deng; Xing-Hua Li; Bhaskar Roy; Guang-Li Li; Jian-Mei Liu; Xiao-Feng Wu; Hong-Xiang Sun; Min-Li Yao; Wan Chi Cheong David; Yun-Gen Miao (Molecular Biology Reports, 2009)

Inhibition of hepatitis B virus replication by small interference RNA induces expression of MICA in HepG2.2.15 cells - Kai-Fu Tang; Min Chen; Jing Xie; Guan-Bin Song; Yi-Song Shi; Qi Liu; Zhe-Chuan Mei; Alexander Steinle; Hong Ren (Medical Microbiology and Immunology, 2009)

Manganese superoxide dismutase expressed in silkworm larvae, Bombyx mori L enhances the NK activity and splenocyte proliferation against Sarcoma 180 tumor cells in vivo - Wan-Fu Yue; Min-Li Yao; Jian-Mei Liu; Guang-Li Li; Xing-Hua Li; Xiao-Feng Wu; Wen Deng; Hong-Xiang Sun; Ji-Yong Zhou; Chuan-Xi Zhang; Yun-Gen Miao (Molecular Biology Reports, 2009)

Effects of silkworm larvae powder containing manganese superoxide dismutase on immune activity of mice - Wan-Fu Yue; Jian-Mei Liu; Guang-Li Li; Xing-Hua Li; Xiao-Feng Wu; Jian-Tong Sun; Hong-Xiang Sun; Yun-Gen Miao (Molecular Biology Reports, 2008)

Platinum-group minerals from the Jinbaoshan Pd–Pt deposit, SW China: evidence for magmatic origin and hydrothermal alteration - Christina Yan Wang; Hazel M. Prichard; Mei-Fu Zhou; Peter C. Fisher (Mineralium Deposita, 2008)

Abundant Fe–Ti oxide inclusions in olivine from the Panzhihua and Hongge layered intrusions, SW China: evidence for early saturation of Fe–Ti oxides in ferrobasaltic magma - Kwan-Nang Pang; Chusi Li; Mei-Fu Zhou; Edward M. Ripley (Contributions to Mineralogy and Petrology, 2008)

Interaction of magma with sedimentary wall rock and magnetite ore genesis in the Panzhihua mafic intrusion, SW China - Clément Ganino; Nicholas T. Arndt; Mei-Fu Zhou; Fabrice Gaillard; Catherine Chauvel (Mineralium Deposita, 2008)

Controls on variations of platinum-group element concentrations in the sulfide ores of the Jinchuan Ni-Cu deposit, western China - Shangguo Su; Chusi Li; Mei-Fu Zhou; Edward M. Ripley; Liang Qi (Mineralium Deposita, 2008)

Temporal and spatial distributions of dissolved organic carbon and nitrogen in two small lakes on the Southwestern China Plateau - Wen Li; Fengchang Wu; Congqiang Liu; Pingqing Fu; Jing Wang; Yi Mei; Liying Wang; Jianyang Guo (Limnology, 2008)

Treatment with proteasome inhibitor bortezomib enhances antigen-specific CD8+ T-cell-mediated antitumor immunity induced by DNA vaccination - Chih-Wen Tseng; Archana Monie; Chao-Yi Wu; Bruce Huang; Mei-Cheng Wang; Chien-Fu Hung; T.-C. Wu (Journal of Molecular Medicine, 2008)

Adrenal myelolipoma within myxoid cortical adenoma associated with Conn’s syndrome - Lu Hong-sheng; Gan Mei-fu; Chen Han-song; Huang Shan-qiang (Journal of Zhejiang University-SCIENCE B, 2008)

Chromosomal polymorphism of ribosomal genes in the genus Oryza - Mei-Chu Chung; Yung-I Lee; Yueh-Yun Cheng; Yi-Jia Chou; Chia-Fu Lu (Theoretical and Applied Genetics, 2008)

Origin of the Tongshankou porphyry–skarn Cu–Mo deposit, eastern Yangtze craton, Eastern China: geochronological, geochemical, and Sr–Nd–Hf isotopic constraints - Jian-Wei Li; Xin-Fu Zhao; Mei-Fu Zhou; Paulo Vasconcelos; Chang-Qian Ma; Xiao-Dong Deng; Zorano Sérgio de Souza; Yong-Xin Zhao; Gang Wu (Mineralium Deposita, 2008)

Loop-mediated isothermal amplification for rapid detection of Bacillus anthracis spores - Yan-Mei Qiao; Yong-Chao Guo; Xian-En Zhang; Ya-Feng Zhou; Zhi-Ping Zhang; Hong-Ping Wei; Rui-Fu Yang; Dian-Bing Wang (Biotechnology Letters, 2007)

Evaluation of dermal absorption and protective effectiveness of respirators for xylene in spray painters - Fu-Kuei Chang; Mei-Lien Chen; Shu-Fang Cheng; Tung-Sheng Shih; I-Fang Mao (International Archives of Occupational and Environmental Health, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Effects of moderate and severe intermittent hypoxia on vascular endothelial function and haemodynamic control in sedentary men - Jong-Shyan Wang; Liang-Yu Chen; Li-Lan Fu; Mei-Ling Chen; May-Kuen Wong (European Journal of Applied Physiology, 2007)

Prohibitin suppresses renal interstitial fibroblasts proliferation and phenotypic change induced by transforming growth factor-β1 - Wei Guo; Hong Xu; Jing Chen; Yong Yang; Jia Wei Jin; Rui Fu; Hai Mei Liu; Xi Liang Zha; Zhi Gang Zhang; Wen Yan Huang (Molecular and Cellular Biochemistry, 2007)

Genesis of the Permian Baimazhai magmatic Ni–Cu–(PGE) sulfide deposit, Yunnan, SW China - Christina Yan Wang; Mei-Fu Zhou (Mineralium Deposita, 2006)

Precise molybdenite Re–Os and mica Ar–Ar dating of the Mesozoic Yaogangxian tungsten deposit, central Nanling district, South China - Jiantang Peng; Mei-Fu Zhou; Ruizhong Hu; Nengping Shen; Shunda Yuan; Xianwu Bi; Andao Du; Wenjun Qu (Mineralium Deposita, 2006)

Soil microbial biomass as affected by non-flooded plastic mulching cultivation in rice - Yong-Shan Li; Liang-Huan Wu; Xing-Hua Lu; Li-Mei Zhao; Qiao-Lan Fan; Fu-Suo Zhang (Biology and Fertility of Soils, 2006)

Geochemical constraints on the origin of the Permian Baimazhai mafic–ultramafic intrusion, SW China - Christina Yan Wang; Mei-Fu Zhou; Reid R. Keays (Contributions to Mineralogy and Petrology, 2006)

Geochemistry of the Emeishan flood basalts at Yangliuping, Sichuan, SW China: implications for sulfide segregation - Xie-Yan Song; Mei-Fu Zhou; Reid R. Keays; Zhi-Min Cao; Min Sun; Liang Qi (Contributions to Mineralogy and Petrology, 2006)

Zircon U-Pb geochronology and elemental and Sr–Nd isotope geochemistry of Permian mafic rocks in the Funing area, SW China - Mei-Fu Zhou; Jun-Hong Zhao; Liang Qi; Wenchao Su; Ruizhong Hu (Contributions to Mineralogy and Petrology, 2006)

A fine physical map of the rice chromosome 5 - Chia-Hsiung Cheng; Mei-Chu Chung; Shu-Mei Liu; Shi-Kuang Chen; Fang-Yi Kao; Shu-Jen Lin; Shin-Hsin Hsiao; I-Chieh Tseng; Yue-Ie C. Hsing; Hong-Pang Wu; Ching-San Chen; Jei-Fu Shaw; et al. (Molecular Genetics and Genomics, 2005)

Controllable Regioselective Acylation of Rutin Catalyzed by Enzymes in Non-aqueous Solvents - Yong-mei Xiao; Qi Wu; Wei-bo Wu; Qing-yi Zhang; Xian-fu Lin (Biotechnology Letters, 2005)

Geochemistry and petrogenesis of the Yishak Volcanic Sequence, Kudi ophiolite, West Kunlun (NW China): implications for the magmatic evolution in a subduction zone environment - Chao Yuan; Min Sun; Mei-Fu Zhou; Wenjiao Xiao; Hui Zhou (Contributions to Mineralogy and Petrology, 2005)

Molecular Cloning and Expression of IL2 cDNA from the Tibet Pig - Li Hui; Gao Rong; Wu Mei; Wang Li-Huan; Fu Man-Liang; Wu Kai-Yuan (Veterinary Research Communications, 2005)

Ni?Cu?(PGE) magmatic sulfide deposits in the Yangliuping area, Permian Emeishan igneous province, SW China - Xie-Yan Song; Mei-Fu Zhou; Zhi-Min Cao; Min Sun; Yun-Liang Wang (Mineralium Deposita, 2003)

Absence of Archean basement in the South Kunlun Block: Nd‐Sr‐O isotopic evidence from granitoids - Chao Yuan; Min Sun; Mei‐Fu Zhou; Hui Zhou; Wenjiao Xiao; Jiliang Li (Island Arc, 2003)
The West Kunlun mountain range along the northwestern margin of the Tibetan Plateau is crucial in understanding the early tectonic history of the region. It can be divided into the North and South Kunlun Blocks, of which the former is considered to be part of the Tarim Craton, whereas consensus was not reached on the nature and origin of the South Kunlun Block. Samples were collected from the 471 Ma Yirba Pluton, the 405 Ma North Kudi Pluton and the 214 Ma Arkarz Shan Intrusive Complex. These granitoids cover approximately 60% of the Kudi area in the South Kunlun Block. Sr, Nd, and O isotope compositions preclude significant involvement of mantle‐derived magma in the genesis of these granitoids; therefore, they can be used to decipher the nature of lower–mid crust in the area. All samples give Mesoproterozoic Nd model ages (1.1–1.5 Ga) similar to those of the exposed metamorphic complex of this block but significantly different from those of the basement of the North Kunlun Block (2.8 Ga). This indicates that the South Kunlun Block does not have an Archean basement, and, thus, does not support the microcontinent model that suggests the South Kunlun Block was a microcontinent once separated from and later collided back with the North Kunlun Block.

Molecular mapping of S-c, an F1 pollen sterility gene in cultivated rice - Chuxiong Zhuang; Yan Fu; Guiquan Zhang; Mantong Mei; Yonggen Lu (Euphytica, 2002)

Origin of a large breccia-vein system in the Sanerlin uranium deposit, southern China: a reinterpretation - Jian-Wei Li; Mei-Fu Zhou; Xian-Fu Li; Zi-Jin Li; Zhao-Ren Fu (Mineralium Deposita, 2002)

Platinum-group element geochemistry of the Hongge Fe–V–Ti deposit in the Pan-Xi area, southwestern China - Hong Zhong; Xin-Hua Zhou; Mei-Fu Zhou; Min Sun; Bing-Guang Liu (Mineralium Deposita, 2002)

The types of lake in Songnen Plain and their regional character - Jin-fu Lu; Dong-mei Jie; Zhi-min Li; Xue-tian Leng (Chinese Geographical Science, 2000)

Comparative study of platinum‐group elements in the Coto and Acoje blocks of the Zambales Ophiolite Complex, Philippines - Mei‐Fu Zhou; Graciano P. Yumul; John Malpas; Min Sun (Island Arc, 2000)
The Zambales Ophiolite Complex (ZOC), Philippines, includes two geochemically distinct, ophiolitic assemblages: the high‐Al chromitite‐bearing Coto Block and high‐Cr chromitite‐bearing Acoje Block. This paper reports a comparative platinum‐group element (PGE) study of these two blocks. The PGE data were obtained using Ni‐sulfide fire assay preconcentration combined with inductively coupled plasma mass spectrometry (ICP‐MS) measurement. Podiform chromitites in the Acoje Block have higher Cu, Ir, Ru and Rh contents than their equivalents in the Coto Block, although chromitites from both have similar Pt and Pd contents. The PGE mantle‐normalized patterns of dunites from the two blocks are also different: dunites from the Coto Block are depleted in Pt, whereas those from the Acoje Block have a relatively flat pattern. The data demonstrate that Coto and Acoje Blocks have different origins in terms of their source region and partial melting processes. This study implies that the ZOC is a paired ophiolite belt formed in an island arc and back‐arc basin environment.

Comparative study of platinum-group elements in the Coto and Acoje blocks of the Zambales Ophiolite Complex, Philippines - Mei-Fu Zhou; Graciano P. Yumul; John Malpas; Min Sun (Island Arc, 2000)

High-level expression of Trigonopsis variabilis D-amino acid oxidase in Escherichia coli using lactose as inducer - Tzann-Shun Hwang; Hui-Mei Fu; Long-Liu Lin; Wen-Hwei Hsu (Biotechnology Letters, 2000)